A probabilistic framework for seismic resilience assessment of shield tunnels under mainshock-aftershock sequences in locally liquefiable sites - Xiaoyu Zhang; Xiating Li; Yingyi Pan; Yi Zhang; Tao Li; Hai Liu; Jie Cui (Tunnelling and Underground Space Technology, 2026)

Dopamine-Zein synergistic coating for PMP hollow fiber membranes with enhanced biocompatibility and performance in MABR - Fangli Zhang; Chenyang Gu; Yinchao Jin; Rizhi Chen; Dan Li; Jun Pan; Zhaohui Wang; Zhaoliang Cui (Desalination, 2026)

Pro-developmental role of AMPK–PINK1/Parkin-mediated mitophagy in the morula-to-blastocyst transition during early embryonic development: Dual-omics evidence for the beneficial effects of GSH - Tianhao Li; Xuefeng Bai; Yuejiao Liao; Qiyong Zuo; Xin Liu; Yan Cui; Sijiu Yu; Yangyang Pan (Theriogenology, 2026)

Combined exposure to wildfire ash and road salts reshapes skin and gut microbiota and reduces fitness in amphibians - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Yue-liang Pan; Wen-jing Dong; Ming-da Xu; Zhi-wen Luo; Li-yong Cui (Environmental Research, 2026)

Microtopographic and runoff-sediment responses to check-dam configurations under consecutive rainfall: Laboratory experiments in a simulated loess watershed - Zhiwei Cui; Peng Li; Shengde Yu; Songsong Ling; Chenyang Li; Jianchun Han; Chaoya Zhang; Jingjing Pan; Huiyuan Zhang; Shu Yu (CATENA, 2026)

Development of therapeutic PD-1 monoclonal antibodies for treatment of canine tumor - Jinquan He; Xuan Yin; Anqi Xie; Ning Wang; Zeming Guo; Yizhou Chen; Weidong Cui; Xueqiao Qian; Chungen Pan (Veterinary Immunology and Immunopathology, 2026)

Study on the size effect model of mode I fracture characteristics in Longmaxi formation shale based on DIC and acoustic emission technology - Yu Suo; Xian-hang Wei; Gui-quan Wang; Cui-long Kong; Guang-chao Zhang; Xi Chen; Xiaofei Fu; Zhe-jun Pan; Bin Huang (Soil Dynamics and Earthquake Engineering, 2026)

Iron sulfide decorated ramie fiber-derived biochar for efficient Cr(VI) removal from water: Synergistic mechanisms of adsorption, reduction, and co-precipitation - Chengrui Shao; Luyao Gong; Liangxia Kong; Boyan Cui; Lifeng Xu; Xu Deng; Yuwei Deng; Qiang Li; Jun Wan; Yuxuan Ye; Fei Pan (Journal of Water Process Engineering, 2026)

Multi‑dimensional mechanistic insights into sludge deep dewatering via electro-mechanical pore elasticity (EMPE) modeling and experiments in multistage pressurized electro-osmotic oxidation - Xiaojie Cui; Chuzhan Jin; Junjie Feng; Shanshan Wei; Chunying Dong; Weichun Pan; Micong Jin; Meiqiang Cai (Journal of Environmental Chemical Engineering, 2026)

Endogenous impurity regulation in solid waste-derived hydroxyapatite: From single-phase defects to in-situ multiphase reconstruction - Qingning Bai; Tongyu Liu; Xiaoyan Zhao; Zhiyu Chen; Shuo Cui; Jiayu Feng; Rui Cao; Zibin Pan; Ping Ning; Lijuan Jia; Fang Wang (Journal of Environmental Chemical Engineering, 2026)

Future mercury emissions from coal-fired power plants in China under dual-carbon targets: An emission-driven sensitivity assessment integrating machine learning and GEOS-Chem modeling - Hongyan Zhang; Chao Pan; Tianzhi Geng; Na Zhang; Qinhao Cui; Yi Wei; Jianbing Jin; Jianling Fan (Environmental Pollution, 2026)

Optimized decarbonization pathway coupled with carbon trading mechanism for China's steel industry towards carbon neutrality - Jingchao Sun; Hongming Na; Honggang Pan; Tao Du; Yuxing Yuan; Ziyang Qiu; Lei Zhang; Yingnan Li; Jie Cui; Yong Sun (Energy Policy, 2026)

Probabilistic seismic resilience assessment integrating optimal IM selection and system-level fragility analysis: Case study of submarine tunnel - Yingyi Pan; Xiaoyu Zhang; Hai Liu; Jie Cui (Tunnelling and Underground Space Technology, 2026)

Climate–morphology dual regulation of urban land surface temperature: A multi-scale decomposition of driving mechanisms within a baseline–restructuring–fine-tuning framework - Wenguang Xiang; Shuangyun Peng; Fucheng Cai; Juexian Dong; Zhiqiang Lin; Xingqiang Feng; Xianchun Pan; Weihang Wang; Biting Cui; Fapeng Cai (Sustainable Cities and Society, 2026)

Site-specific associations between soil methylmercury accumulation and plant, soil, and hgcA-associated microbial modules across Chinese coastal wetlands - Yuechen Tan; Weiwei Liu; Xu Pan; Songyuan Long; Yukun Hu; Lijuan Cui; Manyin Zhang (Journal of Hazardous Materials, 2026)

Flower-like CoNi-LDH/PtNPs composites for highly efficient electrochemical sensing of methyl parathion in vegetables - Yibo Song; Jingjing Cui; Chunlei He; Jing Cao; Huilin Li; Wenjing Zhao; Mingfei Pan; Shuo Wang (Food Chemistry, 2026)

Combined application of 1-methylcyclopropene and silicon-window modified atmosphere packaging delays cell wall degradation and softening in cold-stored ‘Saiwaihong’ apples - Cheng Zhao; Jiefen Cui; Hao Wu; Xuanming Tang; Xueping Wang; Mengyu Ma; Ting Liu; Yanfang Pan; Jinkai Zheng (Food Chemistry, 2026)

Recovery trajectories of amphibian skin microbiota following ash exposure across translocation and natural recovery scenarios - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Ming-da Xu; Yue-liang Pan; Li-yong Cui (Environmental Pollution, 2026)

Machine learning–fugacity framework reveals the fate and environmental drivers of per- and polyfluoroalkyl substances in a mountainous river - Yanan Li; Wenjing Lv; Jiao Ren; Jianhui Tang; Jiayin Dai; Qiusheng He; Yang Cui; Lijuan Huo; Ke Zhang; Yitao Pan (Environmental Pollution, 2026)

Fluid-like polarization rotation in interpenetrating diffuse phase boundary for dielectric capacitors - Ya Yang; Yawen Cui; Linqiong Xu; Jiarong Lv; Dingheng Lin; Bing Kong; Jinjun Liu; Ning Liu; Zhongbin Pan (Chemical Engineering Journal, 2026)

Structure characterization and multi-target inhibitory activities of fucosylated chondroitin sulfate from sea cucumber Thelenota anax - Ying Hong; Ying Pan; Guangyu Zhu; Jing Wen; Rou Chen; Lige Cui; Huilin Chen; Tong Wu; Ronghua Yin; Jinhua Zhao (Carbohydrate Polymers, 2026)

The histone methyltransferase SETD2 regulates the PI3K/AKT signaling pathway to affect the in vitro fertilization of yak oocytes - Qiyong Zuo; Hui Zhang; Donglan Zhong; Tianhao Li; Yuejiao Liao; Yangyang Pan; Sijiu Yu; Yan Cui (Animal Reproduction Science, 2026)

A pH-regulated single-material fluorescence sensor array with tunable response patterns for discrimination and quantification of Hg(II), Cr(VI), and Mn(VII) - Zhenhua Yang; Jiamin Zhou; Pan Du; Xuyan Cui; Quanxi Zhang; Xianyun Zheng; Chuan Dong; Yuexia Zhang (Analytica Chimica Acta, 2026)

Quantifying seasonal stem water-related radial variations in Larix gmelinii var. principis-rupprechtii and Picea meyeri in a sub-alpine habitat, North-Central China - Feng Xue; Yuan Jiang; Enzai Du; Minghao Cui; Xiaochuan Wang; Xinyang Shi; Hongkun Cui; Aolin Li; Ning Pan; Muyi Kang; Jingze Liu (Agricultural and Forest Meteorology, 2026)

Vertical geochemical characteristics and coupling effects on organic carbon stability in coastal sediments of the Yellow Sea, China - Limin Cui; Mingxiang Pan; Yanru Shao; Manqing Cheng; Zizhen Qi; Xin Fang; Yang Yang; Lei Gao (Acta Oceanologica Sinica, 2026)

AGSMamba: adjacent grouped Mamba with Fourier enhancement for hyperspectral image classification - Jinglong Wang; Zihao Cui; Xuegong Li; Haoran Zhao; Chao Pan (International Journal of Remote Sensing, 2026)

Aeolian transport of evaporite minerals in Utopia Planitia: insights from Qaidam Basin spectral analogs - Jianxun Shen; Honglei Lin; Zhaopeng Chen; Xue Guo; Yuqi Wang; Yizhong Zhang; Li Liu; Chengxiang Huang; Enze Wang; Rui Chang; Xuesen Xu; Zhicheng Cui; et al. (Science Bulletin, 2026)

A comprehensive review on dealkalization from red mud: Driving mechanism, phase reconstruction and future prospects - Xiaolong Liu; Jilong Liu; Can Cui; Tengfei Zhang; Kun Yan; Lijuan Qi; Wanchao Liu; Haiyan Yu; Xiaolin Pan (Process Safety and Environmental Protection, 2026)

Taurine attenuates heat stress-induced intestinal permeability by inhibiting endoplasmic reticulum stress and modulating gut microbiota - Haoran Jiang; Fan Mo; Zhuobin Pan; Chong Wang; Yanjun Cui (Journal of Thermal Biology, 2026)

Spatial distribution of per- and polyfluoroalkyl substances in the Yellow River basin: Role of suspended sediment on the PFAS partition and accumulation - Yanan Li; Yawen Li; Yitao Pan; Wenjing Lv; Fengfeng Dong; Qiusheng He; Lijuan Huo; Yang Cui; Ke Zhang; Jiayin Dai; Jianhui Tang (Journal of Hazardous Materials, 2026)

Key commensal bacteria and dietary components promoting Faecalibacterium prausnitzii growth - Yun Guo; Pan Huang; Gang Wang; Shumao Cui; Wenwei Lu; Xiaomei Lv; Peijun Tian; Jianxin Zhao; Wei Chen; Qixiao Zhai (Food Bioscience, 2026)

Experimental study on clay brick masonry wall retrofitted with sandwich panels containing polyurea under blast loading - Yanchao Shi; Yaqi Pan; Jian Cui; Ou Zhao (Engineering Structures, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

Lifetime burden of congenital heart disease from 1990 to 2021: a systematic analysis from the Global Burden of Disease Study 2021 - Meng-Yi Liu; Yue Cui; Lu-Hong Qiu; Jia-Xing Zhang; Su-Xin Zhang; Jie-Ling Ma; Hong Pan; Jie-Xin Zhang; Wei-Guo Ma; Ji-Mei Chen; Zhi-Cheng Jing (Science China Life Sciences, 2026)

Dimethyl fumarate ameliorates quinolinic acid-induced ageing and neurodegeneration in Caenorhabditis elegans - Yi Sun; Ke Zhou; Jiaorong Cui; Haoxuan Ding; Iqra Shareef; Liuliang Du; Zhen Shi; Linlin Fu; Fenfen Sun; Zuobin Zhu; Wei Pan (Biogerontology, 2026)

Genotypic features of Spinocerebellar Ataxia in Northern China: A Comparative Analysis with Southern China - Bin Chen; Songtao Niu; Xingao Wang; Yutin Ren; Fan Jian; Yuzhi Shi; Hongfei Tai; Hengheng Wang; Zhan Wang; Tao Cui; Wei Li; Hua Pan; et al. (The Cerebellum, 2026)

Artificial Intelligence and Protein Design: A retrospective study on 20-year emerging trends and core research areas from bibliometric perspectives - Wenjuan Zhao; Xiuwu Pan; Wei Yang; Zichang Liu; Xiyi Wei; Anqi Lin; Bufu Tang; Lin Zhang; Mingjia Xiao; Qing Zeng; Quan Cheng; Weiming Mou; et al. (Probiotics and Antimicrobial Proteins, 2026)

A Near-Infrared Fluorescent Probe Based on Naphthalimide for Lysosomal Hydrogen m n;. - Ning Cui; Junhong Xu; Shuqi Hou; Yiqiao Liu; Guojiang Mao; Congjie Pan; Qiujuan Ma (Journal of Fluorescence, 2026)

Editorial Expression of Concern: Knockdown of NOB1 expression inhibits the malignant transformation of human prostate cancer cells - Xiangmin Zhang; Dongxu Zhang; Fajun Qu; Yi Hong; Jianwei Cao; Xiuwu Pan; Lin Li; Yi Huang; Hai Huang; Lei Yin; Lu Chen; Jizhong Ren; et al. (Molecular and Cellular Biochemistry, 2026)

A data-driven life cycle assessment of battery swapping for electric two-wheelers: A multi-city operational perspective - Qian Zhang; Wei Liu; Xiaowei Cui; Xin Pan; Lu Chen; Wangqiu Liu; Yuwei Zhao; Liyao Wang; Mingxue Zhang; Lijun Ren; Zhaojie Cui (Sustainable Production and Consumption, 2026)

Resource-efficient numerical computing and elastic wave behavior analysis in complex poroelastic media - Zhitao Zhang; Yuhang Guo; Zhuwen Wang; Baozhi Pan; Yibo Wang; Lin Gan; Wubing Wan; Zhaoqi Sun; Wenqiang Wang; Ruiyi Han; Jiaxu Guo; Yitong Cui (Computers and Geotechnics, 2026)

Artemisinin derivative SM934 targets α-enolase to inhibit PEP-mediated TAK1 stabilization and inflammation - Jun Pan; Yuwei Zhang; Zhiwei Du; Yuanyuan Huang; Yu Wang; Miya Su; Yuting Cai; Weiya Xu; Lili Chen; Chengdong Huang; Di Cui; Dongsheng Chen; et al. (Science China Life Sciences, 2026)

Single-epoch PPP-RTK with multi-frequency multi-constellation: reliable and instantaneous centimeter-level user positioning - Pan Li; Jiadi Dai; Jiahuan Hu; Xiaohong Zhang; Bobin Cui; Bao Shu; Guanwen Huang; Qin Zhang (Advances in Space Research, 2026)

Orthosilicic acid in functional foods: bioavailability, metabolism, and potential in degenerative disease prevention - Rongzeng Pan; Jia Zeng; Xiaojun Wang; Biyan Cui; Chuanling Deng; Xiaoguang Xu; Zhen-Yu Chen; Hanyue Zhu (Critical Reviews in Food Science and Nutrition, 2026)

Houpu Sanwu decoction alleviates rat intraperitoneal adhesion by regulating macrophage polarization and inhibiting inflammatory responses - Mei Liu; Quanxin Chen; Yan Cui; Tianming Wang; Qun Li; Zhihang Wu; Richeng Li; Yuan Tang; Haibang Pan (Tissue and Cell, 2026)

Effects of check dam construction on runoff–sediment processes and sediment deposition patterns in small watersheds under continuous rainfall conditions - Zhiwei Cui; Peng Li; Tian Wang; Chenyang Li; Songsong Ling; Jingjing Pan; Shengde Yu; Chaoya Zhang; Jianchun Han; Shu Yu (Journal of Hydrology, 2026)

Reaction mechanisms and catalyst design principles of MOFs and their derivatives in the electrocatalytic nitrate reduction for ammonia production - Huaiyu Zhou; Qing Wang; Yan Pan; Shuo Pan; Da Cui; Jingru Bai (Journal of Environmental Chemical Engineering, 2026)

Synergistic pore-acidity engineering in hierarchical H-beta zeolites for molecular sieving of ethylcyclohexane - Xue Ma; Xianjie Wang; Jinhui He; Jingdong Gou; Yaning Zhao; Akang Liu; Shuo Feng; Louwei Cui; Huiyong Chen; Jun Yang; Liuyi Pan; Dong Li (Fuel, 2026)

Potential of supramolecular solvent-based extraction for decontamination of volatile organic compounds in mechanically recycled polyethylene terephthalate - Jinxin Liang; Tianlong Zhang; Can Xu; Jingjing Pan; Huai-Ning Zhong; Qizhi Su; Anqi Cui; Hanke Li; Dan Li; Ben Dong (Food Packaging and Shelf Life, 2026)

Employing L-cysteine-mediated modulation for nickel biorecovery: Bioseparation-photocatalytic upcycling from wastewater - Shunling Li; Peng Cui; Zhaosheng Zhang; Fenxiang Li; Pan Bo; Qing Qu (Environmental Research, 2026)

Ubiquitous and remarkable tire-derived chemicals (TDCs) contamination in road-related environmental receptors across the Tibetan plateau - Qianyuan Yang; Wei Zhou; Qiangying Zhang; Wenxiao Pan; Xiaomei Cui; Yuting Dong; Jifu Liu; Chuanlong Zhang; Duo Bu; Aiqian Zhang; Jianjie Fu; Guibin Jiang (Environmental Research, 2026)

Diagnosing interaction between vegetation greening and terrestrial water storage changes in the arid and semi-arid Mongolian plateau - Jiahe Cui; Yun Pan; Yuchi Wang; Chong Zhang (CATENA, 2026)

Designing the Next Generation of Endolysins: A Triple Strategy Integrating Bioinformatics Mining, Engineering Modification and Encapsulation Formulation - Yongkang Zhang; Xinge Cui; Luwei Chai; Yangwei Pan; Ying Yang; Hongbing Liu; Xingying Mou; Tao Le (Probiotics and Antimicrobial Proteins, 2026)

Integrating elite selection and micropropagation: a production line for early-stage domestication of Vaccinium bracteatum - Chuizheng Xia; Muhammad Junaid Rao; Ying Wu; Yuanyuan Li; Xuefeng Wang; Weicong Hong; Mengxue Wang; Yihong Jin; Jiani Zhu; Xuan Yu; Haidi Yuan; Jiao Wang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Imbalanced Si:N Alters Lipid Production and Photosynthesis in the Marine Diatom Phaeodactylum tricornutum and Dinoflagellate Prorocentrum donghaiense - Jiaxuan Cui; Chuanli Zhang; Rong Bi; Yunyun Zhuang; Xiaoqian Pan; Xiao Qin; Zhong Cao; Hailong Zhang; Li Li; Yang Ding; Meixun Zhao (Journal of Ocean University of China, 2026)

Early Paleozoic Affiliation between South China Block and Gondwana Revealed by Early Silurian Remagnetization - Min Zhang; Yan Liu; Huafeng Qin; Jinhua Li; Yifei Hou; Bitian Wei; Wei Liu; Linhao Cui; Xingliang Zhang; Chenglong Deng; Yongxin Pan (Journal of Earth Science, 2026)

A novel pretreatment strategy for non-aggressive chromium speciation based on a sole bifunctional magnetic ion-imprinted nanocomposite with mild freezing grinding - Yi-Fan Pan; Sen Zhang; Jing Yang; Xiao-Bing Cui; Hong-Zhen Lian (Analytica Chimica Acta, 2026)

Cover Image - Yinnan Mu; Weini Zhang; Pan Qin; Wenxing Li; Zhengwei Cui; Yang Ding; Jingqun Ao; Jiangtao Gao; Xinhua Chen (Reviews in Aquaculture, 2026)
The cover image is based on the article Elucidating the Immunological Basis of Large Yellow Croaker Larimichthys crocea Offers New Strategies for Its Disease Management by Yinnan Mu et al., https://doi.org/10.1111/raq.70164 . image

Elucidating the Immunological Basis of Large Yellow Croaker Larimichthys crocea Offers New Strategies for Its Disease Management - Yinnan Mu; Weini Zhang; Pan Qin; Wenxing Li; Zhengwei Cui; Yang Ding; Jingqun Ao; Jiangtao Gao; Xinhua Chen (Reviews in Aquaculture, 2026)
Large yellow croaker Larimichthys crocea is a major mariculture species in China, achieving an annual yield of 292,615 tons by 2024. Commercial production faces considerable challenges from disease outbreaks, necessitating comprehensive immune mechanism research. Through comprehensive genomic and transcriptomic investigations, scientists have identified distinguishing characteristics within the L. crocea immune system, encompassing robust innate defense mechanisms, marked by the expansion of pattern recognition receptor lineages, antimicrobial peptide gene families, and antiviral defense‐related genes, and well‐developed adaptive immune capabilities. The current review outlines the molecular foundations underlying immune responses in L. crocea , highlighting the cooperative interplay between innate and adaptive defense systems when confronting pathogenic threats and environmental fluctuations. It bridges basic scientific inquiry with practical aquaculture implementation, exploring disease control strategies. Available evidence indicates possibilities for strengthening disease resistance through precision immunomodulation and improved aquaculture methods. Priority research areas encompass elucidating host‐pathogen relationships and establishing practical disease prevention protocols for industrial‐scale operations.

Two-dimensional experimental study on the degradation of soil arching effect considering foundation expansion - Xianfeng Liu; Gaofeng Pan; Shengyang Yuan; Haibin Xu; Yibo Wang; Zhongdong Cui; Shiqiang Song; Guanlu Jiang (Transportation Geotechnics, 2026)

A colorimetric and NIR fluorescent dual-mode probe based on xanthene-quinoline conjugate for detecting mercury ion in water/soil/seafood samples, living cells and mice - Dai Zeng; Pan Pan; Bin Zhang; Jing Wang; Ao Shen; Aiping Xing; Jixian Cui; Jiaxing Lu; Yuanlin Li; Juan Yuan (Journal of Hazardous Materials, 2026)

Valorization of industrial carbide slag via microwave processing: A low-cost route to high-performance CaO-based CO2 sorbents - Fang Wang; Yi Dong; Shaojun Luo; Zixia Tian; Shuo Cui; Rui Cao; Zibin Pan; Ping Ning; Futing Xia; Jiayu Feng; Lijuan Jia (Journal of Environmental Management, 2026)

Natural deep eutectic solvents (NADESs) as cryoprotectant for Lactiplantibacillus plantarum YR07: antifreeze mechanisms and applications - Sha sha Zheng; Li jun Tan; Qiong Pan; Yu fei Zhang; Wen di Zhang; Li fang Zou; Wei Cui; Yu Zhou; Ying ying Hu; Bao cai Xu (Food Research International, 2026)

Impact of node restriction on Cd and Zn transportation in wheat plant treated with swine manure and its biochar: a field experiment - Zhonghua Cui; Yu Pan; Zhangtao Li; Jian Liu; Alexandru Ozunu; Jun Meng; Kiril Manevski; Shengdao Shan (Food Chemistry, 2026)

Mining and characterization of novel prolyl endopeptidases from human gut microbes for degrading the immunogenic gluten 33-mer peptide - Xiaojing Zhou; Pan Huang; Chuan Zhang; Chengcheng Zhang; Gang Wang; Shumao Cui; Wenwei Lu; Bo Yang; Junjun Wu; Xiaomei Lyu; Fengwei Tian; Jianxin Zhao; et al. (Food Bioscience, 2026)

First investigation into occurrence, trophodynamics, and risk implication of polychlorinated naphthalenes and polychlorinated biphenyls in a terrestrial food chain from Tibetan Plateau - Siyuan Xiong; Wenxiao Pan; Duo Bu; Kai Huang; Boyuan Hu; Shuyi Shen; Qiangying Zhang; Zeng Dan; Xiaomei Cui; Yingming Li; Guorui Liu; Qinghua Zhang; et al. (Environmental Pollution, 2026)

Sweat-responsive natural small-molecule-based co-assembled hydrogels: multifunctional properties, transdermal delivery, and potential for hyperhidrosis therapy - Mingping La; Jiamei Le; Chunxia Yin; Pan Cheng; Fen Ju; Xiaohong Zhu; Cui Li (Chemical Engineering Journal, 2026)

Nano-delivery system of milk-derived exosomes loaded with Forsythiaside A: Studies on bovine mammary epithelial cells and mastitis induced mice - Xiaoqing Yang; Yangyang Pan; Meng Wang; Xin Ma; Xiaohong Han; Tianhao Li; Shanshan Yang; Jianying Chang; Hanxun Liu; Sijiu Yu; Yan Cui (Theriogenology, 2026)

Robust oxygen reduction electrocatalysis via dioxygen-bridged cobalt diatomic sites scaffolded by hierarchically porous nanoarchitectures - Ran Jin; Xiaoxue Xu; Yu Xia; Yanqun Shi; Jiaojiao Wu; Mingjie Wu; Yuchao Pan; Xun Cui; Wendan Xue; Yingkui Yang (Science Bulletin, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Single-frame motion vector imaging with phonon-engineered perovskite optoelectronic synapses for neuromorphic visual perception - Hao Wang; Tianhua Liu; Yongle Pan; Junjie Zhou; Junfang Wang; Xu Wang; Shiwei Zhang; Enhao Cui; Shuyang Wang; Ziquan Yuan; Zengsheng Li; Yashuai Qi; et al. (Science Bulletin, 2026)

Synergistic utilization of circulating fluidized bed fly ash and pulverized fly ash in low-carbon solid waste cementitious materials: Performance and hydration mechanism - Jianmin Li; Liwen Guo; Ye Li; Jiayong Zhang; Cheng Zhang; Hui Pan; Xiao Cui; Xiaofan Zhao (Journal of Environmental Chemical Engineering, 2026)

Tripolyphosphate-enhanced Fe-C promotes O2 activation for bisphenol A removal: Roles of tripolyphosphate and dominant reactive oxygen species - Xiang Li; Mengke Zhang; Huajing Song; Qingge Cui; Yuwei Pan; Zhenglong Li; Wei Zou (Journal of Environmental Chemical Engineering, 2026)

Plantaricin-producing Lactiplantibacillus plantarum NDF28B2 as an adjunct culture enhances fermented Milk texture and suppresses Listeria monocytogenes - Nan Xiao; Yang Liu; Chengcheng Zhang; Chuan Zhang; Pan Huang; Gang Wang; Shumao Cui; Wenwei Lu; Bo Yang; Junjun Wu; Xiaomei Lyu; Fengwei Tian; et al. (Food Research International, 2026)

PtPdRu nanozyme relay catalysis: Toward a portable and multimode platform for thiamethoxam detection - Binbin Zhang; Wentao Zhang; Zhuoying Pu; Junwei Cui; Jun Xu; Xiaohu Wu; Fengshou Dong; Yongquan Zheng; Xinglu Pan (Chemical Engineering Journal, 2026)

Complete upcycling of iron phosphate slag via ammonium sulfide: Synchronous recovery of phosphorus, Fe7S8/C catalyst, and elemental sulfur - Shaoxiang Yang; Fei Zhang; Yikun Li; Fang Wang; Jiayu Feng; Shuo Cui; Rui Cao; Zibin Pan; Ping Ning; Lijuan Jia (Chemical Engineering Journal, 2026)

The performance and mechanism of sodium carboxymethyl cellulose in promoting the anaerobic ammonium oxidation coupled with Fe (III) reduction - Hong-Yan Meng; Shen Cui; Lei Yang; Yu-Chao Wang; Hao-Qi Lu; Dun Guo; Pan Liang; Jun Lan; Yong-Xiang Ren (Bioresource Technology, 2026)

Tracing fluid evolution forming multistage wolframite mineralization in vein-type tungsten (-tin) deposit: new insight from LA-ICP-MS analysis of fluid inclusion - Zhi-Lin Cheng; Jun-Yi Pan; Pei Ni; Li-Li Chen; Jian-Ming Cui; Zhe Chi; Jun-Ying Ding (Mineralium Deposita, 2026)

Synergy mechanisms of algal extracellular organic matter and manganese oxides in 17α-ethinylestradiol photochemical degradation - Zhicheng Liao; Huan He; Feiyuan Liu; Jingye Cui; Ziwei Guo; Al-Anazi Abdulaziz; Bin Huang; Hongwen Sun; Xuejun Pan (ENGINEERING Environment, 2026)

Monotonic and cyclic shear response of calcareous sand retrieved from South China Sea - Yang Wu; Neng Li; Fulin Zhou; Linxuan Pan; Xinzhi Wang; Jie Cui; Yamamoto Haruyuki; Liwei Wen; Weifeng Peng (Bulletin of Engineering Geology and the Environment, 2026)

Diversity loss of soil microbiome stimulates soil carbon emissions - Haibo Pan; Yingyi Fu; Hairong Tu; Yongxing Cui; Beibei Chen; Jiejun Qi; Ziheng Peng; Shi Chen; Chunling Liang; Jiai Liu; Xiaomeng Li; Min Gao; et al. (Soil Biology and Biochemistry, 2026)

Ethyl methanesulfonate (EMS) mutagenesis with cucumber pollens and a case study of the map-based gene cloning with EMS-induced mutants - Yachen Xiang; Haibing Cui; Linglong Fu; Xiaoxue Wang; Yuqing Zhou; Senyang Yao; Mimi Li; Hanqiang Liu; Yupeng Pan (Plant Science, 2026)

Rice husk ash-derived nano-silica: A sustainable carrier for Kasugamycin to combat rice blast disease - Ziqi Cui; Zhihao Li; Yufeng Wu; Huiyan Li; Xueping Guo; Aisha Khalfan Nassor; Zhi Chen; Xiong Guan; Xiaohong Pan; Yujiao Jia (Pesticide Biochemistry and Physiology, 2026)

Collagen type XV regulation via MMP2-dependent degradation governs ovarian development in the rice stem borer, Chilo suppressalis - Yue Li; Suijie Kuang; Yan Tang; Zhuotian Yao; Yechen Pan; Ziren Zang; Yang Cui; Hongshuai Gao; Lin Qiu; Yansong Xiao; Tin Liu; Qi Su; et al. (Insect Biochemistry and Molecular Biology, 2026)

High-value utilization of hazardous solid waste for efficient electrocatalytic oxygen reduction to produce hydrogen peroxide - Bo Liu; Xiaoshuang Song; Guoxin Mu; Jiayu Feng; Fang Wang; Rui Cao; Zibin Pan; Feixiang Lu; Ping Ning; Shuo Cui; Lijuan Jia (Environmental Research, 2026)

Characterization and biological activities of a high-yield galactosylated heparan sulfate from Bursatella leachii egg strings - Yan Ma; Ying Pan; Lutan Zhou; Lige Cui; Xuewen Wu; Mengchen Ji; Dilihumaer Ruzemaimaiti; Wenwen Ma; Haitian Wang; Linxia Chen; Weilie Xiao; Ronghua Yin; et al. (Carbohydrate Polymers, 2026)

An ICT-FRET Fluorescent Probe Derived from Coumarin-Naphthalimide for Ratiometric Detection of Copper Ions - Qiujuan Ma; Junhong Xu; Shuangyu Liu; Congjie Pan; Guojiang Mao; Ning Cui; Ruxue Xia (Journal of Fluorescence, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Elucidating the role of g-C₃N₄ nanostructural dimensionality in organosilica composite membranes for optimized molecular separation through pervaporation - Yuanliang Gu; Zinan Zhang; Shengshen Gu; Qi Zhang; Meng Guo; Yang Pan; Genghao Gong; Zhaoliang Cui; Xiuxiu Ren; Jing Zhong (Journal of Environmental Chemical Engineering, 2026)

Microstructure and flow in argillaceous silt hydrate-bearing sediments: Insights from SEM characterization and simulation - Lu Yu; Chenlu Xu; Hongfeng Lu; Guodong Cui; Jiyong Liu; Yinghua Lian; Xian Li; Rongrong Qi; Shansi Tian; Zhejun Pan (Gas Science and Engineering, 2026)

The multi-carboxyl metal-organic framework MIL-101(Fe) effectively adsorbs total purines from whole soybean seeds - Deshuai Shao; Cui He; Na Li; Yuqing Gao; Xiaoyu Hu; Yingrun Cai; Qinqin Zhang; Jiahui Yao; Shuo Wang; Yifan Yang; Jiayi Pan; Huihui Gao; et al. (Food Chemistry, 2026)

Distribution of folate synthesis genes in Lactobacillaceae and characterization of high folate production - Zhihao Chen; Chuan Zhang; Yiyi Li; Chengcheng Zhang; Pan Huang; Gang Wang; Shumao Cui; Wenwei Lu; Bo Yang; Qixiao Zhai; Fengwei Tian (Food Bioscience, 2026)

Pesticide residues in maize kernels: Monitoring and human dietary risk assessment - Longbing Wei; Xiaozhong Zhang; Xing Liang; Junwei Cui; Xinglu Pan; Xiaohu Wu; Jun Xu; Fengshou Dong; Yongquan Zheng (Food Control, 2026)

Effects of different iron compounds on the acclimation of Feammox sludge: Nitrogen-iron transformation, sludge physicochemical properties, and microbial communities - Pan Liang; Lei Yang; Yu-Chao Wang; Hao-Qi Lu; Dun Guo; Hong-Yan Meng; Shen Cui; Jun Lan; Yong-Xiang Ren (Environmental Research, 2026)

Iron and platinum alternating active sites for efficient photocatalytic overall water splitting - Yanfei Fan; Yan Liu; Ying Liang; Kang Chen; Qingqing Li; Dongxu Pan; Shiqiu Zhang; Guanwei Cui; Bo Tang (Chemical Engineering Journal, 2026)

Transforming Camellia oleifera meal into feedstuff: Enhancing value through detoxification and fermentation - Yiyan Cui; Yuheng Lei; Zhenming Li; Zhichang Liu; Min Song; Dun Deng; Zhimei Tian; Ting Rong; Pan Yang; Xianyong Ma; Miao Yu (Bioresource Technology, 2026)

Rapid excretion of raw microplastics and longer persistence of fragmented microplastics in the quail digestive system - Ziye Zhang; Ying Yang; Wenzhuo Shi; Wei Pan; Xiaoli Zhao; Song Cui; Lihui An (Environmental Chemistry Letters, 2026)

Identification and transcriptomic analysis of a new pathogen, Photobacterium damselae SCXP, associated with sea cucumber skin ulceration syndrome - Linwei Yang; Shuming Liu; Hui Lv; Haiyun Wei; Tong Wu; Bilian Lou; Jingsong Yang; Qingmei Huang; Yuxin Shi; Tongxin Lin; Zhengwei Cui; Xinhua Chen; et al. (Aquaculture, 2026)

Influence of interweaving configuration and impactor rotation on the performance of flexible rockfall barriers - Junyi He; Aiguo Xing; Yufang Zhang; Jian Cui; Bo Liu; Kun Yuan; Pan Chen (Transportation Geotechnics, 2026)

Spatiotemporal characteristics of RPL24 expression in the yak oviduct and its regulatory mechanism on epithelial cell proliferation via DDX3X/DDX5 - Yanhu Wang; Yangyang Pan; Rui Ma; Yuejiao Liao; Kangle Xian; Yan Cui; Sijiu Yu (Theriogenology, 2026)

Intensified NAO-South Asian Monsoon teleconnection during the Little Ice Age: Insights from speleothem records - Jingyao Zhao; Wen Liu; Liangkang Pan; Qiuqiu Luo; Jiahui Cui; Jian Wang; Kexin Wang; Hai Cheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Association between prenatal PFAS exposure and catch-up growth in children born with adverse outcomes: evidence from a prospective cohort study - Su-Qin Tan; Yan-Xi Li; Shao-Ya Huang; Shen-Pan Li; Qiong Zhang; Cui-Lan Tang; Ying-Chao Ye; Guang-Hui Dong; Jian Chen; Dan Cai; Xiao-Wen Zeng (Journal of Hazardous Materials, 2026)

Interplay between manganese and algal metabolism: From metabolic regulation to photochemical feedbacks via algal organic matter - Danni Cui; Yuan Gui; Ziwei Guo; Huan He; Xi Deng; Xi-Zhi Niu; Yu Luo; Bin Huang; Xuejun Pan (Journal of Hazardous Materials, 2026)

Occurrences of antibiotics and antimicrobial resistance in combined and separate sewage overflow effluents of Shanghai, China - Wujie Chen; Bingjie Cui; Zhuyu Sun; Ying Zhang; Pan Wang (Journal of Environmental Management, 2026)

Biochar and moisture variability shape soil carbon pools via microbial carbon-degrading genes - Yue Pan; Tingting Tan; Jie Meng; Hongpeng Guo; Yingbo Dong; Yukui Cui; Na Yu; Xinxin Jin; Yuling Zhang; Hongtao Zou; Nanthi Bolan; Kadambot H.M. Siddique (Journal of Environmental Management, 2026)

Satellite-observed first large-scale Sargassum bloom in the northern South China Sea - Longxiao Zheng; Xinliang Pan; Lin Qi; A Runa; Yanfang Xiao; Keunyong Kim; Rongjie Liu; Mengmeng Cao; Yanwei Song; Joo-Hyung Ryu; Tingwei Cui (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

The abfA gene cluster maintains microbial homeostasis by regulating the complexity and stability of the gut microbiome network - Bowen Zhu; Chengcheng Zhang; Chuan Zhang; Pan Huang; Gang Wang; Shumao Cui; Wenwei Lu; Bo Yang; Fengwei Tian; Qixiao Zhai (Food Bioscience, 2026)

Functionalized UiO-66-NO2 for selective separation of coal-derived C8 cyclohexane isomers: A dual mechanism of geometric confinement and electronic recognition - Xianjie Wang; Yaning Zhao; Hengsheng Wei; Yi Wang; Jingdong Gou; Jinhui He; Xue Ma; Louwei Cui; Liuyi Pan; Jiaojiao Liu; Dong Li (Chemical Engineering Journal, 2026)

Advanced oxidation coupled biodegradation for antibiotic treatment: A review of interaction mechanisms, latest developments and potential challenges - Wentao Pan; Peilin Li; Nanxi Song; Yiwen Cui; Yian Zheng (Chemical Engineering Journal, 2026)

Does a threshold of litter density exist for hillslope hydrological processes in typical plantations on the Loess Plateau? - Fengjiao Niu; Chengzhong Pan; Lan Ma; Yongsheng Cui; Chong Yu (CATENA, 2026)

Nitrogen sites induce homogeneous dispersion of iron species on biochar for enhanced hydrogen sulfide removal in a low-temperature anaerobic environment - Jiayu Feng; Fei Zhao; Huang Xiang; Fang Wang; Shuo Cui; Zibin Pan; Rui Cao; Ping Ning; Lijuan Jia (Bioresource Technology, 2026)

Research Progress on the Effects of Nanoparticles Extracellular Polymer Substances Corona Biological Function and Aquatic Environmental Behavior - Mei Pan; Yusen Diao; Guixiang Quan; Jinlong Yan; Liqiang Cui; Xiran Chen; Qi Li (Water, Air, & Soil Pollution, 2026)

Research on individual differences in risk preferences for personnel evacuation during flood disasters in underground spaces - Yixuan Wei; Mengcan Wang; Minrui Ni; Ying Cui; Tianmei Sun; Chunqing Wang; Song Pan (Natural Hazards, 2026)

Simulation of the impact of the carbon peak target allocation method on the energy structure of electricity generation—based on electricity market equilibrium modeling - Qing Xu; Jue Cui; Feng Dong; Yuling Pan (Clean Technologies and Environmental Policy, 2026)

Spatial and temporal evolution of wetland ecological quality in the Yellow River Delta: a comprehensive analysis based on multi-temporal remote sensing and improved ecological indices - Ruifeng Liu; Lansong Lv; Yurong Cui; Wenxin Pan; Xiulong Zhang; Juan Fu (Advances in Space Research, 2026)

In situ isolation of haloalkaliphilic microalga from the Yellow River Delta: enhancing legume crop resilience under saline-alkali stresses - Xiaoli Zhu; Minmin Xu; Jiahao Liang; Shenkun Liu; Xiao Yu; Yanpeng Pan; Guangwen Zhu; Xiaojing Wang; Jianchao Yang; Kang Wang; ZhiHai Zhong; Chenggang Ren; et al. (Algae, 2025)
Coastal saline-alkaline soils in China's Yellow River Delta represent vital yet underutilized arable reserves, where crop productivity is severely constrained by dynamic salinity-alkalinity stress, compounded by the scarcity of native stress-adapted biological resources for sustainable remediation. This study addressed this critical gap through in situ isolation of a novel halo-alkaliphilic microalga from saline waters, identified as Desmodesmus sp. R1108 via morphological characterization (distinctive single/quad-cell palisade structures; 8 × 4–6 μm cells) and molecular phylogeny. The strain exhibited unprecedented alkaliphilic traits, demonstrating 35% enhanced growth at 100 mM NaHCO3 while tolerating pH 10.0. Crucially, soil irrigation with live cells significantly boosted Sesbania cannabina resilience across multiple stress regimes: germination rates surged 47% under 200 mM NaCl, plant height increased 42% under 200 mM NaHCO3 , and root biomass rose 56% under neutral salt stress—representing a novel application of a locally isolated, halo-alkaliphilic microalga via soil irrigation to leverage intrinsic stress-adaptation mechanisms for green-manure legume cultivation. This pot-scale study demonstrates a promising, eco-friendly bioinoculant approach that enhanced legume growth by 27–47% under controlled saline-alkaline conditions, highlighting its potential as a foundational strategy for the future development of scalable remediation techniques for marginal saline ecosystems.

Extraction, structural characterisation, antioxidant, and hypoglycaemic activity of polysaccharides from Floccularia luteovirens - Wei Feng; Yuhao Cui; Yaqi Tian; Junlong Wang; Yonggang Lin; Wen-Pan Shi (Natural Product Research, 2025)

Spatial distribution characteristics and innovation response of marine strategic science and technology forces in Shandong Province - Chenyu Pan; Wanglai Cui (Regional Studies in Marine Science, 2025)

Origin of hydrogen sulfide in produced gas of Upper Permian shales from western Hubei, southern China: A preliminary study - Yasheng Cui; Le Li; Huan Yang; Keliang Pan; Jie Xin; Yuanqing Hu; Xiaogui Peng; Feng Yang (Marine and Petroleum Geology, 2025)

Hydration disparities in crustal and mantle magmatic systems: Insights from the Stillwater complex, Alaskan-type complexes, and Pozantı-Karsantı ophiolite - Meng-Meng Cui; Ben-Xun Su; Yang Bai; Wan-Feng Zhang; Qi-Qi Pan (Lithos, 2025)

Surfactants facilitate microbial growth on the surface of microplastics in biological wastewater treatment - Feiyuan Liu; Keyu Ma; Huan He; Xing Wan; Ziwei Guo; Jingye Cui; Wanqi Shi; Bin Huang; Xuejun Pan (Journal of Environmental Management, 2025)

Scalability potential of a pneumatic extrusion-based 3D printing system for food products - Jingfu Pan; Xiaochen Chen; Jingyao Liu; Ziyi Wang; Tariq Aziz; Majid Alhomrani; Walaa F. Alsanie; Abdulhakeem S. Alamri; Haiying Cui; Lin Lin (Innovative Food Science & Emerging Technologies, 2025)

From washing to cooking: A comprehensive assessment of ten household processing methods on typical pesticide residues in cowpeas - Jiarong Cui; Jun Xu; Xiaohu Wu; Xinglu Pan; Yongquan Zheng; Fengshou Dong (Food Research International, 2025)

Enhanced Type-II singlet oxygen production via 3D topological porphyrin-based covalent organic framework - Xiaoning Zhan; Yucheng Jin; Houhe Pan; Baoqiu Yu; Rong Jiang; Boce Cui; Dongdong Qi; Siyu Liu; Yanjun Zhao; Jianzhuang Jiang (Chemical Engineering Journal, 2025)

Ecosystem drought recovery and influencing factors in temperate China and the Qinghai-Tibet alpine region - Yunfan Sun; Qingyu Guan; Zepeng Zhang; Jun Zhang; Ziyang Cui; Leyao Pan (CATENA, 2025)

Fabrication of waste bread-derived biodegradable mulch film with sustained-release atrazine performance - Zerong Song; Pan Zhao; Mengjia Cui; Qunbo Wang; Hanmo Cui; Jiajun Wu; Jie Wu; Xianghai Kong; Dongqing Cai; Yu Chi; Dongfang Wang (Bioresource Technology, 2025)

Identification of writers and erasers in tomato and their response to drought stress and hormones - Yushi Lu; Sheng Luo; Jing Cui; Yuxia Yao; Yuna Pan; Wenjin Yu; Changxia Li (Plant Cell Reports, 2025)

Semantic Consistency Network with Edge Learner and Connectivity Enhancer for Cervical Tumor Segmentation from Histopathology Images - Lisha Pang; Peng He; Yue Han; Hao Cui; Peng Feng; Chi Zhang; Pan Huang; Sukun Tian (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Smeat-seq transcriptomic profiling unveils key regulatory events during Maternal-to-Zygotic transition and supports High-Efficiency culture system development in Tibetan sheep embryos - Tianhao Li; Yangyang Pan; Tian Zhao; Jinglei Wang; Hui Zhang; Xiaoqing Yang; Xiaolin Ye; Donglan Zhong; Xin Ma; Sijiu Yu; Yan Cui (Functional & Integrative Genomics, 2025)

Genome-wide identification and analysis of paclobutrazol-resistance gene family in cotton and the positive role of GhPRE3 in salt stress and drought stress resistance - Shuaikang Geng; Jingjing Zhai; Bingkai Cui; Huiyun Shan; Zili Liu; Jiahui Li; Cong Wang; Yuling Liu; Pengtao Li; Quanwei Lu; Zihan Xiao; Xiaoping Pan; et al. (Functional & Integrative Genomics, 2025)
Compared with other transcription factors, much less studies have been performed on paclobutrazol-resistance (PRE), a subgroup of the extensive bHLH transcription factor gene family, and the research in cotton was also limited. By utilizing the PRE genes and their conserved domains identified in Arabidopsis, a total of 23, 22, 11, and 12 PRE genes were identified from two major cultivated cotton species and their two ancestors, respectively. The cotton PRE gene family was categorized into three subgroups based on evolutionary tree analysis. Motif and intron analyses indicated that the PRE gene has remained highly conserved throughout evolution. Collinearity analysis indicated that gene duplication, particularly through fragment replication, has significantly contributed to the expansion of the cotton PRE family. An exploration of the conserved elements within the PRE gene family uncovered numerous elements associated with plant stress resistance. Additionally, cotton transcriptome and qRT-PCR analysis showed that PRE genes were associated with a variety of abiotic stresses, including salt, drought, and cold treatments. Subcellular localization experiments indicated that the GhPRE3 gene is associated with membrane proteins. Finally, we selected the GhPRE3 gene for a VIGS experiment, which revealed that under salt stress and drought stress conditions, the wilting of leaves in the GhPRE3- silenced plants was significantly more severe than that observed in the control group, with T-AOC levels notably lower and MDA levels significantly higher. Overexpression of GhPRE3 enhanced seed germination and root development in transgenic Arabidopsis thaliana under salt stress and drought stresses. This suggests that GhPRE3 plays a positive regulatory role in cotton tolerance to salt and drought stressed, providing a reference for molecular genetic breeding of cotton with salt and drought tolerance.

A Review of Polyhalogenated Carbazoles (PHCZs) as an Emerging Contaminant: Environmental Occurrence, Toxicity and Remediation - Bingjie Cui; Innocent Tayari Mwizerwa; Xiao Chen; Zhuyu Sun; Ying Zhang; Pan Wang (Reviews of Environmental Contamination and Toxicology, 2025)

Zeolitic imidazolate framework-8 nanoparticles: A promising nano-antimicrobial agent for sustainable management of bacterial leaf streak in rice - Dingyang Zhang; Ziqi Cui; Shujing Liang; Wenhua Rao; Yakubu Saddeeq Abubakar; Xiong Guan; Wenhui Zheng; Xiaohong Pan (Pesticide Biochemistry and Physiology, 2025)

Dammarane triterpenoids with anti-inflammatory and promoting glucose uptake activities from the leaves of Cyclocarya paliurus - Xiaoqin Liang; Qingfang Zheng; Biqun Zou; Yanqin Li; Liwei Pan; Chenyang Ren; Jiwen Xin; Bo Yang; Ruiyun Yang; Weifeng Xu; Chaowen He; Yanling Cui; et al. (Phytochemistry, 2025)

The perspective of future climate warming impacts on harmful algae blooms in eutrophic Lake Taihu, China - Chixiao Cui; Ting Pan; Justin Brookes; Qingji Zhang; Boqiang Qin; Yunlin Zhang; Guangwei Zhu (Journal of Hydrology, 2025)

Fundamental research on recycling spent lithium-ion batteries for environmental pollutant control - Lizhen Feng; Chuanqi Pan; Baozhong Zhang; Lijuan Liu; Jingwei Wan; Shengfeng Cui; Wei Li (Journal of Environmental Management, 2025)

Interactions between raw dark tea chemistry and dominant fungi shape Hei brick tea quality - Yating Guo; Haijing Cui; Xinxin Wang; Haowei Guo; Xinyu Feng; Anran Yan; Yani Pan; Lixin He; Liping Liu; Kexin Zhang; Hua Fang; Hesham R. El-Seedi; et al. (International Journal of Food Microbiology, 2025)

Alleviating effect and mechanism of Lactobacillus helveticus ZJUIDS18 on colitis induced by DSS in mice - Nan Cui; Chongwei Yu; Feiwei Cao; Qinchao Ding; Huiling Pan; Yaqi Zeng; Daxi Ren (Food Bioscience, 2025)

Discovery of two IgM subclasses in Nile tilapia (Oreochromis niloticus) provides insights into IgM evolution in teleost fish - Yuan-Yuan Yao; Chen-Xi Pan; Yu-Dong Hao; Xun Liu; Dan-Dan Chen; Zheng-Wei Cui; Xiang-Yang Zhang; Jian-Min Ye; Yong-An Zhang; Xu-Jie Zhang (Fish & Shellfish Immunology, 2025)

Experimental study of the dynamic performance of clay brick masonry walls under blast loading - Yanchao Shi; Yaqi Pan; Jiahao Gao; Wei Zhong; Jian Cui (Engineering Structures, 2025)

Fe-SMA prestressed strengthening of damaged transverse hinge joints in hollow slab bridges - Zhiqiang Dong; Cui Zou; Xinliang Sun; Xihua Zhan; Hong Zhu; Yijie Pan; Elyas Ghafoori (Engineering Structures, 2025)

DHA sustains frozen-cell-induced efferocytosis by mitigating endoplasmic reticulum stress to promote inflammation resolution and bone repair - Boya Zhang; Hanze Du; Lei Huang; Lijun Liu; Jing Cui; Linlin Wen; Junguang Liu; Wenhao Zhai; Rongrong Ye; Yuhuan Li; Kexuan Liu; Wangni Xie; et al. (Chemical Engineering Journal, 2025)

Bioactive glass with integration of hyperthermia to manipulate pH-responsive release of chemotherapeutic agent for osteosarcoma combating and time-sequential reconstruction of bone homeostasis - Qingshan Li; Yuyang Gao; Runmeng Li; Hao Li; Changjiang Yang; Honglong Li; Limin Zhao; Bochen An; Gang Han; Jiying Chen; Haobo Pan; Quanyi Guo; et al. (Chemical Engineering Journal, 2025)

Design of modified carboxymethyl cellulose adsorbent for effective removal of Pb (II) and cd (II) from aqueous solutions - Shiqin Pan; Yudong Yang; Shitong Zhang; Xinyu Wang; Shuangling Zhong; Xuejun Cui (Carbohydrate Polymers, 2025)

Reducing toxicity of atrazine using subcritical hydrolysis technology and investigation the hydrolysis mechanism - Shuo Pan; Huaiyu Zhou; Shuang Wu; Qing Wang; Jingru Bai; Da Cui; Junting Su (Environmental Science and Pollution Research, 2025)

DCDNet: A deep neural network for dead chicken detection in layer farms - Dihua Wu; Yibin Ying; Mingchuan Zhou; Jinming Pan; Di Cui (Computers and Electronics in Agriculture, 2025)

Activation of YAP1 and TAZ enhances the in vitro maturation of yak oocytes and influences subsequent embryonic development - Donglan Zhong; Yangyang Pan; Meng Wang; Hui Zhang; Ruihua Xu; Qiyong Zuo; Tianhao Li; Sijiu Yu; Yan Cui (Theriogenology, 2025)

Tetraether-based temperature record from Lake Xingyun in southwestern China since late MIS3 and implication for regional differences in temperature reconstruction - Haiyang Yu; Xu Wang; Ming Ji; Shihao Zhang; Gaochao Pan; Licheng Guo; Linlin Cui; Xueyun Ma; Wubiao Li; Dongsheng Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Geochemical pattern, quality and driving forces of multi-layer groundwater in a high-capacity mining area basin: A comprehensive analysis based on the interweaving of multiple factors - He Cui; Limin Duan; Hao Pan; Tingxi Liu (Journal of Hydrology, 2025)

Interactions of extracellular polymeric substances with ferrihydrite and subsequent 17α-ethinylestradiol photodegradation: Impact of Fe(III)-EPS complexes formation - Jingye Cui; Huan He; Wanqi Shi; Zhicheng Liao; Danni Cui; Jianxiang Yang; Yixin Liu; Chaochao Lai; Bin Huang; Xuejun Pan (Journal of Hazardous Materials, 2025)

Trophodynamic mechanisms of per- and polyfluoroalkyl substances in oligotrophic ecosystem from the Tibetan Plateau river - Yanan Li; Jiao Ren; Yawen Li; Fengfeng Dong; Qiusheng He; Yang Cui; Ke Zhang; Zhentao Wang; Xinqi Xin; Yitao Pan; Jianhui Tang (Journal of Hazardous Materials, 2025)

Contrasting effects of different acid rain types on soil nitrogen pools - Xingyu Pan; Yi Jian; Zhenfeng Xu; Bo Tan; Xinglei Cui; Tong Zhang; Lin Xu; Han Li; Li Zhang; Hongwei Xu; Sining Liu; Lixia Wang; et al. (Journal of Environmental Management, 2025)

How does large-scale underground mining affect the water cycle? — Comprehensive analysis based on isotopes, water levels and hydrogeological conditions - He Cui; Limin Duan; Hao Pan; Wenrui Zhang; Tingxi Liu (Journal of Environmental Management, 2025)

Differences in odor-active compounds and non-volatile precursors between spray-dried and freeze-dried Spirulina platensis revealed by GC×GC-TOFMS-O and UPLC-MS/MS - Xiao Jia; Jingnan Ren; Qi An; Gang Fan; Hongli Cui; Song Qin; Jinchu Yang; Shaoqian Cao; Siyi Pan (Food Chemistry, 2025)

Characterization of OSA-starch/tea polyphenol complexes with enhanced oil-water interfacial properties by molecular dynamics simulation and isothermal titration calorimetry - Lidan Pan; Xiaorui Liu; Die Dong; Li Guo; Meng Zhao; Bo Cui (Food Chemistry, 2025)

CoFe-LDH “Armour” modified nanofiber membrane with multiple synergistic effects for wastewater purification - Hengchao Liang; Atian Xie; Jun Chen; Can Wei; Jirong Luo; Jiuyun Cui; Jianming Pan (Chemical Engineering Journal, 2025)

Low temperature efficient adsorption of toxic gas phosphine over CuCe co-doped nitrogen-rich biochar in an anaerobic environment - Ruoxu Liu; Min Shao; Junjie Ma; Fang Wang; Rui Cao; Zibin Pan; Ping Ning; Jiayu Feng; Shuo Cui; Lijuan Jia (Chemical Engineering Journal, 2025)

Bridging papermaking and zinc-ion batteries: Engineering partial Janus separators from hierarchically porous softwood fibers - Rukun Cui; Siyu Pan; Yonghao Ni; Zhibin He; Hui Mao; Jing Shen (Chemical Engineering Journal, 2025)

The role of N6-methyladenosine (m6A) modification in plants - Cui-Xian Qin; Ao-Mei Li; Zhong-Liang Chen; Fen Liao; Miao Wang; You-Qiang Pan; Li Zhou; Bao-Qing Zhang; Jian-Hui Zhou; Dong-Liang Huang (Theoretical and Applied Genetics, 2025)

Assessment of Egg Yolk IgY Antibodies Against Live or Inactivated Aeromonas hydrophila for Polyvalent Passive Immunization in Goldfish (Carassius auratus) - Pan Cui; Jing Chen; Huihui Xiao; Xixian Che; Shujun Sun; Zijian Ma; Juan Lu; Gaoxiao Xu; Xiang Liu (Fishes, 2025)
Egg yolk IgY antibody has significant application potential in aquaculture as a form of passive immunotherapy against various bacterial infections owing to its capacity for large-scale and cost-effective production. In this research, laying hens were immunized with live or inactivated Aeromonas hydrophila to produce IgY antibodies. Following this, experiments were carried out to assess the passive immune protection rates of the two types of IgY antibodies when used to immunize goldfish (Carassius auratus), which were then infected with A. hydrophila or Aeromonas veronii. ELISA experiments were conducted to demonstrate the interaction between the IgY antibodies and the bacteria. The kidneys of C. auratus were coated on a Luria–Bertani (LB) medium to evaluate bacterial content. The leukocyte phagocytosis was detected by a cell phagocytosis assay. The serum of C. auratus was used to assess the expression of antioxidant factors, and a qRT-PCR was conducted to evaluate the mRNA expression of inflammatory factors in visceral tissue. Furthermore, histopathology and immunofluorescence analysis were performed to evaluate the structural integrity, apoptosis, and DNA damage of visceral tissues. The results indicated that the live or inactivated A. hydrophila IgY antibodies exhibited passive immune protection rates against A. hydrophila and A. veronii and could recognize these two bacteria in vitro. Additionally, these two IgY improved the phagocytic ability of leukocytes, diminished renal bacterial concentration, and decreased the levels of antioxidant factors and mRNA expression of inflammatory factors. Meanwhile, the two IgY antibodies did not cause any pathology of the kidney, spleen, and intestine, and decreased the levels of DNA damage factor (γH2A.X) and cell apoptosis factor (p53) in renal tissue. Therefore, live and inactivated A. hydrophila IgY antibodies can resist bacterial infections, with live bacteria IgY providing greater protection than inactivated bacteria IgY. Further, A. hydrophila is an aquatic pathogen that causes minimal damage to laying hens, and the immunity of live A. hydrophila conforms to animal welfare. Altogether, live A. hydrophila IgY antibody can serve as a polyvalent passive immune vaccine candidate in aquaculture.

The multivalent passive immune-protective vaccines of egg yolk immunoglobulin Y derived from live or inactivated Pseudomonas anguilliseptica against aquaculture pathogens (P. anguilliseptica and Aeromonas veronii) in goldfish (Carassius auratus) - Pan Cui; Jing Chen; Ziye Ma; Huihui Xiao; Juan Lu; Juan Wang; Gaoxiao Xu (Frontiers in Marine Science, 2025)
Background Egg yolk immunoglobulin Y (IgY) can be produced on a large scale, with simple and economical preparation and no drug residue, making it promising for application in prophylactic multivalent passive immunization vaccines for aquaculture. Methods IgY antibodies of live Pseudomonas anguilliseptica (L-PA-IgY) or inactivated P. anguilliseptica (I-PA-IgY) were prepared by immunizing laying hens. Carassius auratus individuals were passively immunized with the two types of IgY antibodies and then challenged with P. anguilliseptica and Aeromonas veronii to detect the immune protection rate. The kidneys were homogenized and coated on Luria–Bertani (LB) solid medium to assess their bacterial content. Additionally, a cell phagocytosis assay was conducted to detect leukocyte phagocytosis. C. auratus serum was obtained to evaluate the recognition of the two bacteria by enzyme-linked immunosorbent assay (ELISA), and the expression of antioxidant factors [superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px)]. Furthermore, real-time fluorescence-based quantitative PCR (qRT-PCR) was performed to assess the expression of inflammatory factors (IL-6, IL-8, TNF-α, and IL-1β) in the kidney and spleen. Moreover, histopathological analysis was used to assess the integrity of visceral tissue structure, and immunofluorescence analysis was employed to assess the expression of apoptosis factor (p53) and DNA damage factor (γH2A.X) in the kidney. Results The results indicated that the IgY antibodies of L-PA-IgY or I-PA-IgY exhibited passive immune protection against P. anguilliseptica and A. veronii . The sera of C. auratus passively immunized with L-PA-IgY or I-PA-IgY could interact with the two bacteria. Additionally, in C. auratus , the two IgY antibodies enhanced the phagocytic activity of leukocytes, reduced bacterial content in the kidneys, and diminished the expression of inflammatory and antioxidant factors. Furthermore, the structures of the kidney, spleen, and intestinal tissues were intact, and the expression of p53 and γH2A.X decreased in the kidney. Conclusion L-PA-IgY and I-PA-IgY can resist multiple bacterial infections and have immunoprotective effects with no significant differences. Moreover, the inactivated P. anguilliseptica immunization in laying hens is in line with animal welfare standards, and I-PA-IgY can serve as an immunization strategy of a prophylactic multivalent passive vaccine to resist multiple bacterial infections in aquaculture.

Putting the recent 100-year of Asian summer monsoon weakening into context - Jingyao Zhao; Hai Cheng; Liangkang Pan; Kexin Wang; Jiahui Cui; Ming-Qiang Liang; Xiyu Dong; Jiayu Lu; Qiang Li; Yan Yang (Science Bulletin, 2025)

Oceanic redox variations during the Cambrian Age 2–3 in the Yangtze Block of South China: Evidence from pyrite-based proxies - Fangliang Fu; Caineng Zou; Zhengfu Zhao; Songqi Pan; Wei Wang; Cui Luo; Ganlin Hua; Guanwen Lu; Ming Yuan; Jia Yin; Zhenhua Jing (Marine and Petroleum Geology, 2025)

An integrated carbon dots-based sensing platform via alkali-assisted hydrothermal reaction for pH/Fe(II) detection and a sensing array for sulfur species - Zhenhua Yang; Xuyan Cui; Pan Du; Quanxi Zhang; Xianyun Zheng; Xiaojuan Gong; Yuexia Zhang; Chuan Dong (Journal of Hazardous Materials, 2025)

In-situ bioaugmentation with indigenous Pseudomonas sp. BO3–4 for the remediation of organic-contaminated groundwater in an operating petrochemical enterprise - Ji Ouyang; Lixu Pan; Fei Gu; Shiming Lei; Xin Chen; Yan Zhou; Xin Zhu; Changzheng Cui (Chemical Engineering Journal, 2025)

S-scheme/Schottky dual heterojunction BiOBr/Fe3O4/Ti3C2 MXene boost synergistic roles of photocatalysis and persulfate activation via multi-channel photoelectron transfer - Xiaoyan Wei; Caiwei Su; Hanbing Zhang; Xianglong Tang; Jingyi Zhou; Fan Ye; Cui Pan; Yuelong Qin; Kun Liu; Zhangfa Tong (Chemical Engineering Journal, 2025)

Wheat stripe rust resistance gene Yr9, derived from rye, is a CC-NBS-LRR gene in a highly conserved NLR cluster - Yang Yu; Jiajun Liu; Shengjie Lan; Qihang Chen; Jinlong Li; Haoyuan Song; Chen Pan; Juan Qi; Yu Cui; Xingfeng Li; Ming-Cheng Luo; Fei Ni; et al. (Science China Life Sciences, 2025)

Experimental Study of High-Efficiency Anchoring Device for Improving the Performance of Resin-Grouted Bolt - Lei Cui; Ying Zhang; Yishan Pan; Shaowei Liu (Rock Mechanics and Rock Engineering, 2025)

Rotenone-driven DNA hypermethylation of the miR-6991–3p promoter induces death of mouse brain organoids - Zeyu Cui; Xin Liu; Xijin Gao; Zhihua Yu; Weidong Pan; Te Liu (Tissue and Cell, 2025)

Oleanane-type triterpenoids from Sabia limoniacea with nitric oxide inhibitory activity - Ping Hou; Liwei Pan; Liuting Peng; Chunqiu Gan; Chenyang Ren; Ruiyun Yang; Weifeng Xu; Chaowen He; Yanlin Cui; Wen Tang; Jun Li; Yan Huang (Phytochemistry, 2025)

Deciphering pollinator exposure hazards: Systemic translocation and accumulation of seed-coating pesticides in maize and their synergistic exposure risk to bees - Fengjiao Hao; Baoling Zhang; Junwei Cui; Jun Xu; Fengshou Dong; Xiaohu Wu; Yongquan Zheng; Xinglu Pan (Journal of Hazardous Materials, 2025)

Geochemistry of sulfides from massive carbonate replacement type tin ore at Gaofeng, Dachang orefield: Insights into precipitation conditions and enrichment of critical metals - Yu-Pei Liu; Pei Ni; Jun-Yi Pan; Wen-Chao Su; Stefano Albanese; Jian-Ming Cui; Yuan-Feng Cai; Ming-Sen Fan; Zhi-Lin Cheng (Journal of Geochemical Exploration, 2025)

Investigation on the discharge port and discharge valve lift in the R32 rotary compressor for performance improvement - Junhong Wu; Guangqian Peng; Songlin Cui; Wang Zeng; Junlong Xie; Xi Pan (International Journal of Refrigeration, 2025)

Enhancing Feammox efficiency through riboflavin and humic acid: Nitrogen and iron transformation, energy metabolism, and microbial response - Dun Guo; Lei Yang; Hao-Qi Lu; Yu-Chao Wang; Hong-Yan Meng; Pan Liang; Shen Cui; Zhang-Wei He; Jun Lan; Yong-Xiang Ren (Bioresource Technology, 2025)

Neutral pH induces complex and stable soil microbial networks in agricultural ecosystems - Jianwei Zhang; Zhiying Guo; Jie Liu; Xianzhang Pan; Yanan Huang; Xiaodan Cui; Yuanyuan Wang; Yang Jin; Jing Sheng (Plant and Soil, 2025)

BSA-Seq-based genetic mapping of fruit length regulating locus in oriental melon XNM125 and XNM020 - Yuqing Yang; Ning Zhang; Yuqing Zhou; Haibing Cui; Yuan Zhou; Huijun Zhang; Hanqiang Liu; Yupeng Pan (Euphytica, 2025)

3D Dubins Curve-Based Path Planning for UUV in Unknown Environments Using an Improved RRT* Algorithm - Feng Pan; Peng Cui; Bo Cui; Weisheng Yan; Shouxu Zhang (Journal of Marine Science and Engineering, 2025)
The autonomous navigation of an Unmanned Underwater Vehicle (UUV) in unknown 3D underwater environments remains a challenging task due to the presence of complex terrain, uncertain obstacles, and strict kinematic constraints. This paper proposes a novel smooth path planning framework that integrates improved Rapidly-exploring Random Tree* (RRT*) with 3D Dubins curves to efficiently generate feasible and collision-free trajectories for nonholonomic UUVs. A fast curve-length estimation approach based on a backpropagation neural network is introduced to reduce computational burden during path evaluation. Furthermore, the improved RRT* algorithm incorporates pseudorandom sampling, terminal node backtracking, and goal-biased exploration strategies to enhance convergence and path quality. Extensive simulation results in unknown underwater scenarios with static and moving obstacles demonstrate that the proposed method significantly outperforms state-of-the-art planning algorithms in terms of smoothness, path length, and computational efficiency.

SETD2 regulates oocytes in vitro maturation through histone methylation and maternal mRNA degradation in yak - Hui Zhang; Yangyang Pan; Meng Wang; Jinglei Wang; Jiaxin Huang; Rui Ma; Shanshan Yang; Wenbin Ma; Sijiu Yu; Yan Cui (Theriogenology, 2025)

Spatiotemporal dissipation, metabolic dynamics and bumblebees’ toxicity risk of the neonicotinoid insecticide thiacloprid in greenhouse conditions - Lu Bai; Shaodong Pan; Yuweng Sun; Yongpan Shan; Xianpeng Song; Dan Wang; Yajie Ma; Hongyan Hu; Xiangliang Ren; Jinjie Cui; Yan Ma; Changcai Wu (Journal of Hazardous Materials, 2025)

Cotreatment strategy for hazardous arsenic-calcium residue and siderite tailings via arsenic fixation as scorodite - Rui Su; Xinrong Su; Yanjiao Gao; Xu Ma; Xiaoming Zhao; Xiaoxia Ou; Yubo Cui; Jinru Lin; Yuanming Pan; Shaofeng Wang (Journal of Environmental Sciences, 2025)

Engineering the Ni-N3 microenvironment: Electronic and spatial effect significantly improves the performance of the thermal catalytic acetylene semi-hydrogenation - ZiHao Tao; Hedan Yao; Guoqing Qi; Hengrui Li; Yi Qin; Louwei Cui; Liuyi Pan; Dong Li; Wenhong Li (Chemical Engineering Journal, 2025)

Corrigendum to “Scalable solar-driven reforming of alcohol feedstock to H2 using Ni/Zn3In2S6 photocatalyst” [Chem. Eng. J. 513 (2025) 162965] - Denny Gunawan; Tahlia Stern; Jiajun Zhang; Jodie A. Yuwono; Jian Pan; Qiyuan Li; Haolin Yu; Michael Gunawan; Rosalie K. Hocking; Cui Ying Toe; Jason Scott; Rose Amal (Chemical Engineering Journal, 2025)

Deciphering the interfacial electrochemistry of non-nucleophilic Mg(TFSI)2 as 4 V-class electrolyte for Mg batteries - Lu Zhang; Yuping Liu; Xiaolei Wang; Zhihong Cui; Chenlong Xiao; Changguo Chen; Jingfeng Wang; Guangsheng Huang; Dingfei Zhang; Fusheng Pan (Chemical Engineering Journal, 2025)

Analysis of the potential resource, environmental and economic impacts of EU battery and waste battery regulations on China's lithium-ion battery industry - Min Liu; Wei Liu; Mingyue Zhang; Xin Pan; Qian Zhang; Mingxue Zhang; Tengyun Ma; Zhaojie Cui (Resources, Conservation and Recycling, 2025)

Fluorescent molecularly imprinted hydrogel sensing strip based on nitrogen-doped carbon dots and inverse opal photonic crystals applying for effective detection for imidacloprid in fruits and vegetables - Mingfei Pan; Mengmeng Gao; Jingjing Cui; Rui Gao; Huilin Li; Jingming Sun; Wenjie Chen; Shuo Wang (Food Chemistry, 2025)

Polyvalent immunoprotection of protein, DNA and IgY antibody vaccines of Vibrio fluvialis outer membrane protein VF08100 in fish - Huihui Xiao; Saixing Duan; Pan Cui; Jing Chen; Xixian Che; Juan Lu; Juan Wang; Guoping Zhu; Yong Liu; Xiang Liu (Fish & Shellfish Immunology, 2025)

Scalable solar-driven reforming of alcohol feedstock to H2 using Ni/Zn3In2S6 photocatalyst - Denny Gunawan; Tahlia Stern; Jiajun Zhang; Jodie A. Yuwono; Jian Pan; Qiyuan Li; Haolin Yu; Michael Gunawan; Rosalie K. Hocking; Cui Ying Toe; Jason Scott; Rose Amal (Chemical Engineering Journal, 2025)

Type I Interferon Signalling and Ischemic Stroke: Mechanisms and Therapeutic Potentials - Pan Cui; Bo Song; Zongping Xia; Yuming Xu (Translational Stroke Research, 2025)

Coupling of algae, algal organic matter, and nutrient biogeochemical cycling in eutrophic waters - Danni Cui; Huan He; Zhe Zhang; Feiyuan Liu; Yuan Gui; Ziwei Guo; Zhicheng Liao; Xi-Zhi Niu; Bin Huang; Xuejun Pan (Reviews in Environmental Science and Bio/Technology, 2025)

Capabilities and Limitations of Air‐Dried Soils in Microbial Biogeography: A Regional‐Scale Comparative Analysis - Jianwei Zhang; Zhiying Guo; Jie Liu; Xianzhang Pan; Yanan Huang; Xiaodan Cui; Yuanyuan Wang; Yang Jin; Jing Sheng (Environmental Microbiology, 2025)
Air‐dried soil archives offer valuable potential for studying long‐term microbial dynamics, yet systematic evaluations across large spatial scales with paired fresh‐soil comparisons remain limited. Here, we systematically evaluated the effects of 1‐month air‐drying on microbial biogeography across 244 paddy fields in eastern China. Results showed that air‐drying significantly altered communities by reducing diversity through the elimination of rare taxa while enriching desiccation‐resistant phyla like Firmicutes, Chloroflexi and Actinobacteria. These compositional shifts further triggered functional bias, enhancing fermentation/methanogenesis pathways while suppressing nitrogen cycling processes. Despite these alterations, air‐dried samples maintained remarkable fidelity to key ecological patterns observed in fresh soils. Multivariate analyses demonstrated strong structural concordance between paired samples, with soil pH consistently emerging as the primary environmental driver in both data sets. This preservation of biogeographical relationships occurred despite significant changes in underlying ecological mechanisms. Air‐dried soil communities exhibited increased stochastic assembly, reduced niche breadth and simplified co‐occurrence networks with altered keystone taxa, indicative of a two‐phase process: deterministic filtering of drought‐sensitive taxa followed by stochastic reorganisation among survivors. Overall, our findings provide a framework for utilising soil archives in microbial ecology, showing that while air‐drying introduces predictable distortions, samples retain essential ecological information for reconstructing historical microbial–environmental relationships at large scales.

Interspecific differences in nitrogen form acquisition strategies contribute to species dominance - Ming Guan; Xiao‐Cui Pan; Jian‐Kun Sun; Ji‐Xin Chen; Xiao‐Lin Wei; Bernhard Schmid; Michel Loreau; Yu‐Long Feng (Ecology, 2025)
Plant's ability to use prevalent or less prevalent soil nitrogen (N) forms may affect their dominance within vegetation types, and these partitioning‐driven changes in dominance may facilitate species co‐existence. However, the mechanisms underlying these processes remain unclear, particularly given the strong influence of altitude on soil N forms, which in turn affect plant N acquisition strategy. In this study, we first determined the effects of preference and plasticity in N form uptake on partitioning of soil N forms and species dominance, and then assessed the relative importance of these two N form use strategies for 19 dominant and non‐dominant species in three vegetation types along an altitudinal gradient on Changbai Mountain, northeast China. To achieve this, we measured dominance, the contents of different N forms in rhizosphere soils, their proportional contributions to leaf N, and N form uptake preference and plasticity for these 19 species. Our results show significant interspecific differences in the proportional contributions of different soil N forms to leaf N within all three vegetation types, providing a novel mechanism underlying niche differentiation among plants. Species dominance was positively associated with the proportional contributions of soil dissolved organic N (the most prevalent N form) and the main inorganic N form to leaf N, while negatively with that of the subordinate inorganic N. These associations were not altered by the altitude‐driven changes in the absolute and proportional contents of different soil N forms, suggesting a potentially widespread phenomenon. Both preference and plasticity in N form uptake contributed to the proportional contributions of different N forms to leaf N, and therefore to species dominance and co‐existence within vegetation types. Furthermore, N form preference was more critical for non‐dominant relative to dominant species and at high relative to low altitude, while N form uptake plasticity was more important for dominant species and at low altitude. Our study provides robust evidence for the interspecific niche differentiation in N form uptake, contributing to species dominance and co‐existence within vegetation types, and reveals the mechanisms (plasticity and preference) underlying the association between species dominance and the uptakes of different N forms.

How aging impacts cortical dynamics and gait during dual-task turning revealed by fNIRS - Yuqi Dong; Chen Yang; Yan Chen; Feng Pan; Jinwei Wang; Cui Zhang (GeroScience, 2025)

Quantifying the impact of single-tree morphological characteristics on the vertical gradient cooling effect and human thermal comfort during summer - Yue Cai; Chong Li; Chunyu Pan; Guangyu Wang; Jianxiang Xu; Wenyan Cui; Yufeng Zhou; Guomo Zhou (Urban Forestry & Urban Greening, 2025)

Integrative N-glycomics and N-glycoproteomics landscape reveals up-regulation of complex-type N-glycosylation in the tolerance of peach fruit to chilling injury - Huiwen Wang; Tonghao Cui; Jiaqi Wang; Ruohan Ou; Yilong Liu; Bo Zhang; Changjie Xu; Changqing Zhu; Miaojin Chen; Yanna Shi; Yuanjiang Pan; Kunsong Chen; et al. (Postharvest Biology and Technology, 2025)

Efficient adsorption of tetracycline by phytic acid modulated ramie fiber-derived porous carbon: Performance, mechanism, and application potential - Dongxinyu Chen; Yuwei Deng; Boyan Cui; Shou Mei; Lixi Xiao; Huo Zhou; Ziyi Zhan; Rongling Wang; Xuanyuan Pei; Qiang Li; Jun Wan; Yuxuan Ye; et al. (Journal of Water Process Engineering, 2025)

Unveiling the mechanism and driving factors of pharmaceutical and personal care product (PPCP) removal in wastewater treatment plants - Shaoyang Li; Zhen Gao; Tianyi Chen; Zhile Pan; Dianbao Li; Yanran Dong; Junjie Li; Yanli Zhang; Sihan Cui; Weiling Sun; Nan Xu (Journal of Environmental Management, 2025)

Immunomagnetic metal-organic frameworks based coupling-free and extraction-free sensitive detection of aflatoxin B1 in peanut oils - Zhihong Xuan; Jin Ye; Baoxia Ni; Hua Cui; Li Li; Jinnan Chen; Yao Qin; Quan Pan; Hongmei Liu; Songxue Wang (Food Chemistry, 2025)

Performance study of high-temperature proton exchange membrane fuel cell based on novel fan-fins gas channel - Zhiqing Zhang; Hui Liu; Feng Jiang; Shuwan Cui; Mingzhang Pan; Dongmei Li; Guangyu Ma; Jiajia Dou (Journal of Environmental Chemical Engineering, 2025)

Nonlinear feedback of Asian summer monsoon to abrupt events in North Atlantic: Evidence from a precisely dated speleothem record during late MIS3 - Xi Chen; Jingyao Zhao; Kexin Wang; Xiyu Dong; Jiahui Cui; Liangkang Pan; Carlos Pérez-Mejías; Hai Cheng (Global and Planetary Change, 2025)

Exploring the mechanisms of enhanced activated carbon’s toluene adsorption and regeneration by utilizing inherent pyrite in coal - Huirong Zhang; Lijun Zhu; Zihe Pan; Jinglei Cui; Baofeng Wang; Dongke Zhang; Yanxia Guo; Fangqin Cheng (Fuel, 2025)

Preparation and characterization of covalent starch-protein-tea polyphenol complexes with enhanced interfacial properties - Die Dong; Tenglong Geng; Lidan Pan; Xiaorui Liu; Chenxi Yu; Chao Yuan; Li Guo; Meng Zhao; Bo Cui (Food Research International, 2025)

Chemical characterization and classification of vegetable oils using DESI-MS coupled with a neural network - Yiwei Cui; Liangcun Zhu; Yan Li; Kai Ge; Weibo Lu; Lijun Ge; Kang Chen; Jing Xue; Feiyang Zheng; Shuncong Dai; Huafei Pan; Jingjing Liang; et al. (Food Chemistry, 2025)

Prevalence and Predictors of Hemorrhagic Foci on Long-term Follow-up MRI of Recent Single Subcortical Infarcts - Shuai Jiang; Wen-Zuo Shang; Jing-Yu Cui; Yu-Ying Yan; Tang Yang; Yi Hu; Le Cao; Xun Yue; Ruo-Su Pan; Chen Ye; Jia-Yu Sun; Bo Wu (Translational Stroke Research, 2025)
Hemorrhagic foci surrounding the lacune in the long-term evolution of recent single subcortical infarcts (RSSIs) remains largely unexplored. We aimed to determine the prevalence, characteristics, and predictors of hemorrhagic foci in patients with RSSI. From a prospective, longitudinal study of RSSIs, we recruited patients who underwent multimodal MRI assessments both at baseline and approximately one year after the stroke onset. Hemorrhagic foci were identified using susceptibility-weighted imaging (SWI). Among 101 patients with RSSI, nearly half (n = 45, 44.6%) had hemorrhagic foci within the index RSSI lesions on follow-up SWI. RSSIs with hemorrhagic foci formation were associated with a longer time to follow-up imaging (median 449 versus 401 days, P = 0.005) and higher likelihood of being located in the anterior circulation compared to those without hemorrhagic foci (88.9% versus 64.3%, P = 0.003). Hemorrhagic foci were also associated with larger lesion size (P < 0.001), a higher proportion of cavitation formation (P = 0.003), higher baseline NIHSS scores (P = 0.004), and poorer functional outcomes (P = 0.001). In the subset of RSSIs in the lenticulostriate artery (LSA) territory, after adjustment for covariates, larger initial lesion volume (OR 1.80, 95% CI 1.13–2.87; P = 0.014) and greater decreases in LSA total length (OR 0.59, 95% CI 0.36–0.96; P = 0.035) were independently associated with hemorrhagic foci formation. The extent of ischemia in the initial infarct is predictive of the presence of hemorrhagic residues. Our findings contribute to the current understanding of the mechanisms underlying the evolution of RSSIs.

Dynamic proteome and acetylome profiling reveals key regulators of sucrose accumulation in sugarcane - Miao Wang; Ao-Mei Li; Zhong-Liang Chen; Cui-Xian Qin; Fen Liao; You-Qiang Pan; Prakash Lakshmanan; Xiao-Feng Li; Dong-Liang Huang (Plant Cell Reports, 2025)

Histaminergic Innervation of the Ventral Anterior Thalamic Nucleus Alleviates Motor Deficits in a 6-OHDA-Induced Rat Model of Parkinson’s Disease - Han-Ting Xu; Xiao-Ya Xi; Shuang Zhou; Yun-Yong Xie; Zhi-San Cui; Bei-Bei Zhang; Shu-Tao Xie; Hong-Zhao Li; Qi-Peng Zhang; Yang Pan; Xiao-Yang Zhang; Jing-Ning Zhu (Neuroscience Bulletin, 2025)
The ventral anterior (VA) nucleus of the thalamus is a major target of the basal ganglia and is closely associated with the pathogenesis of Parkinson’s disease (PD). Notably, the VA receives direct innervation from the hypothalamic histaminergic system. However, its role in PD remains unknown. Here, we assessed the contribution of histamine to VA neuronal activity and PD motor deficits. Functional magnetic resonance imaging showed reduced VA activity in PD patients. Optogenetic activation of VA neurons or histaminergic afferents significantly alleviated motor deficits in 6-OHDA-induced PD rats. Furthermore, histamine excited VA neurons via H1 and H2 receptors and their coupled hyperpolarization-activated cyclic nucleotide-gated channels, inward-rectifier K + channels, or Ca 2+ -activated K + channels. These results demonstrate that histaminergic afferents actively compensate for Parkinsonian motor deficits by biasing VA activity. These findings suggest that targeting VA histamine receptors and downstream ion channels may be a potential therapeutic strategy for PD motor dysfunction.

Pathogenic characterization and drug resistance of neonatal sepsis in China: a systematic review and meta-analysis - Ruixue Wu; Xiaoyu Cui; Rui Pan; Na Li; Ying Zhang; Jianbo Shu; Yang Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Identifying spatial drivers of soil heavy metal pollution risk integrating positive matrix factorization, machine learning, and multi-scale geographically weighted regression - Yujie Pan; Anmeng Sha; Wenjing Han; Chang Liu; Guowangchen Liu; Emily Welsch; Min Zeng; Shasha Xu; Yi Zhao; Shang Tian; Yiyi Li; Rui Deng; et al. (Journal of Hazardous Materials, 2025)

Extraction of short-chain fatty acid ethyl Ester in Baijiu using covalent organic framework–based magnetic nanoparticles: Theoretical screening and experimental validation - Xiaolong Shang; Ying Han; Xudong Lian; Siting Ye; Ling Ao; Baoguo Sun; Rong Liu; Pan Zhen; Yongqing Zhang; Yintao Jia; Wei Dong; Xiaotao Sun; et al. (Food Chemistry, 2025)

Warmer summers have the potential to affect food security by increasing the prevalence and activity of Actinobacteria - Yuanyuan Bao; Jan Dolfing; Zhiying Guo; Jie Liu; Xianzhang Pan; Xiaodan Cui; Yuanyuan Wang; Yang Jin; Lixia Zhang; Ruirui Chen; Xin Li; Youzhi Feng (European Journal of Soil Biology, 2025)

China's non-energy-intensive sectors have greater carbon reduction potential: Based on a three-tier SDA approach from energy substitution perspective - Chang Qin; Feng Dong; Yangfan Li; Xiaoyun Zhang; Yuling Pan; Caixia Li; Jue Cui (Environmental Impact Assessment Review, 2025)

Damage Analysis of High-Frequency Disturbance in Sandstone Creep Process Based on NMR Technology - Jie Chen; Ziyang Chen; Xiaokang Pan; Yi Cui; Yicao Rui; Jinlai Zhao; Lei Gou (Rock Mechanics and Rock Engineering, 2025)

Exploring the Correlation Between Varied Serum Iodine Nutritional Levels and Anti-Thyroglobulin Antibodies - Qiuyi Song; Tingting Xu; Yu Wang; Hongyan Wei; Feng Tan; Yanting Chen; Fang Fang; Tingkai Cui; Ziyun Pan; Xiaohui Guo; Wen Chen; Jun Shen; et al. (Biological Trace Element Research, 2025)

Pathogenicity comparison between porcine G9P[23] and G5P[23] RVA in piglets - Zixin Li; Yudi Pan; Yanxiang Zhou; Jianshuang Cui; Hailiang Ge; Wei Zhao; Li Feng; Jin Tian (Veterinary Microbiology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Genetic link between concealed granite and tin mineralization in the Yuling tin deposit, Nanling Range, South China: Constraints from zircon and cassiterite U-Pb dating, geochemistry, and Lu-Hf isotopes - Yong-Kang Chen; Pei Ni; Jun-Yi Pan; Yi-Ming Xu; Qi-Zhi Yang; Jian-Ming Cui; Wen-Sheng Li; Guan-Jian Fang (Journal of Geochemical Exploration, 2025)

Dynamic mechanism triggering the catastrophic Xinjing Landslide in Alxa, Inner Mongolia, China - Fangpeng Cui; Chen Xiong; Qiang Wu; You Zhou; Chengheng Hou; Linfeng Fan; Miao Liu; Hao Xu; Xu Pan (Engineering Geology, 2025)

Fabrication of a Single-Atom Mo catalyst for significantly enhanced hydrodesulfurization activity of dibenzothiophene - Bin Liu; Hongyang Lv; Fengyu Tian; Wenkui Xue; Xingxing Cui; Yuan Pan; Yichuan Li; Bin Dong; Yongming Chai; Chenguang Liu (Chemical Engineering Journal, 2025)

Modulation of Fe0-FexSy heterostructure by sulfurization constitutes an electron transfer channel for efficient triclosan degradation - Hantong Qie; Xuan Pan; Daibing Hou; Zihan Wang; Xuedan Cui; Aijun Lin; Jun Cui; Wenjie Yang; Dan Zhao (Chemical Engineering Journal, 2025)

Efficient oxidative cyanation of fructose to nitriles over Acidic-MnO under ambient air pressure - Wenjie Shao; Junpeng Wang; Meiying Niu; Jun Tang; Qiuhong Pan; Ziguo He; Ping Cui; LiFeng Chen; Zhiyong Fang; Qingping Ke (Chemical Engineering Journal, 2025)

Achieving synergistic enhancement in the anaerobic digestion of corn straw by (CH4 + CO2) nanobubbles in conjunction with optimized particle sizes - Zhiqiang Cui; Pengfei Li; Xiaohui Pan; Yongkang Yuan; Gang Li; Youzhou Jiao; Francesco Petracchini; Tingting Hou; Chao He (Bioresource Technology, 2025)

Investigating enhancement of protease and lysozyme combination pretreatment on hydrolysis of sludge organics under humic acid inhibition - Xiang Zou; Junguo He; Xinlei Pan; Qiupeng Cai; Shengye Duan; Yijie Zhong; Xinxin Cui; Jie Zhang (Bioresource Technology, 2025)

The reverse-reduction effect of dissolved organic matter on the degradation of micropollutants induced by halogen radicals (Cl2•- and Br2•-) - Shuangshuang Cheng; Rui Cui; Yangjian Zhou; Yu Lei; Ni Wang; Yanheng Pan; Xin Yang (Water Research, 2025)

Hydrous ferric arsenate transformation coupled with As, Fe, and S environmental cycling in sulfidic systems under anoxic and circumneutral conditions - Xu Ma; Jia Chen; He Chang; Kongyun Zhu; Kedong Ma; Xiaoming Zhao; Jinru Lin; Shuhua Yao; Yubo Cui; Yongfeng Hu; Yuanming Pan; Shaofeng Wang (Science of The Total Environment, 2025)

Evaluation of runoff variability in transboundary basins over High Mountain Asia: Multi-dataset merging based on satellite gravimetry constraint - Jiashuang Jiao; Yuanjin Pan; Xiaoming Cui; Hussein A. Mohasseb; Hao Ding (Remote Sensing of Environment, 2025)

Enzymatic oxidation increases the antibacterial activity of myricetin against Staphylococcus aureus - Jiao Li; Min Sun; Yu Pan; Xiaodong Cui; Chen Li (Food Chemistry, 2025)

Exploration on the cultivar specifity and processing progress of an excellent hybrid tea cultivar ‘Jinmudan’ - Yue Pan; Huiyan Jia; Junyao Li; Yuqing Cui; Wenxuan Yuan; Jun Yang; Rangjian Wang; Wei-Wei Deng (Food Bioscience, 2025)

Potential of probiotic-fermented Flos sophorae as a functional food: Enhanced anti-hyperuricemic activity and modulation of volatile components - Rui Cui; Cong Zhang; Zhen-Hui Pan; Teng-Gen Hu; Hong Wu (Food Bioscience, 2025)

Dy and K double-additive modified Co3O4 catalyst with high resistance to NO for catalyzing N2O decomposition - Haibiao Yu; Yanan Li; Yan Pan; Yuanting Du; Xiaogeng Feng; Junshuo Cui; Zhenning Lou; Weijun Shan; Ying Xiong (Chemical Engineering Journal, 2025)

Ag,Cd double gradient doping at front interface for high efficiency CZTSSe solar cells - Xiu-Chun Guo; Xin-Pan Cui; Ke Sun; Xue-Ying Luo; Wen-Hui Zhou; Dong-Xing Kou; Si-Xin Wu (Chemical Engineering Journal, 2025)

Trends in conductive MOFs for sensing: A review - Lingli Qu; Yiwen Xu; Weikang Cui; Lingjuan Wu; Yi Feng; Yangyang Gu; Hongzhi Pan (Analytica Chimica Acta, 2025)

Determining the geographical origins of goji berries using the Twin-Tower model for Multi-Feature - Jiarui Cui; Cheng Wu; Shibo Pan; Kenken Li; Sijia Liu; Yu Lv; Songlei Wang; Ruiming Luo (Computers and Electronics in Agriculture, 2024)

Green commuting within the x-minute city: Towards a systematic evaluation of its feasibility - Wenxiu Gao; Miaocun Cui; Entong Pan; Becky P.Y. Loo (Journal of Transport Geography, 2024)

A comprehensive review on human enteric viruses in water: Detection methods, occurrence, and microbial risk assessment - Chicheng Yan; Lingli Liu; Tingyuan Zhang; Yaru Hu; Hongchen Pan; Changzheng Cui (Journal of Hazardous Materials, 2024)

Association between indoor PM2.5 components and accelerated biological aging in schizophrenia patients: Evidence from multi-omics mechanisms - Rubing Pan; Xingxu Yi; Yanlong Xu; Jian Song; Weizhuo Yi; Jintao Liu; Rong Song; Xuanxuan Li; Li Liu; Jiajun Yuan; Ning Wei; Yuxing Huang; et al. (Journal of Hazardous Materials, 2024)

Fluid inclusion LA-ICP-MS constraint on hydrothermal evolution of proximal cassiterite-bearing quartz veins in the giant Gejiu orefield: Implications for controls on metallogenic potential of granite-related skarn system - Zhi-Lin Cheng; Pei Ni; Jun-Yi Pan; Liang Han; Wen-Sheng Li; Stefano Albanese; Zhe Chi; Jun-Ying Ding; Jian-Ming Cui (Journal of Geochemical Exploration, 2024)

Construction mechanisms, synthesis strategies, and photocatalytic applications of homojunction catalysts: A review - Hao-wen Zhu; Rui-tang Guo; Qing-shan Wang; Cong Liu; Heng-fei Cui; Ming-yang Liu; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2024)

Carboxylic acid-based deep eutectic solvent for efficient desulfurization: Experimental and computational thermodynamics - Wanxiang Zhang; Pan Xu; Zhengrun Chen; Qinghua Liu; Guoxuan Li; Peizhe Cui (Fuel, 2024)

Characterizing and decoding the key odor compounds of Spirulina platensis at different processing stages by sensomics - Xiao Jia; Hongli Cui; Song Qin; Jingnan Ren; Zhifeng Zhang; Qi An; Nawei Zhang; Jinchu Yang; Yongfeng Yang; Gang Fan; Siyi Pan (Food Chemistry, 2024)

Impact of mutations in carbohydrate binding sites of tandem-repeat type galectin from Takifugu obscurus on its antimicrobial activity - Ying Huang; Li-Fan Cui; Rui Shen; Ding-Yi Chen; Min Jin; Xue Jiao; Yu-Guang Chen; Ming-Xuan Pan; Ya-Dong Hu; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Multifunctional flexible self-supporting film electrode for wearable energy-storage sensing system - Guoju Zhang; Zijian Gao; Chongyang Zhu; Fuhan Cui; Zhenjing Jiang; Rui Pan; Jiaxin Shen; Lin Zhu; Bowen Jiang; Litao Sun; Kuibo Yin (Chemical Engineering Journal, 2024)

Efficacies of vegetation litter and roots in strengthening rainfall infiltration for different stand ages on the Loess Plateau - Fengjiao Niu; Chengzhong Pan; Lan Ma; Yongsheng Cui (CATENA, 2024)

Lysozyme coupling protease pretreatment to relieve the humic acid inhibition on excess sludge anaerobic fermentation - Xiang Zou; Junguo He; Xinlei Pan; Qiupeng Cai; Shengye Duan; Xinxin Cui; Yijie Zhong; Jie Zhang (Bioresource Technology, 2024)

Exosomal miRNA-21 derived from umbilical cord mesenchymal stem cells inhibits microglial overactivation to counteract nerve damage - Lianxu Cui; Dongsheng Li; Junrong Xu; Haomin Li; Yufeng Pan; Jianguo Qiu; Siwei Peng; You Wang; Chen Wang; Jinhui Wang; Guoqiang Chen (Molecular Biology Reports, 2024)

Tripartite-motif 3 represses ovarian cancer progression by downregulating lactate dehydrogenase A and inhibiting AKT signaling - Yu Cong; Xin Cui; Yaqian Shi; Xinxing Pan; Ke Huang; Zhe Geng; Pengfei Xu; Lili Ge; Jin Zhu; Juan Xu; Xuemei Jia (Molecular and Cellular Biochemistry, 2024)

Colletotrichum siamense causing leaf spot on Parthenocissus semicordata in China - Yan Fang; Pan Zhao; Shuqin Wang; Xiaochen Cui; Tao Zhang; Rou Ye; Yongchun Zeng; Yang Zhang (Crop Protection, 2024)

Detecting natural gas storage microleakage based on K-means clustering under constraint of Jeffries-Matusita distance criterion using mobile LiDAR data - Xinda Wang; Kangning Li; Jinbao Jiang; Ximin Cui; Yingyang Pan; Kangni Xiong (Journal of Environmental Management, 2024)

The failure of edge-cracked hard roof in underground mining: An analytical study - Songtao Ji; Xingping Lai; Feng Cui; Yong Liu; Ruikai Pan; Jurij Karlovšek (International Journal of Rock Mechanics and Mining Sciences, 2024)

The intensification of moisture resistance over MFI zeolite via heteroatom incorporation for diluted CO2 capture - Quanli Ke; Pengyun Pan; Mei Lu; Guonan Fang; Wei Zhang; Ruina Zhang; Guokai Cui; Xiaopo Niu; Feng Xiong; Ying Zhou; Bo Zhao; Hanfeng Lu (Fuel, 2024)

Oat β-(1 → 3, 1 → 4)-d-glucan alleviates food allergy-induced colonic injury in mice by increasing Lachnospiraceae abundance and butyrate production - Mingrui Zhang; Yingyue Cui; Pan Liu; Ruixia Mo; Haotian Wang; Yingying Li; Yi Wu (Carbohydrate Polymers, 2024)

Comparative efficacy of alkaline slag, biomass ash, and biochar application for the amelioration of different acidic soils - Ernest Uwiringiyimana; Hong-wei Lai; Ni Ni; Ren-yong Shi; Xiao-ying Pan; Jia-ning Gao; Md Romel Biswash; Jiu-yu Li; Xiu-min Cui; Ren-kou Xu (Plant and Soil, 2024)

Seismic fragility assessment of shield tunnels in liquefiable soil-rock strata using fuzzy method for IM optimization - Xiaoyu Zhang; Yingyi Pan; Lei Su; Entong Ou; Hai Liu; Chao Liu; Jie Cui (Tunnelling and Underground Space Technology, 2024)

Effects of socioeconomic status and regional inequality on the association between PM2.5 and its components and cardiometabolic multimorbidity: A multicenter population-based survey in eastern China - Zhiqian Cui; Xinxu Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Rong Song; Jintao Liu; Rubing Pan; Weizhuo Yi; Xiaoyu Jin; Jian Song; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Safety performance evaluation of offshore high integrity pressure protection system using multiphase dynamic Bayesian network methodology - Yang Yu; Yuqing Liang; Shibo Wu; Baoping Cai; Yu Pan; Ruilong Gao; Siyuan Cheng; Yupeng Cui; Yuheng Yang; Hao Guo (Ocean Engineering, 2024)

Potentially toxic element source apportionment and risk assessment in agricultural soils around a large-scale Pb-Zn mine in Southwest China - Heng Wei; Xuekui Niu; Minmin Li; Canwen Cui; Zhonghua Wei; Wei Long; Man Tang; Hong Yu; Peng Zhang; Liping He; Bo Pan (Journal of Environmental Chemical Engineering, 2024)

Modeling the top-of-atmosphere radiance of alpine snow with topographic effects explicitly solved - Gongxue Wang; Lingmei Jiang; Fangbo Pan; Huizhen Cui; Shuhua Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Enzymatic synthesis and sensory evaluation of the novel kokumi compound N-butyryl phenylalanine - Lei Cai; Yuqin Cheng; Yuqing Pan; Lu Wang; Xu Zhao; Wenxiang Gao; Pimiao Huang; Chun Cui (Food Chemistry, 2024)

Preparation of presulfided oil-soluble NiMo catalyst for slurry bed hydrocracking of vacuum residue - Bin Liu; Hongyang Lv; Xingxing Cui; Guangzheng Sun; Xu Zhang; Bin Dong; Yichuan Li; Yuan Pan; Yongming Chai; Chenguang Liu (Chemical Engineering Journal, 2024)

Shining light on atomic vacancies in electrocatalysts for boosted water splitting - Mingpeng Chen; Huachuan Sun; Qingjie Lu; Dequan Li; Di Liu; Tong Zhou; Baoye Zi; Hongshun Zheng; Bin Xiao; Tianwei He; Jianhong Zhao; Yumin Zhang; et al. (Chemical Engineering Journal, 2024)

The MYB transcription factor PpMYB5 regulates Pp4CL1/Pp4CL2 expression to promote lignin biosynthesis of fruit russeting in the flat nectarine - Yule Miao; Wenyi Duan; Ang Li; Mingzhu Yuan; Junren Meng; Hongmei Wang; Lei Pan; Shihang Sun; Guochao Cui; Caiyun Shi; Liang Niu; Wenfang Zeng (Plant Cell Reports, 2024)

Tracing the magmatic-hydrothermal evolution of the Xianghualing tin-polymetallic skarn deposit, South China: Insights from LA-ICP-MS analysis of fluid inclusions - Yong-Kang Chen; Pei Ni; Jun-Yi Pan; Jian-Ming Cui (Mineralium Deposita, 2024)

Modeling and Analysis of Resistance-Sensing Characteristics for Two-Way Shape Memory Alloy-Based Deep-Sea Actuators - Jian Guo; Binbin Pan; Weicheng Cui; Huiming Xiang (Journal of Marine Science and Engineering, 2024)
Deep-sea actuators based on shape memory alloys (SMAs) are an emerging frontier field of multidisciplinary crossover, and the resistive sensing characteristics are the basis for the drive control of SMA deep-sea actuators. The resistance and resistivity of SMAs are complex and highly dependent on temperature and stress, and there is no complete description of SMAs for extreme environments of high pressure, low temperature, and high salinity in the deep sea. In this study, the logistic function is introduced to improve the kinetic equation of phase transition, and the macromechanical model, the law of resistance, and the resistivity mixing rule are integrated to model and analyze the resistive self-awareness characteristics of two-way shape memory alloy deep-sea actuators. The complex coupling relationships among resistance, strain, stress, resistivity, and temperature under constant load conditions are investigated, and the validity of the resistance-sensing model is verified by the water bath cycling test. The results show that the predicted values of the model agree well with the measured values. The self-perceived relationship between the resistance and deformation of the two-way shape memory alloy can be effectively expressed, which provides theoretical model support for the design of memory alloy deep sea actuators and sensorless drive control.

Plastic particles and fluorescent brightener co-modify Chlorella pyrenoidosa photosynthesis and a machine learning approach predict algae growth - Yaodan Dai; Zhi Guo; Xingpan Guo; Rui Deng; Lele Li; Ting Fan; Kangping Cui; Tao Pan (Journal of Hazardous Materials, 2024)

ALCSF: An adaptive and anti-noise filtering method for extracting ground and top of canopy from ICESat-2 LiDAR data along single tracks - Bingtao Chang; Hao Xiong; Yuan Li; Dong Pan; Xiaodong Cui; Wuming Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Soil texture contributes to shaping comammox Nitrospira communities in rice-wheat rotation soils - Zhiying Guo; Jie Liu; Luyuan Sun; Xiaodan Cui; Guiping Ye; Jia Liu; Xianzhang Pan; Yongxin Lin (European Journal of Soil Biology, 2024)

Large-scale additive fabrication of tough nanocellulose yarns - Yanduo Zhai; Yande Cui; Meng Zhou; Pan Chen; Chunyu Chang; Jinghua Chen (Chemical Engineering Journal, 2024)

Autocatalytic oxidation of thiophene derivatives and co-degradation of refractory contaminants in Fenton reaction - Yaodan Cui; Yini He; Ying Jin; Zhichao Yang; Chao Shan; Qingrui Zhang; Weiming Zhang; Bingcai Pan (Chemical Engineering Journal, 2024)

Intestinal lymphatic transport of Smilax china L. pectic polysaccharide via Peyer's patches and its uptake and transport mechanisms in mononuclear phagocytes - Junxi Liu; Xiaoke Zhang; Yan Liu; Zhijing Wu; Zheng Cui; Xianglin Pan; Yuheng Zheng; Jinglin Wang; Kaiping Wang; Yu Zhang (Carbohydrate Polymers, 2024)

Research trends and prospects for hydrogen production from sludge fermentation: based on bibliometric analysis - Yunchuan Pan; Jiao Tao; Shijie Yang; Jianguo Cui; Jian Xiong; Xuebin Lu (Waste Disposal & Sustainable Energy, 2024)

New Method for Calculating Soil Pressure on Shallow Underground Structures in Layered Soil - Yingdong Pan; Xiaojun Zhou; Shi Han; Lu Zhang; Pengbo Cui (Geotechnical and Geological Engineering, 2024)

Process, advances, and perspectives of graphene oxide-SELEX for the development of aptamer molecular probes: A comprehensive review - Zhuoer Chen; Ying Yang; Xinge Cui; Luwei Chai; Hongbing Liu; Yangwei Pan; Yongkang Zhang; Yujia Xie; Tao Le (Analytica Chimica Acta, 2024)

A novel zwitterionic magnetic nanocomposite developed for non-invasive speciation analysis of inorganic chromium - Faisal Faiz; Yi-fan Pan; Sen Zhang; Jinxia Dai; Jun-qin Qiao; Hong-zhen Lian; Li Mao; Xiao-bing Cui (Journal of Hazardous Materials, 2024)

The gelling properties of fish gelatin as improved by ultrasound-assisted phosphorylation - Yong Wang; Qinan Cui; Xiuqin Wang; Caiyun Wu; Xianbing Xu; Xiuping Dong; Jinfeng Pan (Food Chemistry, 2024)

Differential polyvalent passive immune protection of egg yolk antibodies (IgY) against live and inactivated Vibrio fluvialis in fish - Xiang Liu; Huihui Xiao; Pan Cui; Jing Chen; Jia Chao; Xiaoqing Wu; Juan Lu; Xiaoying Zhang; Gaoxiao Xu; Yong Liu (Fish & Shellfish Immunology, 2024)

Study of Water Resource System Adaptability Based on the Connection Number and Three-Dimensional Risk Matrix - Pan Zhengwei; Cui Yunhui; Zhou Yuliang; Zhou Ping; Wang Jing (Water Resources Management, 2024)

A computational efficient approach for multi-GNSS real-time precise clock estimation with undifferenced ambiguity resolution - Xiang Zuo; Pan Li; Bobin Cui; Maorong Ge; Harald Schuh (Journal of Geodesy, 2024)

Adaptive Integrated Coastal Zone Planning: History, Challenges, Advances, and Perspectives - Xinyi Wang; Fenzhen Su; Xuege Wang; Tingting Pan; Yikun Cui; Vincent Lyne; Fengqin Yan (Chinese Geographical Science, 2024)

A Comparison of Polyvalent Passive Immunoprotection from Antibodies with Different Immunity Models of Live or Inactivated Vibrio fluvialis in Fish - Huihui Xiao; Pan Cui; Jing Chen; Xiaohui Han; Ziye Ma; Chen Chen; Yong Liu; Xiang Liu (Fishes, 2024)
Polyvalent passive vaccines can act fast in resisting various bacteria with good efficacy, and they have application value in aquaculture. This study prepared live and inactivated Vibrio fluvialis mouse antisera (L-VF-antiserum and I-VF-antiserum), and administered them to goldfish (Carassius auratus) infected with V. fluvialis and Aeromonas hydrophila. The passive protective rates of live and inactivated mouse antisera against V. fluvialis were 60% (p

Paraspeckles / CARM1 mediates the regulation of OEVs on cell differentiation during in vitro embryonic development of yak - Jinglei Wang; Yan Cui; Meng Wang; Wenbin Ma; Libin Wang; Sijiu Yu; Yangyang Pan (Theriogenology, 2024)

Biomass power generation: A pathway to carbon neutrality - Wei Du; Zhanpeng Cui; Jinze Wang; Yiming Qin; Jianhuai Ye; Nan Lin; Yuanchen Chen; Wenyan Duan; Zhaofeng Chang; Hao Li; Peng Zhang; Bo Pan (Science of The Total Environment, 2024)

Simulated in vitro infant digestion and lipidomic analysis to explore how the milk fat globule membrane modulates fat digestion - Yue Pan; Yibo Liu; Jiayi Zhao; Liqin Cui; Xiaodong Li; Lu Liu; Kouadio Jean Eric-Parfait Kouame; Zhong Wang; Xin Tan; Yanxi Jiang; Chao Gao (Food Chemistry, 2024)

Novel a-linolenic acid emulsions stabilized by octenyl succinylated starch -soy protein-epigallocatechin-3-gallate complexes: Characterization and antioxidant analysis - Tenglong Geng; Lidan Pan; Xiaorui Liu; Die Dong; Bo Cui; Li Guo; Chao Yuan; Meng Zhao; Haibo Zhao (Food Chemistry, 2024)

Debris flow susceptibility and hazard assessment in Fushun based on hydrological response units - Shanjun Liu; Shiyao Liu; Donglin Lv; Lianhuan Wei; Meng Ao; Xingyu Pan; Bing Li; Yuan Cui; Lun Wang; Xin He (Natural Hazards, 2024)

Synergizing meat Science and AI: Enhancing long-chain saturated fatty acids prediction - Jiarui Cui; Yu Lv; Sijia Liu; Shibo Pan; Kenken Li; Shuang Gao; Ruiming Luo; Hao Wu; Zhongxiong Zhang; Songlei Wang (Computers and Electronics in Agriculture, 2024)

The dehydration-responsive protein PpFAS1.3 in moss Physcomitrium patens plays a regulatory role in lipid metabolism - Zhenyu Qi; Chen Liu; Ning Wang; Jipeng Cui; Jia Hu; Ruoqing Gu; Le Meng; Pan Wang; Jianan Zhai; Guanghou Shui; Suxia Cui (Journal of Plant Physiology, 2024)

Design and development of dual-extruder food 3D printer based on selective compliance assembly robot arm and printing of various inks - Jingfu Pan; Xiaochen Chen; Yulin Zhu; Baoguo Xu; Changzhu Li; Myat Noe Khin; Haiying Cui; Lin Lin (Journal of Food Engineering, 2024)

Ruthenium decorated nickel-iron layered double hydroxides (NiFe-LDH) for promoting peroxymonosulfate activation and atrazine degradation - Yu Yin; Shuting Pan; Jiajie Lu; Abdul Hannan Asif; Sheng Cui; Shaobin Wang; Hongqi Sun (Journal of Environmental Chemical Engineering, 2024)

Effect of pyrolysis atmospheres on gaseous products evolution of coal pyrolysis at high temperature - Yaning Wu; Shu Tao; Zhiheng Wang; Yi Cui; Qinghe Jing; Wei He; Jie Guo; Lianfu Hai; Zhejun Pan (Fuel, 2024)

Mechanism of catalytic subcritical water oxidation of m-nitroaniline and nitrogen conversion by CuCo2O4 catalyst - Mian Hu; Meiqi Chen; Zhibin Li; Zhiheng Ye; Zhong-Ting Hu; Zhiyan Pan; Dabin Guo; François Nkinahamira; Jinling Wan; Libo Wu; Baihui Cui; Junliang Wang (Chemical Engineering Journal, 2024)

Patterns and determinants of calcium concentrations in forest litter and different soil horizons in warm-temperate China - Feng Xue; Ning Pan; Hongkun Cui; Mingfei Zhao; Kaixiong Xing; Yuhang Wang; Xuejuan Bai; Jingze Liu; Muyi Kang (CATENA, 2024)

Concentration, composition and exposure risk assessment of particulate matter with different particle sizes in subway stations - Xinru Wang; Xin Meng; Li Chang; Fei Pei; Taocheng Wan; Tong Cui; Yiqiao Liu; Song Pan (Building and Environment, 2024)

A hybrid learning approach to model the diversity of window-opening behavior - Yiqiao Liu; Wen Tong Chong; Yat Huang Yau; Jinshun Wu; Yufan Chang; Tong Cui; Li Chang; Song Pan (Building and Environment, 2024)

Sugarcane borers: species, distribution, damage and management options - Ao-Mei Li; Zhong-Liang Chen; Fen Liao; Yong Zhao; Cui-Xian Qin; Miao Wang; You-Qiang Pan; Shao-Long Wei; Dong-Liang Huang (Journal of Pest Science, 2024)
Lepidopteran borers stand out as the most destructive pests in sugarcane, leading to reductions in stalk weight, juice quality and sugar recovery. Presently, integrated pest management (IPM) systems are utilized for sugarcane borer management, employing diverse methods encompassing cropping system, chemical pesticides, behavioral manipulation, biological agents and the selection of resistant varieties. However, the effectiveness of this strategy remains controversial due to concerns about harmful residues, formulation limitations, environmental variability, labor shortages and increased input costs. Currently, multiple lines of transgenic sugarcane expressing insecticidal genes from the bacterium Bacillus thuringiensis (Bt) have been developed globally, offering the prospect of increases production with reduced pesticides application, thereby eliminating the negative effect of IPM. In Brazil, the first genetically modified sugarcane cultivars resistant to the sugarcane borer have been approved and released for commercial cultivation, shedding a bright light on a viable solution for sugarcane borers. This paper reviews borer species and distribution, the significant damage caused by sugarcane borers, current control approaches and the future effective control strategies. Additionally, this work provides comprehensive understanding on Bt sugarcane, serving as an additional tool to complement conventional sugarcane borers control resistance programs.

Machine to brain: facial expression recognition using brain machine generative adversarial networks - Dongjun Liu; Jin Cui; Zeyu Pan; Hangkui Zhang; Jianting Cao; Wanzeng Kong (Cognitive Neurodynamics, 2024)

Application and Comparison of Different Regression Models in Iodine Balance Experiment on Women of Childbearing Age and Pregnant Women - Yu Wang; Xiaoxiao Tian; Qiuyi Song; Wenqiang Wang; Xiaohui Guo; Tingkai Cui; Ziyun Pan; Yongjie Chen; Wen Chen; Long Tan; Wanqi Zhang (Biological Trace Element Research, 2024)

Recent progress in mesenchymal stem cell-based therapy for acute lung injury - Jinfeng Liang; Weiyou Dai; Shihang Xue; Feifei Wu; Enhai Cui; Ruolang Pan (Cell and Tissue Banking, 2024)

DNMT1 driven by mouse amniotic fluid mesenchymal stem cell exosomes improved corneal cryoinjury via inducing microRNA-33 promoter DNA hypermethylation modification in corneal epithelium cells - Weiqi Xu; Xinfeng Fei; Zeyu Cui; Dikang Pan; Yan Liu; Te Liu (Human Cell, 2024)

Spatial response of urban land use intensity to ecological networks: a case study of Xi'an Metropolitan Region, China - Yaotao Xu; Peng Li; Jinjin Pan; Nibing Gong; Zixuan Yan; Junfang Cui; Binhua Zhao (Environmental Science and Pollution Research, 2024)

Climate change intensifies algal biomass resurgence in eutrophic Lake Taihu, China - Ting Pan; Chixiao Cui; Boqiang Qin; Kan Ding; Jian Zhou (Science of The Total Environment, 2024)

Characteristics of second-hand exposure to aerosols from e-cigarettes: A literature review since 2010 - Tong Cui; Rui Lu; Chuan Liu; Zehong Wu; Xingtao Jiang; Yiqiao Liu; Song Pan; Yanpeng Li (Science of The Total Environment, 2024)

Multi-performance reliability-based concept-detailed co-design of offshore structures using modified conjugate FR algorithm - Yupeng Cui; Yang Yu; Siyuan Cheng; Mingxiu Wei; Yu Pan; Zewei Dong (Ocean Engineering, 2024)

Robust remote sensing retrieval of key eutrophication indicators in coastal waters based on explainable machine learning - Liudi Zhu; Tingwei Cui; A Runa; Xinliang Pan; Wenjing Zhao; Jinzhao Xiang; Mengmeng Cao (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Atomic insights into the thermal degradation of polyethylene terephthalate combining STA-FTIR and DFT methods - Linquan Gong; Yong Pan; Ling Cui; Xin Zhang (Fuel, 2024)

Nanoengineered M1 macrophages enhance photodynamic therapy of melanoma through oxygen production and subsequent antitumor immunity - Xinyue Zhang; Leilei Bao; Zhiliang Yu; Fengze Miao; Lisha Li; Zhen Cui; Huijun Pan; Zhiyu Qian; Tingrui Zhang; Yujing Zhao; Zongguang Tai; Quangang Zhu; et al. (Chemical Engineering Journal, 2024)

Characterization of whole genomes from recently emerging Mpox cases in several regions of China, 2023 - Changcheng Wu; Lunbiao Cui; Yang Pan; Ziquan Lv; Mingxiao Yao; Wenling Wang; Fei Ye; Weibang Huo; Li Zhao; Baoying Huang; Fengcai Zhu; Roujian Lu; et al. (Science China Life Sciences, 2024)

Optimization Analysis of the Arrangement of the Submerged Floating Tunnel Subjected to Waves - Wenbo Pan; Cheng Cui; Chun Chen; Mingxiao Xie; Qian Gu; Zhiwen Yang (Journal of Marine Science and Engineering, 2024)
The motion responses, mooring tensions, and submergence depth are the dominant factors for the arrangement of the Submerged Floating Tunnel (SFT) subjected to waves. Generally, the maximum values of motion responses, mooring tensions, and absolute submergence depth are mainly focused on. In the present study, experiments are implemented to measure the motion responses and mooring tensions of the SFT with different mooring patterns and submergence depths under waves with different characteristic wave heights and periods. In order to evaluate the arrangement of the SFT more effectively and comprehensively, besides the maximum values, several new characteristic parameters are introduced. Such parameters account for the motion responses in the frequency domain, the uniformity of the tension distribution, the length of time during which the cable reaches a relaxed condition during wave action, the KC number, the dimensionless period, the wave height, and the submergence depth. The results from the optimization analysis show the following: according to the characteristic values of motion responses and mooring tensions, the pattern of diagonal cables is better than that of diagonal cables + vertical cables; and within the range of the present experiments, there are optimal dimensionless parameters—the dimensionless submergence depth d0/LP ≥ 0.15, the KC number ≤ 0.8, or the dimensionless wave height Hs/d0 ≤ 0.10—for the condition of which the dynamic responses and mooring tensions vary slightly.

Isolation and absolute configuration of alkylpyridine alkaloids from the marine sponge Hippospongia lachne - Dong-Xue Fan; Xiang-Chao Luo; Ya-Fang Ding; Li-Yun Liu; Xin Wang; Jia-Yan Pan; Yuan-Yuan Ji; Jie Wang; Cui Li; Li-Li Hong; Hou-Wen Lin (Phytochemistry, 2024)

Fluid inclusion constraint on sulfide precipitation in wolframite-quartz veins: A case study of the giant Dajishan W polymetallic deposit, South China - Jian-Ming Cui; Pei Ni; Jun-Yi Pan; Wen-Sheng Li (Journal of Geochemical Exploration, 2024)

Hierarchical interface design of jute fibers/polypropylene composites for enhanced interfacial and mechanical properties - Yun Yang; Haoran Zhang; Xuan Liu; Yuheng Deng; Mengjuan Sun; Jinfeng Wang; Yihua Cui; Lei Pan; Zhong Chen (Journal of Cleaner Production, 2024)

Promoted O2 resistant performance of CO selective catalytic reduction via carbon-coated CuCoAl mixed metal oxides - Keke Pan; Yonghua Yao; Dan Cui; Fei Gao; Minmin Liu; Jianming Dan; Bin Dai; Xuhong Guo; Yanwen Zhang; Feng Yu (Journal of Environmental Chemical Engineering, 2024)

Biomimetic engineered nanoparticles target drug-resistant tumor cells and heterogeneous blood vessels for combination therapy of osteosarcoma - Wenbo Yang; Yongzhi Cui; Qing Pan; Yizhong Peng; Kanglu Li; Wei Huang; Yan Zhang; Hongzhi Hu; Zengwu Shao; Zhicai Zhang (Chemical Engineering Journal, 2024)

Cryogenian and Ediacaran integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Lang Sun; Malik Muhammad Saud Sajid Khan; Chuan Yang; Zhixin Sun; Bing Pan; Shehryar Ahmed; Lanyun Miao; Weichen Sun; Chunlin Hu; Xiaojuan Sun; Cui Luo; Bo Chen; et al. (Science China Earth Sciences, 2024)

uw-WiFi: Small-Scale Data Collection Network-Based Underwater Internet of Things - Jifeng Zhu; Xiaohe Pan; Zheng Peng; Mengzhuo Liu; Jingqian Guo; Jun-Hong Cui (Journal of Marine Science and Engineering, 2024)
The establishment of the Underwater Internet of Things (UIoT) and the realization of interconnection between heterogeneous underwater intelligent devices are urgent global challenges. Underwater acoustic networking is the most suitable technology to achieve UIoT for medium to long ranges. This paper presents an underwater Wi-Fi network, called uw-WiFi, that utilizes a master–slave mode architecture. uw-WiFi is dedicated to solving the problem of underwater acoustic networking with limited coverage range and number of nodes. To ensure the reliability of different types of data in the network, a reliable segmentation transmission protocol based on data type is designed. Additionally, on-demand scheduling based on the reservation MAC protocol is developed to solve the channel resource sharing problem. The uw-WiFi system has undergone shallow sea tests, and the experimental results demonstrate that the uw-WiFi network is capable of achieving a network throughput of 500 bps or higher, indicating superior network performance.

Mogroside V alleviates the heat stress-induced disruption of the porcine oocyte in vitro maturation - Ke Peng; Kexin Cui; Pan Li; Xinxin Liu; Ya Du; Huiyan Xu; Xiaogan Yang; Shengsheng Lu; Xingwei Liang (Theriogenology, 2024)

A ground-independent method for obtaining complete time series of in situ evapotranspiration observations - Wangyipu Li; Zhaoyuan Yao; Xiaoduo Pan; Zhihao Wei; Bo Jiang; Jing Wang; Ming Xu; Yaokui Cui (Journal of Hydrology, 2024)

Occurrence and cycle of dissolved iron mediated by humic acids resulting in continuous natural photodegradation of 17α-ethinylestradiol - Danni Cui; Huan He; Wenxiao Xie; Shanshan Yang; Ziwei Guo; Zhicheng Liao; Feng Liu; Chaochao Lai; Xiaomin Ren; Bin Huang; Xuejun Pan (Journal of Hazardous Materials, 2024)

Green space and its types can attenuate the associations of PM2.5 and its components with prediabetes and diabetes—— a multicenter cross-sectional study from eastern China - Zhiqian Cui; Rubing Pan; Jintao Liu; Weizhuo Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Li Liu; Ning Wei; Rong Song; Jiajun Yuan; et al. (Environmental Research, 2024)

A novel evaluation indicator and optimal heating strategy for using an intermittent-operation catalytic combustion heater in open cold environments - Mingyuan Qin; Bee Teng Chew; Yat Huang Yau; Xiaofei Han; Zhen Yang; Tong Cui; Fei Deng; Song Pan (Building and Environment, 2024)

Preparation, characterization, and synergistic soil moisture retention effects of a by-product-based dust suppressant for fugitive dust suppression - Shuhao Zhang; Xiufeng Cao; Wenxiu Xue; Wenhan Liu; Yongkang Guo; Tao Li; Xiaowei Cui; Huitian Duan; Shaolei Shan; Rudong Pan; Jia Liu; Zhaojie Cui (Atmospheric Pollution Research, 2024)

Coastal distribution and driving factors for blue carbon fractions in the surface soil of a warm-temperate salt marsh in China - Ziwen Ma; Yanan Wu; Yuan Cui; Yueyan Pan; Siqi Zhao; Jiakai Liu; Zhenming Zhang; Mingxiang Zhang (Chemosphere, 2024)

Moored underwater docking system for resident UUVs with acoustic guidance: Design and experiment - Jingqian Guo; Mengzhuo Liu; Xiaohe Pan; Jifeng Zhu; Jun Liu; Hongli Xu; Zheng Peng; Jun-Hong Cui (Ocean Engineering, 2024)

Biomonitoring of glyphosate and aminomethylphosphonic acid: Current insights and future perspectives - Xin Wei; Yanan Pan; Ziqi Zhang; Jingyi Cui; Renli Yin; Huashou Li; Junhao Qin; Adela Jing Li; Rongliang Qiu (Journal of Hazardous Materials, 2024)

How does demographic transition affect energy conservation? Evidences from the resource effects of global demographic transition - Zhibao Wang; Zhilong Pan; Zhimei Xu; Xin Cui; Xiaoping Zhang (Journal of Cleaner Production, 2024)

Hydrocarbon adsorption mechanism of modern automobile engines and methods of reducing hydrocarbon emissions during cold start process: A review - Zhiqing Zhang; Weihuang Zhong; Dongli Tan; Shuwan Cui; Mingzhang Pan; Ziheng Zhao; Jian Zhang; Jingyi Hu (Journal of Environmental Management, 2024)

Denitration performance and mechanism of Mn-Ce supported alkali-modified fly ash catalysts for NH3-SCR - Pan Zhang; Wohui Yu; Bing Gao; Shaoping Cui; Jingxin Li; Liqiang Qi (Fuel, 2024)

Antioxidative bioactive glass reinforced injectable hydrogel with reactive oxygen species scavenging capacity for diabetic wounds treatment - Hao Chang; Pengfei Tian; Liuzhi Hao; Chengwei Hu; Bo Liu; Fengzhen Meng; Xin Yi; Xiaohua Pan; Xiaohua Hu; Huan Wang; Xinyun Zhai; Xu Cui; et al. (Chemical Engineering Journal, 2024)

OsNAC103, an NAC transcription factor negatively regulates plant height in rice - Yan Li; Liming Zhao; Chiming Guo; Ming Tang; Wenli Lian; Siyu Chen; Yuehan Pan; Xiaorong Xu; Chengke Luo; Yin Yi; Yuchao Cui; Liang Chen (Planta, 2024)
Main conclusion OsNAC103 negatively regulates rice plant height by influencing the cell cycle and crosstalk of phytohormones. Abstract Plant height is an important characteristic of rice farming and is directly related to agricultural yield. Although there has been great progress in research on plant growth regulation, numerous genes remain to be elucidated. NAC transcription factors are widespread in plants and have a vital function in plant growth. Here, we observed that the overexpression of OsNAC103 resulted in a dwarf phenotype, whereas RNA interference (RNAi) plants and osnac103 mutants showed no significant difference. Further investigation revealed that the cell length did not change, indicating that the dwarfing of plants was caused by a decrease in cell number due to cell cycle arrest. The content of the bioactive cytokinin N 6 -Δ 2 -isopentenyladenine (iP) decreased as a result of the cytokinin synthesis gene being downregulated and the enhanced degradation of cytokinin oxidase. OsNAC103 overexpression also inhibited cell cycle progression and regulated the activity of the cell cyclin OsCYCP2;1 to arrest the cell cycle. We propose that OsNAC103 may further influence rice development and gibberellin–cytokinin crosstalk by regulating the Oryza sativa homeobox 71 ( OSH71 ). Collectively, these results offer novel perspectives on the role of OsNAC103 in controlling plant architecture.

Connecting the mechanisms of tumor sex differences with cancer therapy - Huan Li; Weibo Jiang; Shui Liu; Manshi Yang; Siyuan Chen; Yihan Pan; Mengying Cui (Molecular and Cellular Biochemistry, 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

An analysis and prediction of carbon emissions in the sphere of consumer lifestyles in Beijing - Tiening Cui; Keru Pan (Environmental Science and Pollution Research, 2024)

Emissions of nitrated and oxygenated polycyclic aromatic hydrocarbons bound to coarse particles from solid fuel combustion - Yaoxing Feng; Jinze Wang; Jie Sun; Zhanpeng Cui; Qi Chen; Kang Mao; Yali Lei; Peng Zhang; Wei Du; Jianwu Shi; Bo Pan (Chemosphere, 2024)

A novel study on influence of ground surface boundary conditions on thermal performance of vertical U-shaped ground heat exchanger - Linrui Jia; Lin Lu; Ping Cui; Jianheng Chen; Aiqiang Pan (Sustainable Cities and Society, 2024)

High capillary effect and solar dual-drive nanofibrillated cellulose aerogels for efficient crude oil spill cleanup - Bingjie Fan; Xueming Bao; Shanshan Pan; Ying Liu; Yuanyuan Yu; Li Cui; Qiang Wang; Ping Wang (Chemical Engineering Journal, 2024)

Antimicrobial peptide dendrimers assisted Nanocomposite-Loaded lyotropic liquid crystalline for multimodal surgical site infection management - Xiao Yue; Ziqiao Zhong; Chen Wang; Ziyu Zhao; Xuejuan Zhang; Guanlin Wang; Wenhao Wang; Xiao Xia; Ziqiang Zhou; Yingtong Cui; Ying Huang; Chuanbin Wu; et al. (Chemical Engineering Journal, 2024)

Self-polarization-enhanced oxygen evolution reaction by flower-like core–shell BaTiO3@NiFe-layered double hydroxide heterojunctions - Shuang Wang; Kai Ge; He Cui; Shunli Li; Yongfang Yang; Mingwang Pan; Lei Zhu (Chemical Engineering Journal, 2024)

Sr-Nd isotopic compositions of aeolian sand in the northern Ulan Buh Desert and Yamalik Desert: Implications for provenance and transport processes - Weiyuan Kong; Shangzhe Zhou; Guipeng Cui; Pan Gao; Shuai Li; Qi Lu (CATENA, 2024)

An investigation of the PM2.5 concentrations and cumulative inhaled dose during subway commutes in Changchun, China - L. Chang; W. T. Chong; Y. H. Yau; T. Cui; X. R. Wang; F. Pei; Y. Q. Liu; S. Pan (International Journal of Environmental Science and Technology, 2024)

Deciphering microbiomes dozens of meters under our feet and their edaphoclimatic and spatial drivers - Haoran He; Jingxiong Zhou; Yunqiang Wang; Shuo Jiao; Xun Qian; Yurong Liu; Ji Liu; Ji Chen; Manuel Delgado‐Baquerizo; Albert C. Brangarí; Li Chen; Yongxing Cui; et al. (Global Change Biology, 2024)
Microbes inhabiting deep soil layers are known to be different from their counterpart in topsoil yet remain under investigation in terms of their structure, function, and how their diversity is shaped. The microbiome of deep soils (>1 m) is expected to be relatively stable and highly independent from climatic conditions. Much less is known, however, on how these microbial communities vary along climate gradients. Here, we used amplicon sequencing to investigate bacteria, archaea, and fungi along fifteen 18‐m depth profiles at 20–50‐cm intervals across contrasting aridity conditions in semi‐arid forest ecosystems of China's Loess Plateau. Our results showed that bacterial and fungal α diversity and bacterial and archaeal community similarity declined dramatically in topsoil and remained relatively stable in deep soil. Nevertheless, deep soil microbiome still showed the functional potential of N cycling, plant‐derived organic matter degradation, resource exchange, and water coordination. The deep soil microbiome had closer taxa–taxa and bacteria–fungi associations and more influence of dispersal limitation than topsoil microbiome. Geographic distance was more influential in deep soil bacteria and archaea than in topsoil. We further showed that aridity was negatively correlated with deep‐soil archaeal and fungal richness, archaeal community similarity, relative abundance of plant saprotroph, and bacteria–fungi associations, but increased the relative abundance of aerobic ammonia oxidation, manganese oxidation, and arbuscular mycorrhizal in the deep soils. Root depth, complexity, soil volumetric moisture, and clay play bridging roles in the indirect effects of aridity on microbes in deep soils. Our work indicates that, even microbial communities and nutrient cycling in deep soil are susceptible to changes in water availability, with consequences for understanding the sustainability of dryland ecosystems and the whole‐soil in response to aridification. Moreover, we propose that neglecting soil depth may underestimate the role of soil moisture in dryland ecosystems under future climate scenarios.

MiR-23a promotes autophagy of yak cumulus cells to alleviate apoptosis via the apoptosis signal-regulating kinase 1/c-Jun N-terminal kinase pathway - Xiaohong Han; Sijiu Yu; Yan Cui; Jingjing Li; Jiangfeng Fan; Libin Wang; Meng Wang; Yangyang Pan; Gengquan Xu (Theriogenology, 2023)

A strong, biodegradable, and closed-loop recyclable bamboo-based plastic substitute enabled by polyimine covalent adaptable networks - Lan Cui; Mingrui Pan; Yu Zhou; Haiyan Xu; Liping Ning; Shanshan Jia; Xiaohui Wang; Zhiping Su (Chemical Engineering Journal, 2023)

Hydrothermal carbonization of food waste for sustainable biofuel production: Advancements, challenges, and future prospects - Shuang Wu; Qing Wang; Minghui Fang; Dongyang Wu; Da Cui; Shuo Pan; Jingru Bai; Faxing Xu; Zhenye Wang (Science of The Total Environment, 2023)

PM1 exposure and spatial transmission of nicotine from the simulated second-hand vapor of pod-based electronic cigarettes - Tong Cui; Rui Lu; Qianyun Liu; Xingtao Jiang; Yanpeng Li; Song Pan (Science of The Total Environment, 2023)

Different responses of precipitation patterns to the East Asian summer monsoon weakening: The 7.2 and 8.2 ka events - Liangkang Pan; Jingyao Zhao; Yan Yang; Kexin Wang; Carlos Pérez-Mejías; Jiahui Cui; Xiyu Dong; Rui Zhang; Hai Cheng (Quaternary Science Reviews, 2023)

Lanostane triterpenoids from mycelia-associated Ganoderma sinense and their anti-inflammatory activity - Liming Teng; Chan Wang; Baokai Cui; Jingsong Zhang; Shuai Zhou; Xinhua Pan; Feng Pan; Yucheng Dai; Na Feng (Phytochemistry, 2023)

Residues of sulfoxaflor and its metabolites in floral and extrafloral nectar from Hibiscus rosa-sinensis L. (Malvaceae) with or without co-application of tebuconazole - Hong-Xia Zhou; Man-Huan Cheng; Juan-Lin Pan; Peng Cui; Yue-Qin Song; Ying Yu; Jun Cao; Hong-Guang Zha (Pesticide Biochemistry and Physiology, 2023)

Pore connectivity and microfracture characteristics of Longmaxi shale in the Fuling gas field: Insights from mercury intrusion capillary pressure analysis - Xiang Zhao; Mengdi Sun; Chima Finnian Ukaomah; Mehdi Ostadhassan; Ziang Cui; Bo Liu; Zhejun Pan (Gas Science and Engineering, 2023)

Functional-structural decoupling in visual network is associated with cognitive decline in patients with type 2 diabetes mellitus: evidence from a multimodal MRI analysis - Min-Hua Ni; Ying Yu; Yang Yang; Ze-Yang Li; Teng Ma; Hao Xie; Si-Ning Li; Pan Dai; Xin-Yu Cao; Yan-Yan Cui; Jun-Ling Zhu; Guang-Bin Cui; et al. (Brain Imaging and Behavior, 2023)

SlbHLH152, a bHLH transcription factor positively regulates iron homeostasis in tomato - Xiaoli Li; Haohao Cao; Deshui Yu; Kedong Xu; Yi Zhang; Xinxin Shangguan; Xiaohong Zheng; Zhongzhou Yang; Chaoqiong Li; Xingchen Pan; Yiming Cui; Zhiqing Zhang; et al. (Plant Science, 2023)

Short-term responses of macroinvertebrate assemblages to the “ten-year fishing ban” in the largest highland lake of the Yangtze basin - Lu Yang; Min Pan; Jingrui Sun; Yongde Cui; Jinyan Dong; Jiaojiao Yang; Songhao Ji; Juan Tao; Chengzhi Ding (Journal of Environmental Management, 2023)

Reflection characteristics of typical road defects in 3D GPR images for collapse mitigation - Jingwen Pan; Zhenshi Shi; Xu Meng; Yunpeng Yue; Caide Lin; Jie Chen; Hai Liu; Jie Cui (Journal of Applied Geophysics, 2023)

Advances and applications of machine learning and deep learning in environmental ecology and health - Shixuan Cui; Yuchen Gao; Yizhou Huang; Lilai Shen; Qiming Zhao; Yaru Pan; Shulin Zhuang (Environmental Pollution, 2023)

Characterization and fine mapping analysis of a major stable QTL qKnps-4A for kernel number per spike in wheat - Ran Qin; Tianhang Ma; Yibiao Cai; Xinyao Shi; Jiajia Cheng; Jizi Dong; Chenyang Wang; Shihui Li; Guoqing Pan; Yuxiang Guan; Lei Zhang; Shuang Yang; et al. (Theoretical and Applied Genetics, 2023)

Exploring the role of PPP–RTK network configuration: a balance of server budget and user performance - Jiahuan Hu; Bobin Cui; Pan Li; Sunil Bisnath; Kai Zheng (GPS Solutions, 2023)
With atmospheric corrections generated from the server, precise point positioning real-time kinematic (PPP–RTK) can achieve high-precision solutions in a fast convergence. PPP–RTK users are concerned about how to use the corrections and the level of performance that can be achieved; thus, our research has focused on correction methods, a priori stochastic modeling, and positioning performance evaluation. Conversely, it is crucial for the server to improve the precision of corrections provided and to consider the balance between cost, computation burden and user performance, especially for commercial applications. We use different scales of the national GPS network of France to generate ionospheric and tropospheric corrections, and corresponding uncertainty information is generated by establishing error functions with respect to an inter-station distance. The quality of corrections and corresponding user performance are analyzed with inter-station distances varying from 22 to 251 km. The results show that the precision of atmospheric corrections can be improved with an increasing number of stations in the network, but the improvement is not significant when the inter-station distances are smaller than 50 km. Regarding user performance, compared to conventional PPP solutions with ambiguity resolution, the convergence time can be reduced by a maximum of 93% and 85% in the horizontal and vertical components, respectively, when the inter-station distance is about 23 km. However, a station spacing within 100 km can still support a 3-min convergence; thus, a balance of server budget and user performance should be considered instead of a dense network.

Individual and joint associations of urinary phthalate metabolites with polycystic ovary and polycystic ovary syndrome: Results from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Fei-Peng Cui; Yu Miao; Wen Yao; Dan-Yu Qin; Yan-Ling Deng; Pan-Pan Chen; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; et al. (Environmental Toxicology and Pharmacology, 2023)

Profiling of single-vesicle surface proteins via droplet digital immuno-PCR for multi-subpopulation extracellular vesicles counting towards cancer diagnostics - Chunchen Liu; Huixian Lin; Jingyun Guo; Chao Yang; Jing Chen; Weilun Pan; Binbin Cui; Junjie Feng; Ye Zhang; Bo Li; Shuhuai Yao; Lei Zheng (Chemical Engineering Journal, 2023)

Rhein alleviates advanced glycation end products (AGEs)-induced inflammatory injury of diabetic cardiomyopathy in vitro and in vivo models - Shao-Yang Zhao; Huan-Huan Zhao; Bao-Hua Wang; Cui Shao; Wen-Jun Pan; Sai-Mei Li (Journal of Natural Medicines, 2023)

Development of a chiral electrochemical sensor based on copper–amino acid mercaptide nanorods for enantioselective discrimination of tryptophan enantiomers - Qian-xiu Pan; Yun-cong Yang; Ning-ning Zhao; Baogang Zhang; Lin Cui; Chun-yang Zhang (Analytica Chimica Acta, 2023)

A Distributed Intelligent Buoy System for Tracking Underwater Vehicles - Mengzhuo Liu; Jifeng Zhu; Xiaohe Pan; Guolin Wang; Jun Liu; Zheng Peng; Jun-Hong Cui (Journal of Marine Science and Engineering, 2023)
Underwater vehicles play a crucial role in various underwater applications, such as data collection in underwater sensor networks, target detection and tracking, and underwater pipeline monitoring. Real-time acquisition of their states, particularly their location and velocity, is vital for their operation and navigation. Consequently, the development of a remote tracking system to monitor these states is essential. In this paper, we propose a system that can track the underwater vehicle’s location and velocity. We take a systematic approach that encompasses the system architecture, system composition, signal processing, and mobility state estimation. We present the system architecture and define its components, along with their relationships and interfaces. The beacon signal employed in the system features dual-hyperbolic-frequency-modulated (HFM) waveform and an OFDM symbol with cyclic prefix (CP). Based on this beacon signal, we demonstrate how signal processing techniques are utilized to precisely determine the time of arrival and reduce false alarm rates in underwater acoustic channels affected by impulsive noise. Additionally, we explain how the CP-OFDM symbol is used to measure the Doppler scaling factor and transmit essential information for localization and velocity estimation purposes. Utilizing the measurements obtained through signal processing, least squares estimators are used for estimating both the location and velocity. To validate the effectiveness of our approach, we implement the system and conduct field trials. Two separate experiments were conducted in which the diagonal lengths of the square topology were designed to be 1000 m and 800 m. The minimum/maximum root mean square error of localization in the first and second experiment is 2.36/2.91 m and 1.47/2.49 m, respectively. And the minimum/maximum root mean square error of velocity estimation in the first and second experiment is 0.16/0.47 m/s and 0.21/0.76 m/s, respectively. Results confirm the effectiveness of the proposed method in estimating the location and velocity of the underwater vehicle. Overall, this paper provides a practical and effective design of a system to track the location and velocity of underwater vehicles. By leveraging the proposed system, signal processing, and mobility state estimation methods, our work offers a systematic solution. And, the successful field experiment serves as evidence of the feasibility and effectiveness of the proposed system, making it a valuable contribution to the field of tracking underwater vehicles.

Investigating the synergic role of asynchronous dosed protease and lysozyme for facilitating excess sludge solubilization and acidogenic fermentation - Xiang Zou; Junguo He; Heliang Pang; Pengfei Zhang; Xinlei Pan; Yijie Zhong; Shengye Duan; Xinxin Cui; Xiaodong Xin; Jie Zhang (Science of The Total Environment, 2023)

A complete assembly of the rice Nipponbare reference genome - Lianguang Shang; Wenchuang He; Tianyi Wang; Yingxue Yang; Qiang Xu; Xianjia Zhao; Longbo Yang; Hong Zhang; Xiaoxia Li; Yang Lv; Wu Chen; Shuo Cao; et al. (Molecular Plant, 2023)

The “umbrella of tolerance”: Nanobodies-armed photothermal lateral flow immunoassay for the detection of staphylococcal enterotoxin B - Haofen Wu; Yihan Li; Yuechun Li; Yan Cui; Conghui Jia; Jianlong Wang; Jiachuan Pan; Gege Yu; Xiaoling Zhang; Xiatong Wang; Pengran Guo; Yanwei Ji (Chemical Engineering Journal, 2023)

A new large-area hierarchical PPP-RTK service strategy - Bobin Cui; Xinyuan Jiang; Jungang Wang; Pan Li; Maorong Ge; Harald Schuh (GPS Solutions, 2023)
Introducing precise atmosphere information into precise point positioning enables rapid ambiguity resolution and introduces a significant accuracy improvement. However, it can only be implemented in regions with dense networks and stable communication links. For larger areas, e.g., an intercontinental level, there is a conflict between the accuracy of corrections and the amount of atmosphere information to be disseminated. We develop a hierarchical augmentation mode to combine the advantages of the fitting model and region interpolation model to relieve the communication burden. Relying on the fitting model with fewer coefficients applied over large areas as the essential information, the unmodeled errors are calculated at each reference station, and further correction information is optional compensation depending on the magnitude of the unmodeled residuals. We perform the proposed models on 103 EUREF Permanent Network stations with 200-km station spacing and 84 stations as the external validation. The ionosphere and troposphere fitting models have an average accuracy of about 4.2 and 1.3 cm, respectively, under meteorologically calm conditions. The unmodeled error transmission determined by the magnitude of residuals can be reduced by 61% and 96% for the ionospheric and tropospheric delays, respectively, with respect to the legacy interpolation mode. Further compensation implemented, i.e., unmodeled residuals, can achieve instantaneous convergence for 83.6% of all solutions, and the overall initialization time is within 1.0 min. Thus, the proposed hierarchical positioning mode satisfies real-time positioning convergence requirements and significantly reduces massive corrections in communication.

QTL mapping and identification of candidate genes for cold tolerance at the germination stage in wild rice - Ying-Hua Pan; Bao-Xuan Nong; Lei Chen; Xing-Hai Yang; Xiu-Zhong Xia; Zong-Qiong Zhang; Dong-Jin Qing; Ju Gao; Cheng-Cui Huang; Dan-Ting Li; Guo-Fu Deng (Genes & Genomics, 2023)

Algal organic matter and dissolved Mn cooperatively accelerate 17α-ethinylestradiol photodegradation: Role of photogenerated reactive Mn(III) - Zhicheng Liao; Huan He; Danni Cui; Jingye Cui; Xiaoxia Yang; Ziwei Guo; Hao Chen; Guohua Dao; Bin Huang; Hongwen Sun; Xuejun Pan (Water Research, 2023)

Long-term exposure to arsenic in drinking water leads to myocardial damage by oxidative stress and reduction in NO - Yi-Xin Cui; Lu Dong; Meng Zhang; Yi-Nan Liu; Yong-Hui Chen; Ming-Zhao Jia; Kun-Pan Chen; Hui Wang; Ya-Wen Shi; Tian-You Ma; Jing-Hong Chen (Toxicology, 2023)

Occurrence and Risk of Organophosphate Flame Retardants in Multiple Urban Water of Beijing, China - Yanmeng Zhang; Weihua Cui; Na Zhang; Pan Qin; Ying Zhang; Xiaochun Guo; Zhi Wang; Shaoyong Lu (Water, Air, & Soil Pollution, 2023)

OrMKK3 Influences Morphology and Grain Size in Rice - Ying Hua Pan; Li Jun Gao; Yun Tao Liang; Yan Zhao; Hai Fu Liang; Wei Wei Chen; Xing Hai Yang; Dong Jin Qing; Ju Gao; Hao Wu; Juan Huang; Wei Yong Zhou; et al. (Journal of Plant Biology, 2023)

Experimental Study on Hydrodynamic Characteristics of a Submerged Floating Tunnel under Freak Waves (I: Time-Domain Study) - Wenbo Pan; Meng He; Cheng Cui (Journal of Marine Science and Engineering, 2023)
The dynamic response characteristics of a two-dimensional submerged floating tunnel (SFT) under random and freak waves were investigated in the present study. The results demonstrate that (1) the dynamic responses of the SFT under the freak wave are significantly larger than those under the largest wave in the wave train excluding the freak wave, particularly for the motion response. The maximum values of the motion responses induced by the freak wave were several times larger than those induced by the largest wave in the wave train excluding the freak wave, far exceeding the proportion of the corresponding wave height. (2) The freak wave parameter α1 has a significant effect on the amplification coefficients of surge, heave and pitch; all increase nonlinearly as α1 increases. Within α1 = 1.90~2.59, the amplification coefficients of the surge, heave and pitch vary in the ranges of 1.91~6.46, 1.53~3.87 and 1.73~5.32, respectively. (3) Amplification coefficients of tension increase almost linearly as α1 increases. Additionally, the amplification effect of the freak wave on the mooring tension is much smaller than that on motion responses. Within α1 = 1.90~2.59, the amplification coefficients of tension vary from 1.15 to 1.35. (4) Generalised amplification coefficients of motion responses increase as α1 increases and are all greater than 1.0, indicating that growth rates for motion responses under the freak wave exceed the growth rates for maximum wave height. Moreover, motion responses show a significantly nonlinear growth as maximum wave height increases. The generalised amplification coefficients of the mooring tension decrease as α1 increases, and are all less than 1.0, indicating that the dynamic amplification effect of the freak wave on the mooring tension is much smaller than that on motions. On the other hand, growth rates of the mooring tension under freak waves are smaller than the linear growth rate of the height of freak waves.

Experimental Study of the Hydrodynamic Characteristics of a Submerged Floating Tunnel under Freak Wave (II: Time-Frequency Domain Study) - Wenbo Pan; Cheng Cui; Meng He (Journal of Marine Science and Engineering, 2023)
A freak wave is a spike in a random wave series and hence the local characteristics in the time-domain are of key importance. When freak waves act on moored floating structures, the dynamic responses of the structures in the time and frequency domains change interdependently in a short period of time. It is difficult to comprehensively and accurately describe this physical process using a single-dimensional analysis method, such as time-domain statistical analysis or frequency-domain spectral analysis. The wavelet analysis method, which can simultaneously provide the time-domain and frequency-domain joint information of the physical process, is used to discuss the time-frequency joint variation characteristics of the dynamic responses of a two-dimensional submerged floating tunnel under a freak wave. The time-frequency characteristics of the dynamic responses induced by the freak wave and the differences from the action under random waves are investigated, with a particular emphasis on the ‘convex variation’ characteristics of the dynamic responses under a freak wave. The results show that: (1) The wavelet analysis method can effectively describe the basic characteristics of the dynamic responses of the SFT under a freak wave and clearly distinguish the differences in dynamic responses under freak and random waves. (2) Freak waves have dynamic amplification effects, which are related to the freak wave parameter α1, on a two-dimensional SFT. Following the action of freak waves on a two-dimensional SFT, significant energy concentration occurs in the time-frequency spectrum of the dynamic response in a certain time and frequency range. The degree of energy concentration increases nonlinearly with an increase in α1, and a certain high-frequency energy appears in the time-frequency spectrum of the motion response. The maximum values of the time-frequency spectra of the dynamic responses under a freak wave are much larger than those under a random wave with the identical wave spectrum. (3) Following the action of a freak wave on a two-dimensional SFT, the generalised energy spectra of surge, heave, pitch, and mooring tensions have convex peak values, which occur simultaneous with the occurrence of the freak wave, and the convex parts significantly increase as α1. (4) The time lengths of the influence of a freak wave on the dynamic responses exceeded the freak wave period. With an increase in α1, the time ranges of the large values of the time-frequency spectra of surge, heave, pitch, and mooring tensions increase nearly linearly.

Dissolved biochar fractions and solid biochar particles inhibit soil acidification induced by nitrification through different mechanisms - Ren-Yong Shi; Ni Ni; Ru-Hai Wang; Jackson Nkoh Nkoh; Xiao-Ying Pan; Ge Dong; Ren-Kou Xu; Xiu-Min Cui; Jiu-Yu Li (Science of The Total Environment, 2023)

Anisotropic interlayer Dzyaloshinskii-Moriya interactions in synthetic ferromagnetic multilayers - Ruyi Chen; Feng Xu; Qirui Cui; Jinghua Liang; Yongjian Zhou; Ning Wang; Feng Pan; Fei Xue; Hongxin Yang; Cheng Song (Science Bulletin, 2023)

Radioactivity research in mosses from typical Karst Regions in Leye Tiankeng, Southern China - Yongjing Guan; Qiaoyan Jing; Shenzhen Wang; Huijuan Wang; Wu Chen; Yuxin Hua; Zichen Guo; Liangjia Cui; Chunping Huang; Liang Wang; Pan Kuang; Xianwen He; et al. (Journal of Environmental Radioactivity, 2023)

Simultaneous ion fractionation and concentration by selectrodialysis for saline wastewater valorization - Zhenzhen Cui; Wenguang Wang; Yong Lin; Min Hu; Yuebiao Li; Boyu Pan; Ming Tan; Yang Zhang (Desalination, 2023)

A uw-Cellular Network: Design, Implementation and Experiments - Jifeng Zhu; Xiaohe Pan; Zheng Peng; Mengzhuo Liu; Jingqian Guo; Tong Zhang; Yu Gou; Jun-Hong Cui (Journal of Marine Science and Engineering, 2023)
The most significant increase of current task is in the desire for operational flexibility and agility in large-scale underwater network application scenarios in recent years. In order to address the challenging problems in Underwater Wireless Sensor Networks (UWSNs), we propose a large-scale UWSN based on the cellular network architecture called Underwater Cellular (uw-Cellular) network. It is designed especially for application scenarios where a large number of both fixed and mobile network nodes exist in a wide area to monitor the underwater environment. We also design protocols in each network layer in order to ensure reasonable channel sharing, data forwarding path selection and data reliability. The purpose of the simulation study we implement is to evaluate the performance of the CLA routing strategy compared to the VBF and the MFLOOD protocols in the uw-Cellular network. We also deploy a twenty-node uw-Cellular network in the real-world environment as the field case study. The experimental results showed that the Data Rate between any nodes could reach above 500 bps, and the network Average Throughput was no less than 550 bps under various load situations.

Triassic igneous activities in the east flank of the East Kunlun orogenic belt: the Daheba complex example - Nan Tian; Feng-Yue Sun; Zhong-Cui Pan; Liang Li; Yan Gu; Dong-Qian Wu; Jia-Fang Deng; Zhe-Dong Liu; Li Wang; Ya-Jing Zhang (International Geology Review, 2023)

Effects of indoor exposure to low level toluene on neural network alterations during working memory encoding - Liping Pan; Jie Liu; Changqing Zhan; Xin Zhang; Mingrui Cui; Xiao Su; Zukun Wang; Lei Zhao; Junjie Liu; Yijun Song (Chemosphere, 2023)

Hydrological responses to litter density on runoff-infiltration patterns and water conservation in Pinus tabuliformis plantation - Yongsheng Cui; Chengzhong Pan (Journal of Hydrology, 2023)

Evaluating response mechanisms of soil microbiomes and metabolomes to Bt toxin additions - Lei Ge; Lili Song; Luyao Wang; Yujie Li; Yu Sun; Cui Wang; Jun Chen; Guogan Wu; Aihu Pan; Yunfei Wu; Zhexue Quan; Peng Li (Journal of Hazardous Materials, 2023)

Insights into characteristics of white rot fungus during environmental plastics adhesion and degradation mechanism of plastics - Feiyan Wu; Zhi Guo; Kangping Cui; Dazhuang Dong; Xue Yang; Jie Li; Zhangzhen Wu; Lele Li; Yaodan Dai; Tao Pan (Journal of Hazardous Materials, 2023)

Zirconium tungstate reinforced energetic composites with inhibited thermal expansion and reduced thermal stress - Congmei Lin; Liangfei Bai; Liyuan Wei; Ruqin Liu; Shiliang Huang; Cui Zhang; Xiaoqing Tu; Zhijian Yang; Feiyan Gong; Chengcheng Zeng; Ling Ding; Liping Pan; et al. (Chemical Engineering Journal, 2023)

An On-Demand Scheduling-Based MAC Protocol for UW-WiFi Networks - Xiaohe Pan; Jifeng Zhu; Mengzhuo Liu; Xiaoyu Wang; Zheng Peng; Jun Liu; Junhong Cui (Journal of Marine Science and Engineering, 2023)
Underwater Internet-of-Things (UIoT) is an extension of Internet-of-Things technology in underwater. The underwater acoustic network with WiFi architecture (UW-WiFi), as a specific deployment of UIoT, has been proved to be a promising technique for wide-ranging marine applications. However, due to the unique features of underwater acoustic channel, such as long and variable propagation delay, low available bandwidth and high bit error rate, conventional medium access control (MAC) protocols designed for terrestrial WiFi networks need an overhaul to work efficiently for UW-WiFi networks. In consideration of the aforementioned channel features, different demands of nodes to occupy channel resources and the reliability of data transmission, a time sequence-based dynamic on-demand assignment (SDDA) MAC protocol for UW-WiFi networks is proposed in this paper. In SDDA, the collision-free scheduling is integrated with the reservation mechanism, aiming to address the issue of various access requirements of diverse task nodes on channel resources in the UW-WiFi network system. The designed protocol employs propagation delays and the amount of data to be sent by terminal nodes to achieve non-conflict transmissions of control packets and on-demand scheduling of data packets. Additionally, the scheme does not require extra overhead for time synchronization. Comparison simulations demonstrate that SDDA provides considerable benefits in terms of channel utilization, end-to-end delay and packet delivery ratio. At last, the SDDA protocol is implemented and a UW-WiFi network system is set up in the marine environment. The ocean field experiment results agree well with the simulated ones and also verify that the proposed protocol achieve conflict-free on-demand scheduling, fairness among terminal nodes at different ranges and the practicability in actual environments.

Frontiers in Deep-Sea Equipment and Technology - Weicheng Cui; Lian Lian; Guang Pan (Journal of Marine Science and Engineering, 2023)
The conflict between population, resources, and environment in the twenty-first century made the ocean the strategic space and resource treasure of human society to realize sustainable development [...]

Deployment optimization of battery swapping stations accounting for taxis’ dynamic energy demand - Tian-yu Zhang; En-jian Yao; Yang Yang; Long Pan; Cui-ping Li; Bin Li; Feng Zhao (Transportation Research Part D: Transport and Environment, 2023)

Characteristics of dynamic shear modulus and damping ratio and the structural formula of EPS particles lightweight soil - Tian-shun Hou; Yi-xiang Cui; Xing-ru Pan; Ya-sheng Luo; Qian Liu (Soil Dynamics and Earthquake Engineering, 2023)

Widespread missing super-emitters of nitrogen oxides across China inferred from year-round satellite observations - Yuqing Pan; Lei Duan; Mingqi Li; Pinqing Song; Nan Xv; Jing Liu; Yifei Le; Mengying Li; Cui Wang; Shaocai Yu; Daniel Rosenfeld; John H. Seinfeld; et al. (Science of The Total Environment, 2023)

SUMOylation-modified Pelota-Hbs1 RNA surveillance complex restricts the infection of potyvirids in plants - Linhao Ge; Buwei Cao; Rui Qiao; Hongguang Cui; Shaofang Li; Hongying Shan; Pan Gong; Mingzhen Zhang; Hao Li; Aiming Wang; Xueping Zhou; Fangfang Li (Molecular Plant, 2023)

Insight into boron-doped biochar as efficient metal-free catalyst for peroxymonosulfate activation: Important role of -O-B-O- moieties - Guoping Pan; Jia Wei; Mengdie Xu; Jiamei Li; Linhao Wang; Yanan Li; Nan Cui; Jun Li; Zhaoxu Wang (Journal of Hazardous Materials, 2023)

A hybrid deep learning model for regional O3 and NO2 concentrations prediction based on spatiotemporal dependencies in air quality monitoring network - Cui-lin Wu; Hong-di He; Rui-feng Song; Xing-hang Zhu; Zhong-ren Peng; Qing-yan Fu; Jun Pan (Environmental Pollution, 2023)

Alterations in functional connectivity of executive control network reveal influence of indoor toluene on cognition at low concentration - Changqing Zhan; Junjie Liu; Mingrui Cui; Wenjuan Wu; Fangfang Hao; Zukun Wang; Jie Liu; Xin Zhang; Liping Pan; Meili Deng; Xiao Su; Jiajing Wang; et al. (Building and Environment, 2023)

Coalbed methane desorption characteristics controlled by coalification and its implication on gas co-production from multiple coal seams - Bin Zhang; Yafei Zhang; Suping Zhao; Wei He; Shu Tao; Zhejun Pan; Yi Cui (Frontiers of Earth Science, 2023)

Supplementation of CO2-nanobubble water to enhance the methane production from anaerobic digestion of corn straw - Hao Song; Tingting Hou; Youzhou Jiao; Liang Liu; Xiaohui Pan; Gang Li; Quanguo Zhang; Yu Zeng; Zhiqiang Cui; Pengfei Li; Mukesh Kumar Awasthi; Chao He (Chemosphere, 2023)

Visible-light-driven iron-based heterogeneous photo-Fenton catalysts for wastewater decontamination: A review of recent advances - Qiangshun Wu; Muhammad Saboor Siddique; Huijuan Wang; Liqiang Cui; Hui Wang; Mei Pan; Jinlong Yan (Chemosphere, 2023)

Improved ResNet-50 deep learning algorithm for identifying chicken gender - Dihua Wu; Yibin Ying; Mingchuan Zhou; Jinming Pan; Di Cui (Computers and Electronics in Agriculture, 2023)

A deep learning approach to predict sea surface temperature based on multiple modes - Shuang Xu; Dejun Dai; Xuerong Cui; Xunqiang Yin; Shumin Jiang; Haidong Pan; Guansuo Wang (Ocean Modelling, 2023)

The long-acting herbicide mesosulfuron-methyl inhibits soil microbial community assembly mediating nitrogen cycling - Junli Cao; Ying Zhang; Gaochen Dai; Kai Cui; Xiaohu Wu; Fanxin Qin; Jun Xu; Fengshou Dong; Xinglu Pan; Yongquan Zheng (Journal of Hazardous Materials, 2023)

Within-day variability, predictors, and risk assessments of exposure to parabens among Chinese adult men - Yu Miao; Pan-Pan Chen; Min Zhang; Fei-Peng Cui; Chong Liu; Yan-Ling Deng; Jia-Yue Zeng; Wen-Jun Yin; Qiang Zeng (Environmental Research, 2023)

Bio-inspired superhydrophobic interface of nano-gaseous film for reducing injection pressure in oil reservoirs - Zhongzheng Xu; Mingwei Zhao; Yiming Zhang; Pan Wang; Yining Wu; Lin Li; Xin Cui; Ning Sun; Caili Dai (Chemical Engineering Journal, 2023)

Plastome evolution and phylogenomics of Impatiens (Balsaminaceae) - He Qiu; Zhi-Hui Zhang; Mei-Zhen Wang; Xin-Jie Jin; Jie-Dong Lin; Hans Peter Comes; Jing-Xuan Chen; Rui-Ning Cui; Ru-Qing Duan; Pan Li (Planta, 2023)

Evaluation of Copper Levels in Dental Calculus of OSF Patients with Chewing Dried Areca-Nut Quids in Hunan Province of Mainland China - Xi-Fan He; Hui Wang; Ye Tian; Te Zhang; Zhi-Peng Qiu; Xiao-Jiao Cui; Jing-Sha Zhou; Xin-Lan Yan; Yi-Wei Wu; Yi-Sha Pan; Yang-Bo Ning; Lin Chen; et al. (Biological Trace Element Research, 2023)

Parthenolide inhibits proliferation of cells infected with Kaposi’s sarcoma-associated herpesvirus by suppression of the NF-κB signaling pathway - Ying Li; Huiling Xu; Xiaohua Tan; Qinghua Cui; Wenyi Gu; Zemin Pan; Lei Yang; Shuyuan Wu; Xiaolu Wang; Dongmei Li (Archives of Virology, 2023)

Resveratrol ameliorates the defects of meiotic maturation in lipopolysaccharide exposed porcine oocytes - Xinxin Liu; Pan Li; Ke Yan; Ya Du; Ke Peng; Mengqi Li; Kexin Cui; Hengye Zhang; Xiaogan Yang; Shengsheng Lu; Xingwei Liang (Reproductive Toxicology, 2023)

Damage evolution, fractal dimension and a new crushing energy formula for coal with bursting liability - Xin Ding; Xiaochun Xiao; Jingzhi Cui; Di WU; Yishan Pan (Process Safety and Environmental Protection, 2023)

Study on pressure wave response and overpressure attenuation law of explosion-proof doors - Rongkun Pan; Bang Cui; Xuebo Zhang; Yanming Wang; Ligang Zheng (Process Safety and Environmental Protection, 2023)

The inhibition of ecdysone signal pathway was the key of pyriproxyfen poisoning for silkworm, Bombyx mori - Pingyang Wang; Qiuying Cui; Xia Wang; Yanwei Liu; Yuli Zhang; Xuhua Huang; Shidong Jiang; Mangui Jiang; Lihui Bi; Biao Li; Wei Wei; Zhixin Pan (Pesticide Biochemistry and Physiology, 2023)

Electron transfer mechanism mediated nitrogen-enriched biochar encapsulated cobalt nanoparticles catalyst as an effective persulfate activator for doxycycline removal - Zijian Jiang; Jia Wei; Yifei Zhang; Xiruo Niu; Jiamei Li; Yanan Li; Guoping Pan; Mengdie Xu; Xueru Cui; Nan Cui; Jun Li (Journal of Cleaner Production, 2023)

Discrimination of the harvesting season of green tea by alcohol/salt-based aqueous two-phase systems combined with chemometric analysis - Xiao-Hua Zhang; Hui-Na Cui; Jing-Jing Zheng; Xiang-Dong Qing; Kai-Long Yang; Ya-Qian Zhang; Lu-Meng Ren; Le-Yuan Pan; Xiao-Li Yin (Food Research International, 2023)

3-Hydroxybutyrate helps crayfish resistant to Vibrio parahaemolyticus infection in versatile ways - Hu Duan; Jiajun Zuo; Namin Pan; Xueping Cui; Jianlin Guo; Liying Sui (Fish & Shellfish Immunology, 2023)

Urinary phthalate metabolites and the risk of endometrial polyp: A pilot study from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Wen Yao; Qing-Yun Yao; Yong Huang; Ni-Jie Li; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Yu-Feng Li; et al. (Environmental Pollution, 2023)

High-efficiency electro-Fenton process based on in-situ grown CoFeCe-LDH@CFs free-standing cathodes: Correlation of cerium and oxygen vacancies with H2O2 - Mengdie Xu; Jia Wei; Xueru Cui; Jiamei Li; Guoping Pan; Yanan Li; Zijian Jiang; Xiruo Niu; Nan Cui; Jun Li (Chemical Engineering Journal, 2023)

Smartphone bioelectronic drug with visual colorimetric sensor and bulk nanoencapsulation optogenetic bacteria for chronic kidney disease theragnostics - Meihui Cui; Wei Ling; Lili Zhang; Yayang Li; Jing Liu; Tao Sun; Binglin Ma; Shenjunjie Lu; Huizhuo Pan; Gaoju Pang; Yingying Zhang; Shufang Zhang; et al. (Chemical Engineering Journal, 2023)

Characterization and expression analysis of basic leucine zipper (bZIP) transcription factors responsive to chilling injury in peach fruit - Muhammad Muzammal Aslam; Li Deng; Junren Meng; Yan Wang; Lei Pan; Liang Niu; Zhenhua Lu; Guochao Cui; Wenfang Zeng; Zhiqiang Wang (Molecular Biology Reports, 2023)

Light-enhanced transparent hydrogel for uric acid and glucose detection by four different analytical platforms - Wei Mao; Xingwei Cai; Ruirong Pan; Sheng Tang; Fu Yang; Yanjuan Cui; Jun Sun; Wei Shen (Analytica Chimica Acta, 2023)

Metabolism balance regulation for squalene production by disturbing triglyceride (TAG) synthesis in Schizochytrium sp. - Ran Duan; Xueshan Pan; Keyan Li; Qinghua Yang; Xiaowen Cui; Yayun Zheng; Yinghua Lu; Chuanyi Yao; Xueping Ling (Algal Research, 2023)

A Nonlinear Phase Transition Dynamic Model for Shape Memory Alloys Based Deep Sea Actuators - Jian Guo; Binbin Pan; Weicheng Cui; Shengbing Hu (Journal of Marine Science and Engineering, 2022)
A constitutive relation for shape memory alloys (SMAs) that is simple, accurate, and effective is the basis for deep-sea intelligent actuators used in marine engineering applications. The existing kinetic models of phase transition all have common drawbacks, such as sharp change at the turning point of the phase transition, constant phase transition rate, and many variable parameters. In this study, the one-dimensional thermodynamic constitutive equation for SMAs is extended based on the thermodynamic framework of the Boyd–Lagoudas constitutive model. In addition, the traditional phase transition function is replaced by an improved logistic nonlinear function in order to construct the relation for the macroscopic variable-speed phase transition that constitutes deep-sea actuator driving wires. The logistic model is compared to other models and verified by the numerical fitting results of the traditional constitutive model and the experimental data for two scenarios: (1) constant load and (2) constant temperature. The results show that the improved constitutive model has more advantages and better adaptability than the traditional models. Consequently, it can accurately describe the slow and gradual phase transitions in the initial and final regions of the phase transition with fewer variable parameters and has the ability to flexibly adjust the rate of change of the phase transition rate. These results provide important theoretical support for the design of SMA deep-sea actuators used in marine engineering applications.

Detection by environmental surveillance and genomic characterization of H5N8 highly pathogenic avian influenza virus from a poultry meat market in Beijing, China, 2021–22 - Shujuan Cui; Lin Zou; Yimeng Liu; Jiachen Zhao; Guilan Lu; Weixian Shi; Yang Pan; Xiaomin Peng; Daitao Zhang; Peng Yang; Quanyi Wang (Veterinary Research Communications, 2022)

Effect of Mytilus coruscus selective filtration on phytoplankton assemblages - Tao Jiang; Huizhu Pan; Laura Steeves; Zengjie Jiang; Ramón Filgueira; Øivind Strand; Tore Strohmeier; Peter J. Cranford; Zhengguo Cui (Frontiers in Marine Science, 2022)
The feeding selectivity of bivalves can play an important role in shaping the structure of phytoplankton communities of natural waters. This could be particularly true in waters with intensive bivalves farming, like Sungo Bay, Northern China. Understanding the role of bivalve feeding behavior is important for assessing how the dense cultivation of bivalves may affect phytoplankton community composition and food web structure in farm areas. In this study, we investigated the feeding selectivity of blue mussel Mytilus coruscus on natural phytoplankton assemblages in Sungo Bay using both optical microscopy and HPLC-pigment analysis. Results showed that cryptophytes dominated the phytoplankton community and made up 66.1% of the total phytoplankton abundance. A comparison of phytoplankton composition between natural and filtered seawater showed that M. coruscus preferred cryptophytes and dinoflagellates than Chaetoceros spp. and Skeletonema spp. Cryptophytes were not detected in gut contents by microscopic observation, while their marker pigment alloxanthin was present, suggesting they were also consumed by M. coruscus and can be readily digested. This highlights the shortcomings of microscopic methods and the significance of HPLC-pigment analysis in obtaining a comprehensive understanding of feeding selectivity of bivalves. The proportions of Chaetoceros spp. and Skeletonema spp. in gut contents were significantly lower than their proportions in the seawater, and contrastingly, the proportions of Cocconeis spp. and Pinnularia spp. showed opposite patterns. The marker pigments prasinoxanthin and zeaxanthin were detected in the gut of M. coruscus indicating that picophytoplankton (e.g., prasinophytes and Synechococcus ) are also food sources for this bivalve. This information furthers our understanding of bivalve aquaculture and environment interactions.

Rose Bengal inhibits β-amyloid oligomers-induced tau hyperphosphorylation via acting on Akt and CDK5 kinases - Chen-Ye Mou; Yan-Fei Xie; Jia-Xin Wei; Qi-Yao Wang; Jing-Yang Le; Yong-Jie Bao; Pan-Pan Zhang; Yue-Chun Mao; Xing-Han Huang; Han-Bo Pan; C. Benjamin Naman; Lin Liu; et al. (Psychopharmacology, 2022)

Anti-Seizure and Neuronal Protective Effects of Irisin in Kainic Acid-Induced Chronic Epilepsy Model with Spontaneous Seizures - Jie Yu; Yao Cheng; Yaru Cui; Yujie Zhai; Wenshen Zhang; Mengdi Zhang; Wenyu Xin; Jia Liang; Xiaohong Pan; Qiaoyun Wang; Hongliu Sun (Neuroscience Bulletin, 2022)

Urinary concentrations of polycyclic aromatic hydrocarbon and phthalate metabolite mixtures in relation to semen quality among men attending an infertility clinic - Yan-Ling Deng; Pan Yang; Yi-Xin Wang; Chong Liu; Qiong Luo; Tian Shi; Jia-Yue Zeng; Ting-Ting Lu; Pan-Pan Chen; Yu Miao; Min Zhang; Fei-Peng Cui; et al. (Environmental Science and Pollution Research, 2022)

Working memory-related alterations in neural oscillations reveal the influence of in-vehicle toluene on cognition at low concentration - Xiao Su; Xin Zhang; Jingjing Pei; Meili Deng; Liping Pan; Jie liu; Mingrui Cui; Changqin Zhan; Jiajing Wang; Yakun Wu; Lei Zhao; Zunkun Wang; et al. (Environmental Science and Pollution Research, 2022)

Alterations in gut microbiota and metabolites associated with altitude-induced cardiac hypertrophy in rats during hypobaric hypoxia challenge - Zhiyuan Pan; Yichen Hu; Zongyu Huang; Ni Han; Yan Li; Xiaomei Zhuang; Jiye Yin; Hui Peng; Quansheng Gao; Wenpeng Zhang; Yong Huang; Yujun Cui; et al. (Science China Life Sciences, 2022)

High-precision potassium isotope analysis using the Nu Sapphire collision cell (CC)-MC-ICP-MS - Wenjun Li; Mengmeng Cui; Qiqi Pan; Jing Wang; Bingyu Gao; Shanke Liu; Meng Yuan; Benxun Su; Ye Zhao; Fang-Zhen Teng; Guilin Han (Science China Earth Sciences, 2022)

Correction to: Linarin Protects against Cadmium-Induced Osteoporosis Via Reducing Oxidative Stress and Infammation and Altering RANK/RANKL/OPG Pathway - Yating Yang; Ruining Cheng; Jingyun Liu; Jing Fang; Xiaojing Wang; Yingxue Cui; Pan Zhang; Bin Du (Biological Trace Element Research, 2022)

Linarin Protects against Cadmium-Induced Osteoporosis Via Reducing Oxidative Stress and Inflammation and Altering RANK/RANKL/OPG Pathway - Yating Yang; Ruining Cheng; Jingyun Liu; Jing Fang; Xiaojing Wang; Yingxue Cui; Pan Zhang; Bin Du (Biological Trace Element Research, 2022)

Why empresses have more sons? Maternal instant social condition determines it - Yan-Peng Li; Wei Ding; Zhi-Pang Huang; Ru-Liang Pan; Na Li; Guo-Peng Ren; Liang-Wei Cui; Qing-hua Cai; Wen Xiao (Behavioral Ecology and Sociobiology, 2022)
Sexual selection echoed by the sex ratio is a critical issue in evolution and reproductive biology studies, and the second sex ratio (sex ratio at birth, SRB) is an important evaluation indicator for sex regulation. However, broad debates on sex ratio at birth exist due to the lack of a clear spatiotemporal genealogical database. This study explicitly tests the Trivers and Willard’s hypothesis stating that parents with good social conditions tend to show a male-biased SRB. Using a database of Chinese imperial families from 211BC to 1912 (2142 years) which avoids the spatiotemporal confusion of data thanks to its clear boundaries and long timespan, we found that a proportion of males at birth was 0.54. In particular, the results indicate that the empresses generated a significantly higher male-biased SRB than the concubines within the imperial harems (0.61 vs 0.53), while the SRB of concubines was not higher than ordinary people (0.53 vs 0.52). A significant difference of SRB before and after empress coronation (0.48 vs 0.65) was detected, indicating that the change to a higher social status is the leading cause of a biased SRB. These findings suggest that mothers with privileged instant social conditions tend to generate more boys than girls. In other words, a higher maternal social rank during the conception period, instead of rich resources, forms the primary mechanism regulating the SRB. Significance statement Adaptive sex ratio has been a debatable topic difficult to clearly verify since the publication of Trivers and Willard Hypothesis in 1973, which proposes that parents who have good conditions should produce more male offspring. The one reason is that the validity and sample size of the databases used contained unavoidable confounding noise, both genealogically and genetically. To overcome these issues, we specifically compiled a historical database of Chinese imperial families, which are characterized by a confined mating harem and unique eunuch system, guaranteeing biological and genetic purity with precise genealogical relationships and genetic linkages between the parents and the offspring. Thus, this is an extraordinary effort to clarify the hypotheses proposed by TWH and other hypotheses.

Coupled effects of saline solution and vertical stress on swelling deformation of compacted GMZ bentonite/sand mixtures - Yong-Gui Chen; Yu-Hao Hu; Kan Pan; Wei-Min Ye; Yu-Jun Cui (Bulletin of Engineering Geology and the Environment, 2022)

Remarkable enhancement of bleomycin production through precise amplification of its biosynthetic gene cluster in Streptomyces verticillus - Hong Li; Wenyan Gao; Yifan Cui; Yuanyuan Pan; Gang Liu (Science China Life Sciences, 2022)

Migration and Deposition Characteristics of Particles in Sand Layers with Fluctuating Water Levels - Xianze Cui; Tao Wen; Jin Li; Dazhou Wu; Yong Fan; Ying Jin; Siyuan He; Yucong Pan (Water, Air, & Soil Pollution, 2022)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

The solar wind plasma upstream of Mars observed by Tianwen-1: Comparison with Mars Express and MAVEN - Kai Fan; Limei Yan; Yong Wei; Aibing Zhang; Linggao Kong; Markus Fränz; Fei He; Lihui Chai; Chongjing Yuan; Yuqi Wang; Jun Zhong; Zhaojin Rong; et al. (Science China Earth Sciences, 2022)

Modeling wide-area tropospheric delay corrections for fast PPP ambiguity resolution - Bobin Cui; Jungang Wang; Pan Li; Maorong Ge; Harald Schuh (GPS Solutions, 2022)
The performance of precise point positioning (PPP) has been significantly improved thanks to the continuous improvements in satellite orbit, clock, and ambiguity resolution (AR) technologies, but the convergence speed remains a limiting factor in real-time PPP applications. To improve the PPP precision and convergence time, tropospheric delays from a regional network can be modeled to provide precise correction for users. We focus on the precise modeling of zenith wet delay (ZWD) over a wide area with large altitude variations for improving PPP-AR. By exploiting the water vapor exponential vertical decrease, we develop a modified optimal fitting coefficients (MOFC) model based on the traditional optimal fitting coefficients (OFC) model. The proposed MOFC model provides a precision better than 1.5 cm under sparse inter-station distances over the Europe region, with a significant improvement of 70% for high-altitude stations compared to the OFC model. The MOFC model with different densities of reference stations is further evaluated in GPS and Galileo kinematic PPP-AR solutions. Compared to the PPP-AR solutions without tropospheric delay augmentation, the positioning precision of those with 100-km inter-station spacing MOFC and OFC is improved by 25.7% and 17.8%, respectively, and the corresponding time to first fix (TTFF) is improved by 36.9% and 33.0% in the high-altitude areas. On the other hand, the OFC model only slightly improves the TTFF and positioning accuracy when using the 200 km inter-station spacing modeling and even degrades the positioning for high-altitude stations, whereas using the MOFC model, the PPP-AR solutions always improve. Moreover, the positioning precision improvement of MOFC compared with OFC is about 22.1%, 21.7%, and 25.7% for the Galileo-only, GPS-only, and GPS + Galileo PPP-AR solutions, respectively.

Effects of Dietary Poly-β-Hydroxybutyrate Supplementation on the Growth, Non-specific Immunity, and Intestinal Microbiota of the Sea Cucumber Apostichopus japonicus - Longzhen Liu; Mingyang Wang; Cong Wei; Yang Liu; Miaojun Pan; Shishuang Wang; Liang Cui; Xiangli Tian (Frontiers in Marine Science, 2022)
The present study evaluated the effects of dietary supplementation with poly-β-hydroxybutyrate (PHB) on the growth performance, non-specific immunity, immune-related gene expression in the Nuclear factor-κB (NF-κB) signaling pathway, and intestinal microbiota of the sea cucumber Apostichopus japonicus . During a 63-day feeding trial, the sea cucumber was fed with basal diet (control, C treatment) and treatment diets supplemented at different doses of PHB, i.e., 0.5% (P treatment), 1% (OP treatment), and 3% PHB (TP treatment) ( w / w ) followed by a stimulation test of inactivated Vibrio splendidus for 7 days. All PHB treatments significantly promoted the specific growth rate and weight gain rate of the sea cucumber ( P < 0.05). The 1% PHB significantly enhanced phagocytic, respiratory burst, superoxide dismutase, alkaline phosphatase, acid phosphatase, catalase, and lysozyme activities in the coelomocytes of A. japonicus ( P < 0.05). However, no elevated activities of catalase and lysozyme were observed in the P treatment ( P < 0.05), and only increased catalase activity appeared in the TP treatment ( P < 0.05). Quantitative real-time PCR revealed significantly higher expression levels of Aj -p105, Aj -p50, and Aj -rel in the mid-intestine tissue of the sea cucumber in the PHB treatments ( P < 0.05), and the relative expression level Aj -lys gene was significantly higher in the OP treatment ( P < 0.05) than that in the control. After injection of inactivated V. splendidus , the relative expression level of four immune-related genes in the OP treatment was significantly up-regulated at 24 h ( P < 0.05). The richness of intestinal microbiota in PHB treatments significantly increased, while diversity in TP treatment significantly decreased ( P < 0.05). The relative abundances of Rhodobacteraceae in the PHB treatments were significantly higher than that in the control ( P < 0.05). Network analysis revealed that 0.5 and 1% PHB supplement enhanced the stability of the intestinal microbial ecosystem. Functional prediction revealed that the PHB diet significantly increased some potential functions of intestinal microbiota, involving amino acid, lipid, and nucleotide metabolisms. In summary, dietary supplementation with a suitable dose of PHB had shown multiple beneficial effects on A. japonicus . Considering collectively the above, the optimum dose of 1% PHB addition to the diet of A. japonicus is recommended.

A procedure for interaction between rock mass and liner for deep circular tunnel based on new solution of longitudinal displacement profile - Qiang Shen; Jun-Jie Zheng; Lan Cui; Yu Pan; Bo Cui (European Journal of Environmental and Civil Engineering, 2022)

NtCycB2 negatively regulates tobacco glandular trichome formation, exudate accumulation, and aphid resistance - Zhaojun Wang; Xiaoxiao Yan; Hongying Zhang; Ying Meng; Yang Pan; Hong Cui (Plant Molecular Biology, 2022)

Recombinant Avian β-Defensin Produced by Food-Grade Lactococcus as a Novel and Potent Immunological Enhancer Adjuvant for Avian Vaccine - Tingting Wang; Zhihao Wang; Jielan Mi; Wenqian Wang; Kai Li; Xiaole Qi; Yulong Gao; Li Gao; Changjun Liu; Yanping Zhang; Qing Pan; Xiaomei Wang; et al. (Probiotics and Antimicrobial Proteins, 2021)
In this study, we expressed rAvBD1-2–6-13 protein through Lactococcus lactis NZ3900, and the effects of the recombinant L. lactis NZ3900 as an immune enhancer and immune adjuvant were verified using in vivo and in vitro tests. In vitro tests revealed that recombinant L. lactis NZ3900 significantly activated the NF-κB signaling pathway and IRF signaling pathway in J774-Dual™ report cells and significantly increased the transcript levels of IL-10, IL-12p70, CD80, and CD86 in chicken PBMCs and chicken HD11 cells. In vivo experiments revealed that the immunized group supplemented with recombinant L. lactis NZ3900 as an adjuvant had significantly higher serum antibody titers and higher proliferative activity of PBMCs in the blood of the chickens immunized with NDV live and inactivated vaccines. Our study shows that the recombinant L. lactis NZ3900 has strong immunomodulatory activity both in vivo and in vitro and is a potential immune enhancer. Our work lays the foundation for the research and development of new animal immune enhancers for application in the poultry industry.

Association of exposure to ethylene oxide with risk of diabetes mellitus: results from NHANES 2013–2016 - Jingyu Guo; Zhenzhen Wan; Guanglin Cui; An Pan; Gang Liu (Environmental Science and Pollution Research, 2021)

Observations on a magnetotactic bacteria-grazing ciliate in sediment from the intertidal zone of Huiquan Bay, China - Si Chen; Kaixuan Cui; Wenyan Zhang; Yicong Zhao; Tian Xiao; Hongmiao Pan; Wuchang Zhang; Long-Fei Wu (Journal of Oceanology and Limnology, 2021)

Characterization and diversity of magnetotactic bacteria from sediments of Caroline Seamount in the Western Pacific Ocean - Kaixuan Cui; Wenyan Zhang; Jia Liu; Cong Xu; Yicong Zhao; Si Chen; Hongmiao Pan; Tian Xiao; Long-Fei Wu (Journal of Oceanology and Limnology, 2021)

Porcine deltacoronavirus and its prevalence in China: a review of epidemiology, evolution, and vaccine development - Pan Tang; Enhui Cui; Yihong Song; Ruoqian Yan; Jingyu Wang (Archives of Virology, 2021)

Correction to: Preparation and Evaluation of Self-emulsifying Drug Delivery System (SEDDS) of Cepharanthine - Pan Gao; Zhujun Jiang; Qiao Luo; Chengqiao Mu; Mengsuo Cui; Xinggang Yang (AAPS PharmSciTech, 2021)

Preparation and Evaluation of Self-emulsifying Drug Delivery System (SEDDS) of Cepharanthine - Pan Gao; Zhujun Jiang; Qiao Luo; Chengqiao Mu; Mengsuo Cui; Xinggang Yang (AAPS PharmSciTech, 2021)

Research progress of disaster factors and a prevention alarm index of coal and gas outbursts - Fakai Wang; Pan Zhang; Bo Cui; Zhongguang Sun; Kaizhi Zhang (Arabian Journal of Geosciences, 2021)

First-arrival automatic picking based on improved energy ratio method and outlier detection theory - Ziyu Qin; Shulin Pan; Linhui Hu; Qinghui Cui; Qiyong Gou (Acta Geophysica, 2021)

The hepatoprotective efficacy and biological mechanisms of three phenylethanoid glycosides from cistanches herba and their metabolites based on intestinal bacteria and network pharmacology - Yongli Guo; Qingling Cui; Shumeng Ren; Deguo Hao; Toshio Morikawa; Dongmei Wang; Xiaoqiu Liu; Yingni Pan (Journal of Natural Medicines, 2021)

MicroRNA expression profiling of sea perch brain cells reveals the roles of microRNAs in autophagy induced by RGNNV infection - Peng Jia; Hongbo Pan; Kuopeng Cui; Kuntong Jia; Meisheng Yi (Journal of Fish Diseases, 2021)
Nervous necrosis virus (NNV) is one of the most destructive fish viruses and affects more than 120 marine and freshwater teleost species. However, the pathogenesis of NNV has not been made clear. MicroRNAs (miRNAs) play important roles in the regulation of viral infection. To understand the roles and regulation patterns of miRNAs in NNV infection, high‐throughput sequencing was carried out in Lateolabrax japonicus brain (LJB) cells with or without red‐spotted grouper NNV (RGNNV) infection at 12 and 24 hr. Here, we identified 59 known and 61 novel differentially expressed miRNAs (DE miRNAs) between mock and RGNNV‐infected LJB cells. KEGG pathway analysis showed that the target genes of DE miRNAs were significantly enriched in immune‐related signalling pathways, such as autophagy, mitophagy and TGF‐beta signalling pathways. The expression patterns of four DE miRNAs (lja‐miR‐145, lja‐miR‐182, lja‐miR‐183 and lja‐miR‐187) were verified by qRT‐PCR both in vivo and in vitro . We found that lja‐miR‐145 promoted RGNNV proliferation, while lja‐miR‐183 suppressed RGNNV proliferation. Furthermore, lja‐miR‐145 facilitated RGNNV‐induced autophagy activation, whereas lja‐miR‐183 repressed autophagy in LJB cells as measured by LC3B‐II/I and p62 protein levels. All these results indicate the involvement of lja‐miR‐145 and lja‐miR‐183 in RGNNV‐induced autophagy. In conclusion, this study provides evidence for the important roles of miRNAs in NNV infection and a basis for uncovering the molecular regulation mechanism of NNV‐induced autophagy.

Fluid Mobility Evaluation of Tight Sandstones in Chang 7 Member of Yanchang Formation, Ordos Basin - Songtao Wu; Shixiang Li; Xuanjun Yuan; Zhi Yang; Aifen Li; Jingwei Cui; Songqi Pan; Zhiguo Mao; Ling Su; You Zhou (Journal of Earth Science, 2021)

Calibrating receiver-type-dependent wide-lane uncalibrated phase delay biases for PPP integer ambiguity resolution - Bobin Cui; Pan Li; Jungang Wang; Maorong Ge; Harald Schuh (Journal of Geodesy, 2021)
Wide-lane (WL) uncalibrated phase delay (UPD) is usually derived from Melbourne–Wübbena (MW) linear combination and is a prerequisite in Global Navigation Satellite Systems (GNSS) precise point positioning (PPP) ambiguity resolution (AR). MW is a linear combination of pseudorange and phase, and the accuracy is limited by the larger pseudorange noise which is about one hundred times of the carrier phase noise. However, there exist inconsistent pseudorange biases which may have detrimental effect on the WL UPD estimation, and further degrade user-side ambiguity fixing. Currently, only the large part of pseudorange biases, e.g., the differential code bias (DCB), are available and corrected in PPP-AR, while the receiver-type-dependent biases have not yet been considered. Ignoring such kind of bias, which could be up to 20 cm, will cause the ambiguity fixing failure, or even worse, the incorrect ambiguity fixing. In this study, we demonstrate the receiver-type-dependent WL UPD biases and investigate their temporal and spatial stability, and further propose the method to precisely estimate these biases and apply the corrections to improve the user-side PPP-AR. Using a large data set of 1560 GNSS stations during a 30-day period, we demonstrate that the WL UPD deviations among different types of receivers can reach ± 0.3 cycles. It is also shown that such kind of deviations can be calibrated with a precision of about 0.03 cycles for all Global Positioning System (GPS) satellites. On the user side, ignoring the receiver-dependent UPD deviation can cause significant positioning error up to 10 cm. By correcting the deviations, the positioning performance can be improved by up to 50%, and the fixing rate can also be improved by 10%. This study demonstrates that for the precise and reliable PPP-AR, the receiver-dependent UPD deviations cannot be ignored and have to be handled.

Improved Crop Management Achieved High Wheat Yield and Nitrogen Use Efficiency - Tingyao Cai; Yongliang Chen; Junxiao Pan; Youliang Ye; Qi Miao; Hongyan Zhang; Zhenling Cui (International Journal of Plant Production, 2021)

Plant growth, ion accumulation, and antioxidant enzymes of endophyte-infected and endophyte-free tall fescue to salinity stress - Lu Pan; Shimao Cui; Randy D. Dinkins; Yiwei Jiang (Acta Physiologiae Plantarum, 2021)

Geochronology, geochemistry, and Hf isotopic compositions of Triassic igneous rocks in the easternmost segment of the East Kunlun Orogenic Belt, NW China: implications for magmatism and tectonic evolution - Dong-Qian Wu; Feng-Yue Sun; Zhong-Cui Pan; Nan Tian (International Geology Review, 2021)

Cytotoxic p -terphenyls from the deep-sea-derived Aspergillus candidus - Yu-Kun Lin; Chun-Lan Xie; Cui-Ping Xing; Bao-Qu Wang; Xiao-Xue Tian; Jin-Mei Xia; Ling-Yun Jia; Ying-Ni Pan; Xian-Wen Yang (Natural Product Research, 2021)

Diversity, metabolism and cultivation of archaea in mangrove ecosystems - Cui-Jing Zhang; Yu-Lian Chen; Yi-Hua Sun; Jie Pan; Ming-Wei Cai; Meng Li (Marine Life Science & Technology, 2021)

Gas Flow Characteristics and Optimization of Gas Drainage Borehole Layout in Protective Coal Seam Mining: A Case Study from the Shaqu Coal Mine, Shanxi Province, China - Zhiheng Cheng; Hui Pan; Quanle Zou; Zhenhua Li; Liang Chen; Jialin Cao; Kun Zhang; Yongguo Cui (Natural Resources Research, 2021)

Global patterns in leaf stoichiometry across coastal wetlands - Yu‐Kun Hu; Xu‐Yan Liu; Nian‐Peng He; Xu Pan; Song‐Yuan Long; Wei Li; Man‐Yin Zhang; Li‐Juan Cui (Global Ecology and Biogeography, 2021)
Aim Coastal wetlands provide crucial ecosystem functions and services, such as coastal protection, nutrient retention and C sequestration. Despite the important roles in global C, N and P cycling, the global variation in leaf stoichiometry across coastal wetlands remains unclear. Location Global. Time period 1980–2018. Major taxa studied Vascular plants. Methods By compiling a global dataset of 698 data records in 205 sites, we carried out systematic analyses of the world‐wide trends and their determinants of leaf element contents and ratios of plants across coastal wetlands. Results Leaf N and P contents increased significantly, but C:N, C:P and N:P ratios decreased with increasing latitude in coastal wetlands. The mean annual temperature was the predominant driver of leaf N, P and C:N, whereas soil N:P was a good predictor of leaf C:P and N:P ratios. Furthermore, N increased faster with P in plant leaves of coastal wetlands compared with terrestrial ecosystems. Within coastal wetlands, herb‐dominated salt marshes had a significantly higher leaf P content, lower leaf N:P ratio and lower scaling exponent of leaf N to P than tree‐dominated mangroves. Main conclusions The similar latitudinal patterns of leaf stoichiometry in coastal wetlands compared with terrestrial ecosystems reflected the similar influences of temperature. However, different slopes of leaf P and N:P ratios and N and P scaling relationships between these two ecosystems suggested that different salinity and tidal inundation levels result in different strategies of N and P use in coastal wetland plants. These differences in leaf stoichiometry between ecosystems and between different types of coastal wetlands might need to be emphasized in future biogeochemical modelling owing to their different roles in global nutrient and carbon cycling.

Study on Vibration Characteristics of Marine Centrifugal Pump Unit Excited by Different Excitation Sources - Cui Dai; Yuhang Zhang; Qi Pan; Liang Dong; Houlin Liu (Journal of Marine Science and Engineering, 2021)
In order to study the vibration mechanism of a marine centrifugal pump unit and explore the contribution of vibration caused by different vibration excitation sources, a marine centrifugal pump with a specific speed of 66.7 was used for research. A numerical calculation model of the flow field and electromagnetic field of the pump unit was established to analyze the frequency spectrum characteristics and contribution of pump unit vibration caused by different excitation sources. Using the modal superposition method, the vibration characteristics of the pump unit caused by fluid excitation and electromagnetic excitation were analyzed. The results show that the main frequency of pump unit vibration caused by fluid excitation was at the 1× blade passing frequency. The main frequency of pump unit vibration caused by electromagnetic excitation was at the 2× utility frequency. The contribution of different excitation sources to the vibration of marine centrifugal pump unit was in the following order: fluid excitation on the inner surface of the pump > electromagnetic excitation > fluid excitation in the impeller.

Docosahexaenoic Acid (DHA) Supplementation Alters Phospholipid Species and Lipid Peroxidation Products in Adult Mouse Brain, Heart, and Plasma - Grace Y. Sun; Michael K. Appenteng; Runting Li; Taeseon Woo; Bo Yang; Chao Qin; Meixia Pan; Magdalena Cieślik; Jiankun Cui; Kevin L. Fritsche; Zezong Gu; Matthew Will; et al. (NeuroMolecular Medicine, 2021)

Molecular evolution and pathogenicity of chicken anemia virus isolates in China - Yue Li; Nana Yan; Yongqiang Wang; Aijing Liu; Changjun Liu; Xingge Lan; Bo Yang; Yulong Gao; Honglei Gao; Xiaole Qi; Hongyu Cui; Kai Li; et al. (Archives of Virology, 2021)

Recent progress in the use of mitochondrial membrane permeability transition pore in mitochondrial dysfunction-related disease therapies - Yuting Cui; Mingyue Pan; Jing Ma; Xinhua Song; Weiling Cao; Peng Zhang (Molecular and Cellular Biochemistry, 2021)

LncRNA MALAT1 mediates doxorubicin resistance of hepatocellular carcinoma by regulating miR-3129-5p/Nova1 axis - Yongxian Cao; Feng Zhang; Haotian Wang; Chunhua Bi; Jinpeng Cui; Fenghai Liu; Huazheng Pan (Molecular and Cellular Biochemistry, 2021)

Three-Dimensional (3D)–Printed Zero-Order Released Platform: a Novel Method of Personalized Dosage Form Design and Manufacturing - Dongyang Fang; Yining Yang; Mengsuo Cui; Hao Pan; Lijie Wang; Pingfei Li; Wenjing Wu; Sen Qiao; Weisan Pan (AAPS PharmSciTech, 2021)

Nutrient Resorption from Leaves of Wetland Plants in a Constructed Wetland Depends on Green Leaf Nutrient Content and Life Form - Xu Pan; Yunmei Ping; Lijuan Cui; Xiaodong Zhang; Wei Li; Yukun Hu; Johannes H. C. Cornelissen (Wetlands, 2020)

Increased density of endosymbiotic Buchnera related to pesticide resistance in yellow morph of melon aphid - Shao-Kun Guo; Ya-Jun Gong; Jin-Cui Chen; Pan Shi; Li-Jun Cao; Qiong Yang; Ary Anthony Hoffmann; Shu-Jun Wei (Journal of Pest Science, 2020)

CSF Brain-Reactive Autoantibodies are Elevated in Patients with Viral Encephalitis - Zhong-Yuan Yu; Jian-Hong Wang; Wei-Wei Li; Ye-Ran Wang; Noralyn B. Mañucat-Tan; Jun Wang; Ju Wang; Gao-Yu Cui; Jie-Xiang Pan; Shui-Xian Zhang; Zu-Juan Liu; Liang Tan; et al. (Neuroscience Bulletin, 2020)

Gelsemine, a natural alkaloid extracted from Gelsemium elegans Benth. alleviates neuroinflammation and cognitive impairments in Aβ oligomer-treated mice - Liping Chen; Hanbo Pan; Yujing Bai; Huiqin Li; Wen Yang; Zhi-Xiu Lin; Wei Cui; Yan-Fang Xian (Psychopharmacology, 2020)

Improvement of water quality in the Pearl River Estuary, China: a long-term (2008–2017) case study of temporal-spatial variation, source identification and ecological risk of heavy metals in surface water of Guangzhou - Yan-ping Zhao; Rui Wu; Jin-li Cui; Shu-chai Gan; Jia-chuan Pan; Peng-ran Guo (Environmental Science and Pollution Research, 2020)

Thioredoxin-Interacting Protein (TXNIP) Regulates Parkin/PINK1-mediated Mitophagy in Dopaminergic Neurons Under High-glucose Conditions: Implications for Molecular Links Between Parkinson’s Disease and Diabetes - Cun-Jin Su; Zhu Shen; Ru-Xiao Cui; Ya Huang; De-Lai Xu; Feng-Lun Zhao; Jie Pan; Ai-Ming Shi; Tong Liu; Yun-Li Yu (Neuroscience Bulletin, 2020)

Study on the mechanism of the influence of flood storage at the end of the Three Gorges Reservoir on the phosphorus forms in the sediments of the tributary reservoir bay - Xinyuan Liu; Baozhu Pan; Linxu Song; Zhengjian Yang; Daobin Ji; Yujie Cui; Qingqing Su (Aquatic Sciences, 2020)

The effective use of camera traps to document the northernmost distribution of the western black crested gibbon in China - Yi-Hao Fang; Yan-Peng Li; Guo-Peng Ren; Zhi-Pang Huang; Liang-Wei Cui; Li-Xiang zhang; Paul A. Garber; Ru-Liang Pan; Wen Xiao (Primates, 2020)

MCL1 regulates cell death, tumor growth and chemosensitivity to sabutoclax in ovarian adenocarcinoma - Cui Li; Yuchun Song; Pan Li (Cell and Tissue Research, 2020)

Identification of a novel COL4A5 mutation in the proband initially diagnosed as IgAN from a Chinese family with X-linked Alport syndrome - Zhihui Li; Peng Zhu; Hui Huang; Ying Pan; Peng Han; Huanhuan Cui; Zhijuan Kang; Mai Xun; Yi Zhang; Saijun Liu; Jian Wang; Jing Wu (Science China Life Sciences, 2019)

Experimental Investigation on Hydrodynamic Coefficients of a Column-Stabilized Fish Cage in Waves - Yun-Peng Zhao; Qiu-Pan Chen; Chun-Wei Bi; Yong Cui (Journal of Marine Science and Engineering, 2019)
This study on hydrodynamic coefficients of a column-stabilized fish cage under wave action plays an important role in the anti-wave design of cages. The regular wave test was used to study the horizontal wave force of the jacket and column-stabilized fish cage under different wave heights, periods, and incident angles; the finite element model of the jacket and the column-stabilized fish cage was established according to the test model. On the basis of the calculation of the finite element model, combined with the wave force obtained from the experiment, the hydrodynamic coefficients of the structure was fitted by the least squares method, and then the drag force, inertial force, and total force of the structure under different conditions were calculated. The results show that the hydrodynamic coefficients of the jacket and netting under the wave condition were more obvious with the change of the KC number and wave incident angles. And as the wave height increased, the drag force, the inertial force, and the proportion of the drag force to the horizontal wave force both increased. When the wavelength was large, the same trend occured as the wave period increased. When the wave incident angles were different, the forces of the jacket and the column-stabilized fish cage were always small in lateral low-frequency waves, which is consistent with the change law of hydrodynamic coefficients of the jacket and netting.

Full-Scale Linear Cutting Tests to Propose Some Empirical Formulas for TBM Disc Cutter Performance Prediction - Yucong Pan; Quansheng Liu; Xingxin Peng; Qi Liu; Jianping Liu; Xing Huang; Xianze Cui; Tao Cai (Rock Mechanics and Rock Engineering, 2019)

Flexibility of 3D Extruded Printing for a Novel Controlled-Release Puerarin Gastric Floating Tablet: Design of Internal Structure - Pingfei Li; Shiming Zhang; Wenliang Sun; Mengsuo Cui; Haoyang Wen; Qijun Li; Weisan Pan; Xinggang Yang (AAPS PharmSciTech, 2019)

Physiological adaptations of Elymus dahuricus to high altitude on the Qinghai–Tibetan Plateau - Guowen Cui; Guoxu Ji; Shengyong Liu; Bing Li; Lu Lian; Wenhua He; Pan Zhang (Acta Physiologiae Plantarum, 2019)

Antagonistic activity of marine Streptomyces sp. S073 on pathogenic Vibrio parahaemolyticus - Mingxia Yang; Jun Zhang; Qiting Liang; Guanxin Pan; Jiachang Zhao; Miao Cui; Xinqing Zhao; Qizhong Zhang; Delin Xu (Fisheries Science, 2019)

Field-evolved resistance and cross-resistance of the two-spotted spider mite, Tetranychus urticae, to bifenazate, cyenopyrafen and SYP-9625 - Jin-Cui Chen; Ya-Jun Gong; Pan Shi; Ze-Hua Wang; Li-Jun Cao; Peng Wang; Shu-Jun Wei (Experimental and Applied Acarology, 2019)

Over-expression of Peach PpIAA19 in Tomato Alters Plant Growth, Parthenocarpy, and Fruit Shape - Yifeng Ding; Wenfang Zeng; Xiaobei Wang; Yan Wang; Liang Niu; Lei Pan; Zhenhua Lu; Guochao Cui; Guohuai Li; Zhiqiang Wang (Journal of Plant Growth Regulation, 2019)

Structure-Based Gastro-Retentive and Controlled-Release Drug Delivery with Novel 3D Printing - Haoyang Wen; Bosai He; Haoyu Wang; Fen Chen; Pingfei Li; Mengsuo Cui; Qijun Li; Weisan Pan; Xinggang Yang (AAPS PharmSciTech, 2019)

Allelopathic Effects on Microcystis aeruginosa and Allelochemical Identification in the Cuture Solutions of Typical Artificial Floating-Bed Plants - Li Zhou; Guifa Chen; Naxin Cui; Qi Pan; Xiangfu Song; Guoyan Zou (Bulletin of Environmental Contamination and Toxicology, 2019)

Lack of Association Between DNMT3B Polymorphisms and Sporadic Parkinson’s Disease in a Han Chinese Population - Hong Pan; Jun-Yi Shen; Juan-Juan Du; Shi-Shuang Cui; Jin Liu; Yi-Qi Lin; Yi-Xi He; Yang Fu; Chao Gao; Gen Li; Sheng-Di Chen; Jian-Fang Ma (Neuroscience Bulletin, 2018)

QTL for sensitivity of seedling height to exogenous GA 3 and their effects on adult plant height in common wheat - N. Zhang; R.Q. Pan; J.J. Liu; X.L. Zhang; Q.N. Su; F. Cui; C.H. Zhao; L.Q. Song; J. Ji; J.M. Li (Cereal Research Communications, 2018)

Characterization of a novel lytic podovirus O4 of Pseudomonas aeruginosa - Fenjiao Zhang; Kechong Huang; Xiaojing Yang; Li Sun; Jiajia You; Xuewei Pan; Xiaoli Cui; Hongjiang Yang (Archives of Virology, 2018)

Mechanical behavior and micro-structure of cement kiln dust-stabilized expensive soil - Su Li Cui; Jia Ding Wang; Xiao Dong Wang; Yan Feng Du; Xue Pan Wang (Arabian Journal of Geosciences, 2018)

Recombinant neuritin affects the senescence, apoptosis, proliferation, and migration of rat bone marrow-derived mesenchymal stem cells - Wumei Yuan; Lijuan Cui; Guoxiang Li; Na Wang; Pan Zhang; Yunhua Zhang; Na Yu; Hongying Wang; Jingling Zhu; Lei Yang; Jin Huang (Biotechnology Letters, 2017)

Natural and anthropogenic factors affecting the shallow groundwater quality in a typical irrigation area with reclaimed water, North China Plain - Xiaomin Gu; Yong Xiao; Shiyang Yin; Xingyao Pan; Yong Niu; Jingli Shao; Yali Cui; Qiulan Zhang; Qichen Hao (Environmental Monitoring and Assessment, 2017)

Methane enhances aluminum resistance in alfalfa seedlings by reducing aluminum accumulation and reestablishing redox homeostasis - Weiti Cui; Hong Cao; Ping Yao; Jincheng Pan; Quan Gu; Sheng Xu; Ren Wang; Zhaozeng Ouyang; Qingya Wang; Wenbiao Shen (BioMetals, 2017)

Cryopreservation of grapevine (Vitis spp.)—a review - Wen-Lu Bi; Chen Pan; Xin-Yi Hao; Zhen-Hua Cui; Mafatlal M. Kher; Zvjezdana Marković; Qiao-Chun Wang; Jaime A. Teixeira da Silva (In Vitro Cellular & Developmental Biology - Plant, 2017)

MiR-125a regulates mitochondrial homeostasis through targeting mitofusin 1 to control hypoxic pulmonary vascular remodeling - Cui Ma; Chen Zhang; Mingfei Ma; Lixin Zhang; Linlin Zhang; Fengying Zhang; Yingli Chen; Fangyuan Cao; Minghui Li; Guangtian Wang; Tingting Shen; Hongmin Yao; et al. (Journal of Molecular Medicine, 2017)

Two new biphenyls from the stems of Garcinia tetralata - Bing-Kun Ji; Xue-Mei Gao; Di Cui; Shan-Shan Wang; Wen-Zhong Huang; Yin-Ke Li; Shuang-Xi Mei; Zhi Yang; Gan-Peng Li; Meng-Yuan Jiang; Yong-Hui He; Zhi-Yong Jiang; et al. (Natural Product Research, 2017)

Characterization of the temporal and spatial expression of wheat (Triticum aestivum L.) plant height at the QTL level and their influence on yield-related traits - Na Zhang; Xiaoli Fan; Fa Cui; Chunhua Zhao; Wei Zhang; Xueqiang Zhao; Lijuan Yang; Ruiqing Pan; Mei Chen; Jie Han; Jun Ji; Dongcheng Liu; et al. (Theoretical and Applied Genetics, 2017)

Identification and Characterization of Chalcone Synthase Gene Family Members in Nicotiana tabacum - Shuai Chen; Xuhao Pan; Yiting Li; Lijie Cui; Yinchao Zhang; Zhiming Zhang; Guangtang Pan; Jun Yang; Peijian Cao; Aiguo Yang (Journal of Plant Growth Regulation, 2017)

N2O emission characteristics and its affecting factors in rain-fed potato fields in Wuchuan County, China - Liwei Wang; Cheng Wang; Zhihua Pan; Hui Xu; Lin Gao; Peiyi Zhao; Zhiqiang Dong; Jingting Zhang; Guohui Cui; Sen Wang; Guolin Han; hui Zhao (International Journal of Biometeorology, 2017)

Adsorption of Dioxin by Bag Filter + Powdered Activated Carbon - Yu-Yong Cui; Guo-Hua Yang; Gui-Hui Xiao; Jiang-Hua Zhou; Guo-Zhu Ding; Xue-Jun Pan (Water, Air, & Soil Pollution, 2017)

A Novel Wheat Nicotianamine Synthase Gene, TaNAS-D, Confers High Salt Tolerance in Transgenic Arabidopsis - Jie Han; Wei Zhang; Lijing Sun; Qiannan Su; Zijing Li; Xiaoli Fan; Na Zhang; Ruiqing Pan; Fa Cui; Jun Ji; Hui Li; Junming Li (Plant Molecular Biology Reporter, 2017)

Three new resin glycosides compounds from Argyreia acuta and their α -glucosidase inhibitory activity - Li Wang; You-Shao Yan; Hong-Hua Cui; Yong-Qin Yin; Jie-Tao Pan; Bang-Wei Yu (Natural Product Research, 2017)

The Rab1 in host cells modulates Brucella intracellular survival and binds to Brucella DnaK protein - Ning Liu; Changjiang Sun; Guimei Cui; Pan Wei; Li Yang; Wanchun Sun; Shuangxi Wang; Lin Wang; Qisheng Peng (Archives of Microbiology, 2016)

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

Phytotoxicity mechanisms of two coumarin allelochemicals from Stellera chamaejasme in lettuce seedlings - Zhiqiang Yan; Dandan Wang; Haiyan Cui; Denghong Zhang; Yuhe Sun; Hui Jin; Xiuzhuang Li; Xiaoyan Yang; Hongru Guo; Xiaofeng He; Le Pan; Xia Ren; et al. (Acta Physiologiae Plantarum, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Highly selective and efficient biotransformation of linarin to produce tilianin by naringinase - Pan Cui; Tong-Yi Dou; Shi-Yang Li; Jun-Xia Lu; Li-Wei Zou; Ping Wang; Yan-Ping Sun; Da-Cheng Hao; Guang-Bo Ge (Biotechnology Letters, 2016)

Breeding of an intraspecific kelp hybrid Dongfang no. 6 (Saccharina japonica, Phaeophyceae, Laminariales) for suitable processing products and evaluation of its culture performance - Xiaojie Li; Zhuangzhi Zhang; Shancun Qu; Guangjin Liang; Nan Zhao; Juan Sun; Shaofeng Song; Zengmei Cao; Xia Li; Jinhua Pan; Shiju Luo; Linan Zhang; et al. (Journal of Applied Phycology, 2016)

Two pentasaccharide resin glycosides from Argyreia acuta - Yong-Qin Yin; Jie-Tao Pan; Bang-Wei Yu; Hong-Hua Cui; You-Shao Yan; Yan-Fen Chen (Natural Product Research, 2016)

Trends in the prevalence of heart diseases over a ten-year period from single-center observations based on a large echocardiographic database - Hao Lu; Wen-zhi Pan; Quan Wan; Lei-lei Cheng; Xian-hong Shu; Cui-zhen Pan; Ju-ying Qian; Jun-bo Ge (Journal of Zhejiang University-SCIENCE B, 2016)

PEDF and 34-mer inhibit angiogenesis in the heart by inducing tip cells apoptosis via up-regulating PPAR-γ to increase surface FasL - Hao Zhang; Tengteng Wei; Xia Jiang; Zhimin Li; Huazhu Cui; Jiajun Pan; Wei Zhuang; Teng Sun; Zhiwei Liu; Zhongming Zhang; Hongyan Dong (Apoptosis, 2016)

Halorubrum rutilum sp. nov. isolated from a marine solar saltern - Shuai Yin; Zhao Wang; Jia-Qi Xu; Wen-Mei Xu; Pan-Pan Yuan; Heng-Lin Cui (Archives of Microbiology, 2015)

Association between Val66Met polymorphisms in brain-derived neurotrophic factor gene and asthma risk: a meta-analysis - Xinming Xie; Yanting Zhu; Jiaojiao Zhang; Cui Zhai; Wei Feng; Yilin Pan; Lu Liu; Xiaofan Su; Lan Yang; Manxiang Li (Inflammation Research, 2015)

MicroRNA expression profiles and networks in mouse lung infected with H1N1 influenza virus - Yanyan Bao; Yingjie Gao; Yahong Jin; Weihong Cong; Xin Pan; Xiaolan Cui (Molecular Genetics and Genomics, 2015)

Halorientalis brevis sp. nov., Isolated from an Inland Salt Lake of China - Pan-Pan Yuan; Shuai Yin; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Current Microbiology, 2015)

Haloarchaeobius amylolyticus sp. nov., isolated from a marine solar saltern - Pan-Pan Yuan; Xin-Juan Sun; Xi Liang; Xiao-Jing Chen; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Archives of Microbiology, 2015)

Transcriptome exploration for further understanding of the tropane alkaloids biosynthesis in Anisodus acutangulus - Lijie Cui; Fenfen Huang; Dasheng Zhang; Yuping Lin; Pan Liao; Jie Zong; Guoyin Kai (Molecular Genetics and Genomics, 2015)

Halosimplex litoreum sp. nov., isolated from a marine solar saltern - Pan-Pan Yuan; Jia-Qi Xu; Wen-Mei Xu; Zhao Wang; Shuai Yin; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Antonie van Leeuwenhoek, 2015)

Mid‐MIS3 climate inferred from reconstructing the Dalijia Shan ice cap, north‐eastern Tibetan Plateau - JIE WANG; HANG CUI; JONATHAN M. HARBOR; LIMIN ZHENG; PAN YAO (Journal of Quaternary Science, 2015)
The local last glacial maximum (LGM L ) on Dalijia Shan occurred during mid‐marine isotope stage 3 (MIS3), which is consistent with some Tibetan Plateau records, but asynchronous with the MIS2 global Last Glacial Maximum (LGM G ). Paleoclimatic reconstructions are key to advancing understanding such spatial and temporal patterns of paleoglaciation. Using multiple methods we reconstructed mid‐MIS3 equilibrium‐line altitude (ELA) on Dalijia Shan and inferred temperature depressions. Geomorphic ELA reconstructions combined with empirical data on current ELA temperature and precipitation yield a mid‐MIS3 ELA of 4000 ± 78 m a.s.l. (618–851 m lower than current, and a temperature depression of 3.3–6.8 °C). Independent glacial modeling using the degree‐day approach suggests a mid‐MIS3 ELA between 3971 and 4024 m a.s.l. and a temperature depression of 4.2–5.6 °C. The consistency of these results indicate that mid‐MIS3 temperature depressions in the Dalijia Shan region were 3.3–6.8 °C, which is less than the LGM G temperature depression inferred from regional climatic proxy data. Combined with other proxy data, this suggests that the LGM L glacial advance in Dalijia Shan resulted from lower temperatures and slightly reduced precipitation compared with present, whereas the LGM G advance was more restricted because much colder conditions were combined with much lower precipitation.

Effect of the Shenfu Injection Combined with Early Goal-Directed Therapy on Organ Functions and Outcomes of Septic Shock Patients - Mao-qin Li; Cui-gai Pan; Xiao-meng Wang; Xun Mo; Zai-xiang Shi; Ji-yuan Xu; Yan-jun Xu; Guan-jie Han (Cell Biochemistry and Biophysics, 2015)

Characterization of 1-aminocyclopropane-1-carboxylic acid synthase (ACS) genes during nectarine fruit development and ripening - Wenfang Zeng; Lei Pan; Hui Liu; Liang Niu; Zhenhua Lu; Guochao Cui; Zhiqiang Wang (Tree Genetics & Genomes, 2015)

Knockdown of NOB1 expression inhibits the malignant transformation of human prostate cancer cells - Xiangmin Zhang; Dongxu Zhang; Fajun Qu; Yi Hong; Jianwei Cao; Xiuwu Pan; Lin Li; Yi Huang; Hai Huang; Lei Yin; Lu Chen; Jizhong Ren; et al. (Molecular and Cellular Biochemistry, 2014)

Effects of Dietary Zinc Oxide Nanoparticles on Growth Performance and Antioxidative Status in Broilers - Cui-Yan Zhao; Shu-Xian Tan; Xi-Yu Xiao; Xian-Shuai Qiu; Jia-Qiang Pan; Zhao-Xin Tang (Biological Trace Element Research, 2014)

Characterizing the heavy metal-complexing potential of fluorescent water-extractable organic matter from composted municipal solid wastes using fluorescence excitation–emission matrix spectra coupled with parallel factor analysis - Xiao-Song He; Bei-Dou Xi; Hong-Wei Pan; Xiang Li; Dan Li; Dong-Yu Cui; Wen-Bin Tang; Ying Yuan (Environmental Science and Pollution Research, 2014)

Analysis of synonymous codon usage in enterovirus 71 - Hua Zhang; Hong-wei Cao; Feng-qi Li; Zi-ye Pan; Zhi-jun Wu; Yan-hong Wang; Yu-dong Cui (VirusDisease, 2014)

Influence of the composition and removal characteristics of organic matter on heavy metal distribution in compost leachates - Xiao-Song He; Bei-Dou Xi; Dan Li; Xu-Jing Guo; Dong-Yu Cui; Hong-Wei Pan; Yan Ma (Environmental Science and Pollution Research, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Reston virus in domestic pigs in China - Yangyang Pan; Wen Zhang; Li Cui; Xiuguo Hua; Meng Wang; Qiaoying Zeng (Archives of Virology, 2014)

Expression of Nemo-like kinase after spinal cord injury in rats - Dawei Xu; Wei Zhao; Gang Pan; Ming Qian; Xinhui Zhu; Wei Liu; Gang Cai; Zhiming Cui (Journal of Molecular Neuroscience, 2014)

Comparison of organic acid levels and L-IdnDH expression in Chinese-type and European-type grapes - Ya-Qin Wen; Jing Cui; Ye Zhang; Chang-Qing Duan; Qiu-Hong Pan (Euphytica, 2014)

Repairing cartilage defects with bone marrow mesenchymal stem cells induced by CDMP and TGF-β1 - Gang Wu; Ying Cui; Linxiang Ma; Xinyu Pan; Xuefeng Wang; Ben Zhang (Cell and Tissue Banking, 2014)

Biosynthesis of terephthalic acid, isophthalic acid and their derivatives from the corresponding dinitriles by tetrachloroterephthalonitrile-induced Rhodococcus sp. - Yu-Cai He; Ya-Dong Wu; Xue-He Pan; Cui-Luan Ma (Biotechnology Letters, 2014)

Natural antisense transcripts of UL123 packaged in human cytomegalovirus virions - Cui-Qing Yang; Ling-Feng Miao; Xing Pan; Cong-Cong Wu; Simon Rayner; Edward S. Mocarski; Han-Qing Ye; Min-Hua Luo (Archives of Virology, 2014)

Stress fermentation strategies for the production of hyperthermostable superoxide dismutase from Thermus thermophilus HB27: effects of ions - Hu Zhu; Jianguo Liu; Jianbo Qu; Xinliang Gao; Tao Pan; Zhanfeng Cui; Xiubo Zhao; Jian R. Lu (Extremophiles, 2013)

Late Quaternary glacial chronology on the eastern slope of Gongga Mountain, eastern Tibetan Plateau, China - Jie Wang; BaoTian Pan; GuoLiang Zhang; Hang Cui; Bo Cao; HaoPeng Geng (Science China Earth Sciences, 2013)

Increased expression of actin filament-stabilizing protein tropomyosin after rat traumatic brain injury - Xinmin Wu; Hongran Fu; Feihui Zou; Wei Jin; Ting Xu; Peipei Gong; Jian Xu; Yaohua Yan; Gang Cui; Kaifu Ke; Yilu Gao; Chunfeng Liu; et al. (Journal of Molecular Histology, 2013)

Transcriptome profiling of the developing postnatal mouse testis using next-generation sequencing - Wei Gong; LinLin Pan; Qiang Lin; YuanYuan Zhou; ChengQi Xin; XiaoMin Yu; Peng Cui; SongNian Hu; Jun Yu (Science China Life Sciences, 2013)

Antigenic and genetic characterization of a European avian-like H1N1 swine influenza virus from a boy in China in 2011 - Xian Qi; Lunbiao Cui; Yongjun Jiao; Yuning Pan; Xihan Li; Rongqiang Zu; Xiang Huo; Bin Wu; Fengyang Tang; Yongchun Song; Minghao Zhou; Hua Wang; et al. (Archives of Virology, 2013)

QTL mapping for nitrogen-use efficiency and nitrogen-deficiency tolerance traits in rice - Dong Wei; Kehui Cui; Guoyou Ye; Junfeng Pan; Jing Xiang; Jianliang Huang; Lixiao Nie (Plant and Soil, 2012)

Increased Th17 cell frequency concomitant with decreased Foxp3+ Treg cell frequency in the peripheral circulation of patients with carotid artery plaques - Zhen-dong Liu; Lin Wang; Fang-hong Lu; Hui Pan; Ying-xin Zhao; Shu-jian Wang; Shang-wen Sun; Cui-ling Li; Xiao-liang Hu (Inflammation Research, 2012)

Frequency and characterization of porcine hokovirus (PHoV) in domestic pigs in eastern China - Yangyang Pan; Qiaoying Zeng; Caixia Zhu; Xiuguo Hua; Meng Wang; Kaixuan Pan; Li Cui (Archives of Virology, 2012)

Low Selenium Diet Alters Cell Cycle Phase, Apoptotic Population and Modifies Oxidative Stress Markers of Spleens in Broilers - Xi Peng; Hengmin Cui; Jing Fang; Zhicai Zuo; Junliang Deng; Kangcheng Pan; Weimin Lai; Yi Zhou (Biological Trace Element Research, 2012)

High level expression and characterization of a thermostable lysophospholipase from Thermococcus kodakarensis KOD1 - Zhicheng Cui; Yuhan Wang; Bang Phuong Pham; Fangfang Ping; Hongyu Pan; Gang-Won Cheong; Shihong Zhang; Baolei Jia (Extremophiles, 2012)

Regulation of colon cancer cell migration and invasion by CLIC1-mediated RVD - Pan Wang; Chao Zhang; PeiWu Yu; Bo Tang; Tao Liu; Hao Cui; JianHua Xu (Molecular and Cellular Biochemistry, 2012)

Excess Dietary Sodium Selenite Alters Apoptotic Population and Oxidative Stress Markers of Spleens in Broilers - Xi Peng; Hengmin Cui; Yaxin He; Wei Cui; Jing Fang; Zhicai Zuo; Junliang Deng; Kangcheng Pan; Yi Zhou; Weimin Lai (Biological Trace Element Research, 2012)

Low-Selenium Diet Induces Cell Cycle Arrest of Thymocytes and Alters Serum IL-2 Content in Chickens - Xi Peng; Hengmin Cui; Jingxin Yuan; Wei Cui; Jing Fang; Zhicai Zuo; Junliang Deng; Kangcheng Pan; Yi Zhou; Weimin Lai (Biological Trace Element Research, 2011)

Highly efficient and catalyst-free synthesis of substituted thioureas in water - Shi-Feng Gan; Jie-Ping Wan; Yuan-Jiang Pan; Cui-Rong Sun (Molecular Diversity, 2011)

Fluid Dynamics Analysis of a Novel Micropatterned Cell Bioreactor - Yuhong Cui; Bo Huo; Shujin Sun; Fan Yang; Yuxin Gao; Jun Pan; Mian Long (Annals of Biomedical Engineering, 2011)

Eld’s Deer Translocated to Human-Inhabited Areas Become Nocturnal - Duo Pan; Liwei Teng; Fangjie Cui; Zhigao Zeng; Benjamin D. Bravery; Qiong Zhang; Yanling Song (Ambio, 2011)

Seedlings growth and antioxidative enzymes activities in leaves under heavy metal stress differ between two desert plants: a perennial (Peganum harmala) and an annual (Halogeton glomeratus) grass - Yan Lu; Xinrong Li; Mingzhu He; Xin Zhao; Yubing Liu; Yan Cui; Yanxia Pan; Huijuan Tan (Acta Physiologiae Plantarum, 2010)

High Mobility Group Box 1: a potential therapeutic target for systemic lupus erythematosus - Hai-Feng Pan; Guo-Cui Wu; Wei-Ping Li; Xiang-Pei Li; Dong-Qing Ye (Molecular Biology Reports, 2010)

Tourist behaviors in wetland park: A preliminary study in Xixi National Wetland Park, Hangzhou, China - Lili Pan; Lijuan Cui; Ming Wu (Chinese Geographical Science, 2010)

Increased serum interleukin 17 in patients with systemic lupus erythematosus - Xue-Fei Zhao; Hai-Feng Pan; Hui Yuan; Wen-Hui Zhang; Xiang-Pei Li; Gui-Hong Wang; Guo-Cui Wu; Hong Su; Fa-Ming Pan; Wen-Xian Li; Lian-Hong Li; Guo-Ping Chen; et al. (Molecular Biology Reports, 2010)

Preliminary studies on the chemical characterization and antioxidant properties of acidic polysaccharides from Sargassum fusiforme - Jing Zhou; Nan Hu; Ya-lin Wu; Yuan-jiang Pan; Cui-rong Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Spatio-temporal variation of stable isotopes of river waters, water source identification and water security in the Heishui Valley (China) during the dry-season - Yuhong Liu; Shuqing An; Zhen Xu; Ningjiang Fan; Jun Cui; Zhongsheng Wang; Shirong Liu; Jiayong Pan; Guanghui Lin (Hydrogeology Journal, 2008)

Characterization of a novel impurity in bulk drug of lisinopril by multidimensional NMR technique - Dan-hua Wang; Sai-feng Pei; Ming-hua Zhou; Cui-rong Sun; Yuan-jiang Pan (Journal of Zhejiang University-SCIENCE B, 2006)

Assessment on the commonweal values of wetlands - Li-juan Cui; Li-li Pan; Yan-bo Zhang (Chinese Geographical Science, 2000)